Secondary battery

By setting a shell layer on the surface of the positive electrode active material of the lithium-ion secondary battery and optimizing the electrode configuration, the problems of thermal runaway and long charging and discharging time of lithium-ion secondary battery are solved, and high safety and fast charging and discharging effects are achieved.

CN119318054APending Publication Date: 2025-01-14SEMICON ENERGY LAB CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202380045088.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-07-08
Filing Date
2023-06-16
Publication Date
2025-01-14

AI Technical Summary

Technical Problem

Existing lithium-ion secondary batteries are prone to thermal runaway during charging, and the charging and discharging time is long, making it difficult to achieve high safety and high-speed charging and discharging at the same time.

Method used

A winding type lithium ion secondary battery structure is adopted, in which the positive electrode active material includes lithium, cobalt and oxygen. A shell is provided on the surface of the positive electrode active material to increase the resistivity, and the configuration of the electrode ears is optimized to reduce the internal resistance.

Benefits of technology

It realizes high safety, fast charging and discharge and high capacity secondary batteries, reducing the risk of internal short circuit, avoiding thermal runaway and fire, and improving the reliability and efficiency of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119318054A_ABST
    Figure CN119318054A_ABST
Patent Text Reader

Abstract

Provided is a secondary battery that achieves both high safety and shortened charge / discharge time. The secondary battery is a winding type secondary battery, a positive electrode current collector of a positive electrode comprises a first tab and a second tab, and a negative electrode current collector of a negative electrode comprises a third tab and a fourth tab. The first tab is located at a portion closer to the winding center than the second tab, and the third tab is located at a portion closer to the winding center than the fourth tab. The first tab and the second tab are joined at a first joint part, and the third tab and the fourth tab are joined at a second joint part. The positive electrode active material includes a first region and a second region on a surface side of the positive electrode active material. The first region includes lithium, cobalt, and oxygen. The second region includes lithium, cobalt, magnesium, and oxygen.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] One embodiment of the present invention relates to a secondary battery. One embodiment of the present invention relates to a lithium ion secondary battery. One embodiment of the present invention relates to an electronic device including the secondary battery.

[0002] Note that one embodiment of the present invention is not limited to the above-mentioned technical field. As an example of the technical field of one embodiment of the present invention disclosed in this specification, etc., there can be cited semiconductor devices, display devices, light-emitting devices, power storage devices, storage devices, electronic devices, lighting devices, input devices, input-output devices, and driving methods or manufacturing methods thereof. Semiconductor devices refer to all devices that can work by utilizing semiconductor characteristics. Background Art

[0003] In recent years, research on various storage batteries such as lithium-ion secondary batteries, lithium-ion capacitors, air batteries and all-solid-state batteries has become increasingly popular. With the development of the semiconductor industry, the demand for high-output, large-capacity lithium-ion secondary batteries has increased dramatically. As a rechargeable energy supply source, it has become a necessity in the modern information society.

[0004] In particular, there is a great demand for lithium ion secondary batteries with large discharge capacity per unit weight and good cycle characteristics for portable electronic devices. Therefore, positive electrode active materials contained in the positive electrode of lithium ion secondary batteries are being actively improved (for example, see patent documents 1 to patent document 4, non-patent documents 1 to non-patent documents 4).

[0005] It is known that in lithium-ion secondary batteries, when the temperature rises during charging, they enter thermal runaway after passing through several states (Non-Patent Document 6). Various research and development have been conducted on the reliability and safety of lithium-ion secondary batteries. For example, Non-Patent Document 7 contains a record of the thermal stability of positive electrode active materials and electrolytes.

[0006] In addition, as the capacity of lithium ion secondary batteries increases, new problems include an increase in the time required for charging and discharging, etc. Therefore, secondary batteries that can be charged and discharged at a high speed are required.

[0007] [Prior technical literature]

[0008] [Patent Document]

[0009] [Patent Document 1] Japanese Patent Application Publication No. 2019-179758

[0010] [Patent Document 2] WO2020 / 026078 Pamphlet

[0011] [Patent Document 3] Japanese Patent Application Publication No. 2020-140954

[0012] [Patent Document 4] Japanese Patent Application Publication No. 2019-129009

[0013] [Non-patent literature]

[0014] [Non-patent document 1] Toyoki Okumura et al, "Correlation of lithium iondistribution and X-ray absorption near-edge structure in O3-and O2-lithiumcobalt oxides from first-principle calculation", Journal of MaterialsChemistry, 2012, 22, p.17340-17348

[0015] [Non-patent document 2] T. Motohashi, T. et al., "Electronic phase diagram of the layered cobalt oxide system Li x CoO2(0.0≤x≤1.0)”, Physical Review B, 80(16); 165114

[0016] [Non-patent document 3] Zhaohui Chen et al., “Staging Phase Transitions in Li x CoO2", Journal of The Electrochemical Society, 2002, 149(12)A1604-A1609

[0017] [Non-patent document 4] GG Amucci et al., "CoO2, The End Member of the Lix CoO2 Solid Solution" J. Electrochem. Soc. 143 (3) 1114 (1996).

[0018] [Non-patent document 5] A. Belsky, A. et al., "New developments in the InorganicCrystal Structure Database (ICSD): accessibility in support of materials research and design", Acta Cryst., (2002) B58 364-369.

[0019] [Non-patent document 6] Nobuo Eda, "2-4 Heat Generation Mechanisms", "Learning the Charging and Discharging Technology of Lithium-ion Batteries from Data" (<<Learning the Charging and Discharging Technology of Lithium-ion Batteries from Data>> 2-4 Heat Generation Mechanism), Japan CQ Publishing, April 4, 2020, pp. 68-72

[0020] [Non-patent document 7] Kitano Shinya et al. GS Yuasa Technical Report Vol. 2 No. 2 (GS Yuasa Technical Report Vol. 2 No. 2) December 2015 P18-24

[0021] [Non-patent document 8] Shannon et al., Acta Cryst. Section A, (1976) 32751. Summary of the invention

[0022] Technical problem to be solved by the invention

[0023] One of the purposes of one embodiment of the present invention is to provide a secondary battery with high safety. One of the purposes of one embodiment of the present invention is to provide a secondary battery capable of high-speed charge and discharge. One of the purposes of one embodiment of the present invention is to provide a secondary battery capable of achieving both high safety and shortened charge and discharge time. One of the purposes of one embodiment of the present invention is to provide a high-capacity secondary battery.

[0024] Note that the description of these purposes does not prevent the existence of other purposes. Note that one embodiment of the present invention does not necessarily achieve all of the above purposes. In addition, purposes other than the above can be extracted from the description of the specification, drawings, claims, etc.

[0025] Solutions to technical problems

[0026] One embodiment of the present invention is a wound secondary battery including a positive electrode and a negative electrode. The positive electrode includes a positive electrode collector and a positive electrode active material. The positive electrode collector includes a first pole ear and a second pole ear. The negative electrode includes a negative electrode collector and a negative electrode active material. The negative electrode collector includes a third pole ear and a fourth pole ear. The first pole ear is located at a portion closer to the winding center than the second pole ear. The third pole ear is located at a portion closer to the winding center than the fourth pole ear. The first pole ear is joined to the second pole ear at a first joint, and the third pole ear is joined to the fourth pole ear at a second joint. The positive electrode active material includes a first region and a second region located on the surface side of the positive electrode active material. The first region contains lithium, cobalt and oxygen. The second region contains lithium, cobalt, magnesium and oxygen.

[0027] Another embodiment of the present invention is a wound secondary battery including a positive electrode and a negative electrode. The positive electrode includes a positive electrode collector and a positive electrode active material. The positive electrode collector includes a first pole tab, a second pole tab, and a fifth pole tab. The negative electrode includes a negative electrode collector and a negative electrode active material. The negative electrode collector includes a third pole tab, a fourth pole tab, and a sixth pole tab. From the side close to the winding center, the first pole tab, the second pole tab, and the fifth pole tab are sequentially connected and connected at the first joint. From the side close to the winding center, the third pole tab, the fourth pole tab, and the sixth pole tab are sequentially connected and connected at the second joint. In the first joint, the first pole tab and the fifth pole tab are arranged in a manner of clamping the second pole tab, and in the second joint, the third pole tab and the sixth pole tab are arranged in a manner of clamping the fourth pole tab. The positive electrode active material includes a first region and a second region located on the surface side of the positive electrode active material. The first region contains lithium, cobalt, and oxygen. The second region contains lithium, cobalt, magnesium, and oxygen.

[0028] Another embodiment of the present invention is a wound secondary battery including a positive electrode and a negative electrode. The positive electrode includes a positive electrode collector and a positive electrode active material. The positive electrode collector includes a first pole tab, a second pole tab, and a fifth pole tab. The negative electrode includes a negative electrode collector and a negative electrode active material. The negative electrode collector includes a third pole tab, a fourth pole tab, and a sixth pole tab. From the side close to the winding center, the first pole tab, the second pole tab, and the fifth pole tab are sequentially connected and connected at the first joint. From the side close to the winding center, the third pole tab, the fourth pole tab, and the sixth pole tab are sequentially connected and connected at the second joint. In the first joint, the second pole tab and the fifth pole tab are arranged in a manner of clamping the first pole tab. In the second joint, the fourth pole tab and the sixth pole tab are arranged in a manner of clamping the third pole tab. The positive electrode active material includes a first region and a second region located on the surface side of the positive electrode active material. The first region contains lithium, cobalt, and oxygen. The second region contains lithium, cobalt, magnesium, and oxygen.

[0029] In any of the above structures, the thickness of the second region is preferably greater than or equal to 2 nm and less than or equal to 5 nm.

[0030] In any of the above structures, the second region preferably further contains nickel.

[0031] In any of the above structures, the second region preferably further contains fluorine.

[0032] In any of the above structures, the first region preferably further includes aluminum.

[0033] In any of the above structures, the second region is preferably located within a range of 5 nm from the surface of the positive electrode active material.

[0034] In any of the above structures, preferably, the volume resistivity of the powder of the positive electrode active material is 1.0×10 5 Ω·cm or more.

[0035] In any of the above structures, preferably, the volume resistivity of the powder of the positive electrode active material is 2.0×10 5 Ω·cm or more.

[0036] In any of the above structures, preferably, the volume resistivity of the powder of the positive electrode active material is 1.0×10 5 Ω·cm or more, and 2.0×10 5 Ω·cm or more.

[0037] Effects of the Invention

[0038] According to one embodiment of the present invention, a secondary battery with high safety can be provided. In addition, according to one embodiment of the present invention, a secondary battery capable of high-speed charge and discharge can be provided. In addition, according to one embodiment of the present invention, a secondary battery capable of achieving both high safety and shortened charge and discharge time can be provided. In addition, according to one embodiment of the present invention, a high-capacity secondary battery can be provided.

[0039] Note that the description of these effects does not prevent the existence of other effects. In addition, one mode of the present invention does not need to have all the above effects. In addition, effects other than the above can be extracted from the description of the specification, drawings, claims, etc. BRIEF DESCRIPTION OF THE DRAWINGS

[0040] Figure 1 is a diagram showing a structural example of a secondary battery.

[0041] Figure 2A and Figure 2B is a diagram showing a structural example of a secondary battery.

[0042] Figure 3is a diagram showing a structural example of a secondary battery.

[0043] Figure 4 is a diagram showing a structural example of a secondary battery.

[0044] Figure 5 is a diagram showing a structural example of a secondary battery.

[0045] Figure 6 is a diagram showing a structural example of a secondary battery.

[0046] Fig. 7A and Figure 7B It is a diagram showing a structural example of a positive electrode active material.

[0047] Fig. 8A and Figure 8B is a graph showing the internal temperature of the secondary battery.

[0048] Fig. 9A and Fig. 9B is a diagram illustrating a needle prick test.

[0049] FIG. 10A to FIG. 10F It is a diagram showing a structural example of a positive electrode active material.

[0050] Fig.11 It is a diagram showing a structural example of a positive electrode active material.

[0051] Fig.12 It is a diagram showing a structural example of a positive electrode active material.

[0052] Fig.13 is an example of a TEM image of a crystal.

[0053] Fig.14A is an example of a STEM image, Fig. 14B and Fig. 14C is an example of an FFT pattern.

[0054] Fig.15 is the XRD pattern.

[0055] Fig.16 is the XRD pattern.

[0056] Fig.17A and Fig. 17B is the XRD pattern.

[0057] 18A to 18C is a graph showing lattice constants.

[0058] Fig.19 It is a diagram showing a structural example of a positive electrode active material.

[0059] FIG. 20A to FIG. 20C It is a diagram for explaining a method for producing a positive electrode active material.

[0060] FIG. 21A to FIG. 21C It is a diagram for explaining a method for producing a positive electrode active material.

[0061] Fig. 22 It is a diagram for explaining a method for producing a positive electrode active material.

[0062] FIG. 23A to FIG. 23C It is a diagram for explaining a method for producing a positive electrode active material.

[0063] Fig.24 It is a diagram for explaining a heating furnace and a heating method.

[0064] FIG. 25A to FIG. 25D is a diagram showing a configuration example of an electronic device.

[0065] FIG. 26A to FIG. 26C is a diagram showing a configuration example of an electronic device.

[0066] FIG. 27A to FIG. 27C It is a diagram showing a structural example of a vehicle.

[0067] FIG. 28A to FIG. 28C This is an example of the structure of a measuring device.

[0068] Fig.29 is the measurement result of volume resistivity according to the example.

[0069] Fig.30 is the measurement result of volume resistivity according to the example. DETAILED DESCRIPTION

[0070] The following describes the embodiments with reference to the accompanying drawings. However, the embodiments can be implemented in a number of different ways, and a person skilled in the art can easily understand that the methods and details can be transformed into various forms without departing from the purpose and scope of the present invention. Therefore, the present invention should not be interpreted as being limited to the contents described in the embodiments shown below.

[0071] Note that in the structure of the invention described below, the same reference numerals are used in common between different drawings to represent the same parts or parts with the same function, and their repeated descriptions are omitted. In addition, when representing parts with the same function, the same hatching is sometimes used without adding a reference numeral in particular.

[0072] Note that in each of the drawings described in this specification, the size of each component, the thickness of a layer, and a region may be exaggerated for the sake of clarity. Therefore, the present invention is not limited to the sizes in the drawings.

[0073] The ordinal numbers such as “first” and “second” used in the present specification and the like are provided to avoid confusion among constituent elements and are not intended to limit the number of constituent elements.

[0074] In this specification, etc., the space group is represented by the short notation of the international symbol (or Hermann-Mauguin symbol). In addition, the Miller index is used to represent the crystal plane and the crystal direction. Each face representing the crystal plane is represented by "()". However, in this specification, etc., due to the symbol limitation in the patent application, sometimes - (minus sign) is attached before the number to represent the space group, crystal plane and crystal direction, instead of attaching a superscript horizontal line to the number. In addition, "[]" is used to represent the individual orientation of the orientation in the crystal, "<>" is used to represent the collective orientation of all equivalent crystal directions, "()" is used to represent the individual face of the crystal plane, and "{}" is used to represent the collective face with equivalent symmetry. In addition, in general, in order to facilitate the understanding of the structure, the trigonal system represented by the space group R-3m is represented by a compound hexagonal lattice of the hexagonal lattice. In this specification, etc., unless otherwise specified, the space group R-3m is also represented by a compound hexagonal lattice. In addition to (hkl), (hkil) is sometimes used as the Miller index. Here, i is -(h+k).

[0075] Note that in this specification, etc., particles are not limited to spherical shapes (circular cross-sectional shapes), and the cross-sectional shapes of each particle may be elliptical, rectangular, trapezoidal, triangular, a quadrilateral with curved corners, asymmetric shapes, etc., and each particle may also be of an amorphous shape.

[0076] In addition, the theoretical capacity of the positive electrode active material refers to the amount of electricity when all the lithium that can be inserted and removed in the positive electrode active material is removed. For example, the theoretical capacity of LiCoO2 is 274mAh / g, the theoretical capacity of LiNiO2 is 274mAh / g, and the theoretical capacity of LiMn2O4 is 148mAh / g.

[0077] In addition, by the x in the composition formula, such as Li x The x in CoO2 represents the amount of lithium that can be inserted and removed from the positive electrode active material. In the positive electrode active material of a lithium ion secondary battery, x = (theoretical capacity - charging capacity) / theoretical capacity. For example, when a lithium ion secondary battery using LiCoO2 as the positive electrode active material is charged to 219.2 mAh / g, it can be said that the positive electrode active material is Li 0.2 CoO2 or x = 0.2. x When x in CoO2 is small, for example, it means 0.1 <x≤0.24。

[0078] When properly synthesized lithium cobalt oxide substantially satisfies the stoichiometric ratio before being used in the positive electrode, the composition formula of the lithium cobalt oxide is LiCoO2 and x = 1. In addition, the composition formula of the lithium cobalt oxide in the lithium ion secondary battery at the end of discharge can also be said to be LiCoO2 and x = 1. Here, "end of discharge" refers to a state where the voltage becomes 3.0V or 2.5V or less at a current of less than 100mA / g, for example.

[0079] To calculate Li x The charge capacity and / or discharge capacity of x in CoO2 is preferably measured under conditions without or with little effect of decomposition by short circuit and / or electrolyte, etc. For example, data of lithium-ion secondary batteries whose capacity changes sharply as if they were short circuited cannot be used to calculate x.

[0080] The space group of a lithium ion secondary battery is identified by XRD, electron diffraction, neutron diffraction, etc. Therefore, in this specification, etc., "belonging to a certain space group" or "space group" means being identified as a certain space group.

[0081] In addition, when three layers of anions are stacked by deviation from each other like ABCABC, the structure is called a cubic closest packing structure. Therefore, anions do not necessarily form a cubic lattice. In addition, in fact, crystallization has defects, so the analysis results are not necessarily consistent with the theory. For example, spots may also appear at positions slightly different from the theoretical positions in FFT (Fast Fourier Transform) patterns of electron diffraction images or TEM (Transmission Electron Microscope: Transmission Electron Microscope) images. For example, when the orientation between the theoretical position is less than 5 degrees or less than 2.5 degrees, it can be said that there is a cubic closest packing structure.

[0082] The distribution of a certain element refers to a region where the element is continuously detected at a level higher than background noise when analyzed by an analysis method capable of spatially continuous analysis.

[0083] In addition, the positive electrode active material to which the additive element is added is sometimes referred to as a composite oxide, a positive electrode material, a positive electrode material for a lithium ion secondary battery, etc. In addition, the positive electrode active material of one embodiment of the present invention preferably includes any one or more of a compound, a composition, and a composite.

[0084] In addition, when describing the characteristics of each particle of the positive electrode active material in the following embodiments, it is not necessary for all particles to have the characteristics. For example, as long as 50% or more, preferably 70% or more, and more preferably 90% or more of the three or more positive electrode active material particles selected irregularly have the characteristics, it can be said that the characteristics of the positive electrode active material and the lithium ion secondary battery including the positive electrode active material are fully improved.

[0085] In addition, the internal short circuit and external short circuit of the lithium ion secondary battery can cause heat and fire in addition to causing defects in at least one of the charging and discharging operations of the lithium ion secondary battery. Therefore, in order to achieve a safe lithium ion secondary battery, it is preferred to suppress internal short circuits and external short circuits even at a high charging voltage. The positive electrode active material of one embodiment of the present invention suppresses internal short circuits even at a high charging voltage. Therefore, a lithium ion secondary battery that simultaneously achieves large discharge capacity and high safety can be manufactured. The internal short circuit of a lithium ion secondary battery refers to the phenomenon that the positive electrode and the negative electrode contact each other inside the battery. In addition, the external short circuit of a lithium ion secondary battery is a phenomenon that the positive electrode and the negative electrode contact each other outside the battery, assuming incorrect use.

[0086] Note that, unless otherwise specified, the materials (positive electrode active material, negative electrode active material, electrolyte, separator, etc.) included in the lithium-ion secondary battery in the state before degradation are described. In addition, the following situation is not referred to as degradation: the situation where the discharge capacity decreases due to aging treatment and burn-in treatment in the stage of manufacturing the lithium-ion secondary battery. For example, the following situation can be referred to as the state before degradation: the situation where the discharge capacity is more than 97% of the rated capacity of the lithium-ion secondary battery composed of a single cell or a battery pack. When using lithium-ion secondary batteries for portable devices, the rated capacity is based on JIS C 8711:2019. When using lithium-ion secondary batteries other than the above, it is not limited to the above-mentioned JIS specifications, but is based on various JIS, IEC specifications, etc. for electric vehicle propulsion and industrial use.

[0087] In this specification, etc., the state before deterioration of the materials included in the lithium-ion secondary battery is sometimes referred to as the initial article or the initial state, and the state after deterioration (the state where the discharge capacity is less than 97% of the rated capacity of the lithium-ion secondary battery) is sometimes referred to as the article in use or the state in use or the used article or the used state.

[0088] In this specification, etc., a lithium ion secondary battery refers to a battery using lithium ions as carrier ions, but the carrier ions of the present invention are not limited to lithium ions. For example, alkali metal ions or alkaline earth metal ions can be used as carrier ions of the present invention, and specifically sodium ions can be used. At this time, lithium ions can be referred to as sodium ions to understand the present invention. In addition, when there is no restriction on the carrier ions, it is sometimes referred to as a secondary battery.

[0089] (Implementation Method 1)

[0090] In this embodiment, a structural example of a secondary battery which is one embodiment of the present invention is described.

[0091] [Structural example of secondary battery]

[0092] Figure 1 A schematic diagram of a secondary battery 10 according to one embodiment of the present invention is shown. The secondary battery 10 includes a wound body in which a stacked body including a positive electrode 11, a negative electrode 12, and two separators 13 is wound. That is, the secondary battery 10 is a wound-type secondary battery.

[0093] The secondary battery 10 is contained in an outer package (not shown), and is sealed after an electrolyte solution containing a salt containing carrier ions is injected. As carrier ions contained in the electrolyte solution, lithium ions can be typically used. A secondary battery containing such lithium ions is called a lithium ion secondary battery.

[0094] From the viewpoint of lightweight, the outer package is preferably in the form of a film, and a secondary battery including a film-shaped outer package can be referred to as a laminated secondary battery. In addition, from the viewpoint of excellent cooling function, a laminated film of a polymer and a metal with good thermal conductivity can also be used as the outer package. Specifically, polypropylene and aluminum are preferably used as the polymer and the metal, respectively, and nylon or the like can also be provided on the outside of the outer package. In addition, a metal can can also be used as the outer package, and when a round can box is used, the battery is referred to as a coin-type secondary battery.

[0095] The positive electrode 11 includes a positive electrode current collector, both surfaces of which are coated with a positive electrode composition containing a positive electrode active material. In addition, the negative electrode 12 includes a negative electrode current collector, both surfaces of which are coated with a negative electrode composition containing a negative electrode active material. The separator 13 is disposed between the positive electrode 11 and the negative electrode 12, and has the function of preventing them from being electrically short-circuited.

[0096] like Figure 1As shown, the positive electrode 11 is preferably located outside the negative electrode 12. In addition, one surface of the positive electrode 11 is preferably located on the outermost surface of the winding body. At this time, part or all of the outermost surface of the winding body of the positive electrode 11 is preferably not coated with the positive electrode composition. Here, aluminum foil and copper foil can be typically used as the positive electrode collector and the negative electrode collector, respectively. At this time, in the case of using a laminate of aluminum foil and a resin film as an outer packaging body, it is possible that a part of the resin film is missing and the aluminum foil of the outer packaging body is in contact with the winding body. At this time, different types of metals sometimes corrode when they come into contact with each other, so the metal used for the outer packaging body and the metal located on the outermost surface of the winding body are preferably the same type of metal (here aluminum).

[0097] In addition, the width of the negative electrode 12 is preferably larger than that of the positive electrode 11. Furthermore, the width of the separator 13 is preferably larger than that of the negative electrode 12 and the positive electrode 11. Thus, the positive electrode 11 is provided so as to be surrounded by the negative electrode 12 via the separator 13, so that an internal short circuit between the positive electrode 11 and the negative electrode 12 can be prevented.

[0098] The positive electrode 11 includes two or more tabs 21. In addition, the negative electrode 12 includes two or more tabs 22. The tab 21 is a part of the positive electrode current collector, and the tab 22 is a part of the negative electrode current collector. The tabs 21 and 22 are made of different metals.

[0099] The plurality of tabs 21 are all protruding portions provided in the positive electrode current collector of the positive electrode 11. In the positive electrode current collector, the plurality of tabs 21 are provided so as to overlap with each other when the winding body is formed through the winding process. Similarly, in the negative electrode current collector of the negative electrode 12, the plurality of tabs 22 are provided so as to overlap with each other when the winding body is formed through the winding process.

[0100] All overlapping portions of the plurality of tabs 21 are bound and joined. The region including the portions where the plurality of tabs 21 are bound and joined is referred to as a joining portion 31. Similarly, all overlapping portions of the plurality of tabs 22 are also bound and joined, and the joined portion is referred to as a joining portion 32. As a joining method, for example, ultrasonic joining can be used. Figure 1 As shown, the joint part 31 and the joint part 32 preferably include a plurality of joint traces. Thus, high mechanical strength and low resistance can be achieved.

[0101] Note that, although not shown here, the lead wire may be connected to each of the plurality of tabs 21 and each of the plurality of tabs 22. For example, the lead wire connected to the positive electrode 11 may be joined to the plurality of tabs 21 at the same joint 31 or may be joined to the plurality of tabs 21 at a position different from the joint 31. The lead wire connected to the negative electrode 12 is similar.

[0102] It is important here that in manufacturing Figure 1In the winding process of the secondary battery shown, the stacked body including the positive electrode 11, the negative electrode 12 and the separator 13 is wound with extremely high accuracy compared to the conventional wound secondary battery to avoid positional deviation of the plurality of tabs 21 and the plurality of tabs 22. For example, even if the tension during winding is slightly deviated, the tabs 21 and 22 may come into contact.

[0103] Thus, when multiple tabs 21 and 22 are provided, multiple current paths are provided compared to a secondary battery including one tab 21 and one tab 22, so the internal resistance of the secondary battery is reduced, and it is easy to realize high-speed charging and discharging. In addition, current concentration during charging and discharging can be suppressed, thereby preventing local high temperature, thereby achieving high safety and suppressing degradation.

[0104] Here, as the positive electrode active material contained in the positive electrode 11, it is preferred to use a positive electrode active material of one embodiment of the present invention having a high resistance region in a region closer to the surface than the center portion or in a surface layer portion including the surface. By using such a positive electrode active material, even if the positive electrode 11 and the negative electrode 12 are short-circuited, the current flowing through the positive electrode active material can be reduced, thereby suppressing fire or smoke, etc., so it is preferred. That is, a secondary battery of one embodiment of the present invention containing such a positive electrode active material can realize a secondary battery that is not easy to burn or does not burn even if an internal short circuit or an external short circuit occurs.

[0105] By adopting this structure, a secondary battery 10 that is highly safe and has a shortened charge and discharge time can be realized. In addition, since it is highly safe and can be charged and discharged at a high speed, it is possible to further achieve a high capacity. For example, in the case where a plurality of batteries (secondary batteries) are used together as a module, the capacity of a battery can be increased, so the number of batteries in each module can be reduced, which not only has the cost advantage of reducing the number of components, but also can achieve lightweight modules.

[0106] Next, a more specific example of the structure of the tab included in the secondary battery 10 will be described.

[0107] Figure 2A 1 is a perspective view of a secondary battery 10a before the tabs are joined. Figure 2B yes Figure 2A An enlarged view of the portion including the tab 22 and the tab 21. Note that Figure 2A and Figure 2B In order to facilitate understanding of the positions and shapes of the positive electrode 11 and the negative electrode 12 , the separator 13 is not shown, but in fact, the separator 13 is provided between the positive electrode 11 and the negative electrode 12 .

[0108] like Figure 2BAs shown, here, an example is shown in which the positive electrode 11 includes four tabs (tabs 21_1 to 21_4) and the negative electrode 12 also includes four tabs (tabs 22_1 to 22_4). Note that the number of tabs is not limited to this, as long as there are two or more tabs each.

[0109] exist Figure 2B In the figure, the two ends of the positive electrode 11 (end 11a, end 11b) and the two ends of the negative electrode 12 (end 12a, end 12b) are shown by arrows. End 11a and end 12a are both ends located on one side of the winding center, and end 11b and end 12b are ends located on the outside of the winding. Here, the winding center can also be represented as the center of the spiral, which can be the area including end 11a and end 12a. Note that the secondary battery illustrated here is flat rather than cylindrical, so the cross-section of the winding body is not a simple turbine shape.

[0110] The positive electrode 11 has four tabs 21_1, 21_2, 21_3, and 21_4 arranged in order from the end 11a to the end 11b. The four tabs are arranged in order from the side close to the winding center.

[0111] Similarly, in the negative electrode 12, four tabs 22_1, 22_2, 22_3, and 22_4 are provided in order from the end 12a to the end 12b. The four tabs are arranged in order from the side close to the winding center.

[0112] Figure 3 An enlarged view of the secondary battery 10a after joining is shown. The tabs 21_1 to 21_4 of the positive electrode 11 are joined at the joining portion 31. In addition, the tabs 22_1 to 22_4 of the negative electrode 12 are joined at the joining portion 32. The joining portion 31 includes a portion where all the tabs of the positive electrode 11 overlap, and the joining portion 32 includes a portion where all the tabs of the negative electrode overlap. The joining portion 31 and the joining portion 32 are each provided with a plurality of joining marks 35.

[0113] exist Figure 3 In the embodiment, the pole tab 21_2 is located between the pole tab 21_1 and the pole tab 21_3, and the pole tab 21_3 is located between the pole tab 21_2 and the pole tab 21_4. Similarly, the pole tab 22_2 is located between the pole tab 22_1 and the pole tab 22_3, and the pole tab 22_3 is located between the pole tab 22_2 and the pole tab 22_4.

[0114] Figure 3The structure shown is an example in which one tab is arranged per turn of the positive electrode 11 and the negative electrode 12. Therefore, since the tab is arranged only on one side of the wound body with the center as the reference, the thickness of the joint 31 and the joint 32 can be reduced.

[0115] Figure 4 An example is shown in which one tab is arranged per half turn on both the positive electrode 11 and the negative electrode 12 of the secondary battery 10 b.

[0116] The positive electrode 11 includes seven electrode tabs (electrode tabs 21_1 to 21_7 ), and the negative electrode 12 also includes seven electrode tabs (electrode tabs 22_1 to 22_7 ).

[0117] In the positive electrode 11, seven tabs are provided in the order of tab 21_1 to tab 21_7 from the end 11a to the end 11b along the winding direction. In addition, tab 21_1 is located between tab 21_2 and tab 21_3. In addition, seven tabs are stacked in the order of tab 21_4, tab 21_2, tab 21_1, tab 21_3, tab 21_5, and tab 21_7 from tab 21_6 to tab 21_7. That is, there is a portion where even-numbered tabs are stacked and a portion where odd-numbered tabs are stacked, with tab 21_1 as the center.

[0118] The negative electrode 12 is similar to the positive electrode 11, and also has tabs 22_1 to 22_7 sequentially arranged along the winding direction from the end 12a to the end 12b. In addition, the tab 22_1 is located between the tab 22_2 and the tab 22_3. In addition, seven tabs are stacked in the order of tab 22_4, tab 22_2, tab 22_1, tab 22_3, tab 22_5, and tab 22_7 from the tab 22_6 to the tab 22_7.

[0119] Compared with the secondary battery 10a, the intervals between the tabs in the secondary battery 10b are narrower, so that not only the internal resistance can be reduced more effectively, but also the heat generation can be suppressed more effectively.

[0120] Figure 5 The secondary battery 10c shown is Figure 3 The main difference of the secondary battery 10 a shown is that the positions of the plurality of tabs included in the negative electrode 12 are different.

[0121] The tabs 22_2 to 22_4 included in the negative electrode 12 are arranged on the opposite side of the tabs included in the positive electrode 11 of the wound body in a manner of sandwiching the center of the wound body. By adopting this structure, the physical distance between the tabs included in the positive electrode 11 and the tabs included in the negative electrode 12 can be increased, thereby effectively suppressing the external short circuit caused by their contact.

[0122] Note that the number of tabs, the positions of the tabs, the arrangement method of the tabs, etc. in the above-exemplified structures are merely examples, and various structures may be adopted depending on the application.

[0123] [Ear]

[0124] Figure 6 FIG. 2 shows the transition of the stack of the positive electrode 11 and the negative electrode 12 from the state before winding to the state after winding. Figure 6 , six states are shown in chronological order from upper left to lower right.

[0125] Note that although Figure 6 Although omitted in the figure, the laminate includes two separators to insulate the positive electrode 11 from the negative electrode 12. In this case, the following structure may be adopted: the first separator, the positive electrode 11, the second separator, and the negative electrode 12 are sequentially stacked as the laminate before winding, and the positive electrode 11 is sandwiched between the two separators. In this case, the following structure may be adopted: a separator formed by folding a separator that is longer in the long side direction of the laminate in half is used instead of the two separators, and the positive electrode 11 is sandwiched in such a way that the fold of the separator is located on the side of the end 11a of the positive electrode 11.

[0126] Alternatively, a structure may be adopted in which the positive electrode 11, the first separator, the negative electrode 12, and the second separator are sequentially stacked as a laminate before winding, and the two separators sandwich the negative electrode 12. In this case, a structure may be adopted in which, as in the above, the negative electrode 12 is sandwiched by using a long separator in such a way that the fold is located on the side of the end 12a of the negative electrode.

[0127] Before winding ( Figure 6 In the upper left state, the positive electrode 11 includes five tabs (tab 21_1 to tab 21_5) from the end 11a to the end 11b. The negative electrode 12 includes five tabs (tab 22_1 to tab 22_5) from the end 12a to the end 12b.

[0128] The 10 tabs included in the stacked body are arranged in order from the end 11a (end 12a) side as tab 22_1, tab 21_1, tab 21_2, tab 22_2, tab 22_3, tab 21_3, tab 21_4, tab 22_4, tab 22_5, and tab 21_5.

[0129] Two adjacent tabs are arranged so that the closer they are to the center of the winding, the smaller the distance between them is, and the farther they are toward the outside of the winding, the larger the distance between them is. For example, when the distance between the tab 21_1 and the tab 21_2 is set to X1 and the distance between the tab 21_3 and the tab 21_4 is set to X2, X2 is greater than X1. Similarly, when the distance between the tab 22_2 and the tab 22_3 is set to Y1 and the distance between the tab 22_4 and the tab 22_5 is set to Y2, Y2 is greater than Y1.

[0130] When winding the laminate, it is important to adjust the winding conditions in such a way that the tabs included in the positive electrode 11 overlap each other and the tabs included in the negative electrode 12 overlap each other. For example, winding is performed while adjusting the tension of each of the positive electrode 11, the negative electrode 12, and the two separators. Thus, at the end of the winding process, a wound body can be obtained in which all the tabs included in the positive electrode 11 overlap each other and all the tabs included in the negative electrode 12 overlap each other. Then, the wound body can also be fixed using a flame-retardant tape (e.g., a polyimide tape) to maintain this state.

[0131] [Each component]

[0132] {positive electrode}

[0133] Fig. 7A An example of a cross-sectional view of a positive electrode 11 used in a secondary battery 10 or the like is shown. The positive electrode 11 includes a positive electrode active material layer 502 on a positive electrode current collector 501. The positive electrode active material layer 502 includes a positive electrode active material 561, a positive electrode active material 562, a conductive material 553, a conductive material 554, and an electrolyte 530. The positive electrode active material layer 502 further includes a binder (not shown). The secondary battery may also have a structure including either the conductive material 553 or the conductive material 554.

[0134] In order to increase the packing density, it is preferable to include positive electrode active materials having different median particle sizes (D50). Here, an example is shown that includes at least positive electrode active material 561 and positive electrode active material 562 having a smaller median particle size (D50) than positive electrode active material 561.

[0135] The median particle size (D50) of the positive electrode active material 561 is greater than 1 μm and less than 50 μm, preferably greater than 5 μm and less than 30 μm. The median particle size (D50) of the positive electrode active material 562 is preferably greater than 1 / 6 and less than 1 / 10 of the median particle size (D50) of the positive electrode active material 561. When the particle size distribution of the active material mixed with the positive electrode active material 561 and the positive electrode active material 562 is measured, two peaks with different maximum values ​​are confirmed. Of course, more than two peaks can also be confirmed. Note that the packing density can be increased even if the positive electrode active material 562 is not included.

[0136] The positive electrode active material 561 and the positive electrode active material 562 preferably both include a shell. The positive electrode active material including a shell can improve insulation and is not prone to thermal runaway. Fig. 7A The boundary between the surface and the interior is marked with a dotted line, but the boundary is not necessarily Fig. 7A The positive electrode active material is not limited to Fig. 7A For example, either the positive electrode active material 561 or the positive electrode active material 562 may include a shell.

[0137] The active material of the positive electrode active material 561 may be the same as or different from the active material of the positive electrode active material 562. The same active material includes materials with the same main raw material of the active material, which may or may not have added elements, etc. Different active material includes materials with different main raw materials of the active material.

[0138] The positive electrode active material 561 and the positive electrode active material 562 preferably contain an additive element, and it is particularly preferred that the additive element is contained in the shell. The additive element contained in the shell can be distributed in a concentrated manner or sparsely distributed inside. Concentrated distribution means that the additive element is unevenly distributed or exists in a concentrated manner. Therefore, sometimes the state in which the concentration of the additive element increases from the inside to the shell is referred to as the additive element being concentratedly distributed in the shell. Concentrated distribution can also be recorded as segregation or precipitation.

[0139] The positive electrode active material 561 and the positive electrode active material 562 are referred to as positive electrode active material particles. The shape of the positive electrode active material can be various shapes other than particle shape. For example, Fig. 7A An example is shown in which the positive electrode active material is spherical and its cross section is circular. Figure 7B An example in which the cross section is not circular is shown.

[0140] Fig. 7A and Figure 7B The positive electrode active material 561 and the positive electrode active material 562 shown are examples of primary particles, but they may also be secondary particles. In this specification, a primary particle refers to a particle (block) that is the smallest unit without a grain boundary when observed using a SEM (scanning electron microscope), for example, at a magnification of 5000. That is, a primary particle is a particle of the smallest unit. In addition, a secondary particle refers to a particle (a particle independent of other particles) in which the above-mentioned primary particles are aggregated in a manner that shares a part of the above-mentioned grain boundary (the periphery of the primary particle, etc.). That is, the secondary particle has a grain boundary. The surface portion of the secondary particle may also be the surface portion of the entire secondary particle. In addition, the surface portion of the secondary particle may also be the surface portion of the primary particle that constitutes the secondary particle.

[0141] Furthermore, the above-mentioned positive electrode active material and other positive electrode active materials may be mixed and used.

[0142] As other positive electrode active materials, there are composite oxides having an olivine crystal structure, a layered rock salt crystal structure or a spinel crystal structure, etc. For example, compounds such as LiFePO4, LiFeO2, LiNiO2, LiMn2O4, V2O5, Cr2O5, and MnO2 can be cited.

[0143] In addition, as other positive electrode active materials, it is preferable to mix a lithium-containing material having a spinel-type crystal structure containing manganese such as LiMn2O4 with lithium nickelate (LiNiO2 or LiNi 1-x M x O2 (0 < x < 1) (M = Co, Al, etc.)). By adopting this structure, the characteristics of the secondary battery can be improved.

[0144] In addition, as other positive electrode active materials, a lithium manganese composite oxide represented by the compositional formula Li a Mn b M c O d can be used. Here, the element M is preferably a metal element selected from metal elements other than lithium and manganese, or silicon or phosphorus, and more preferably nickel. In addition, when measuring the entire particle of the lithium manganese composite oxide, it is preferably satisfied that 0 < a / (b + c) < 2, c > 0, and 0.26 ≤ (b + c) / d < 0.5 during discharge. The composition of metals, silicon, phosphorus, etc. of the entire particle of the lithium manganese composite oxide can be measured by, for example, ICP-MS (inductively coupled plasma mass spectrometry). In addition, the composition of oxygen of the entire particle of the lithium manganese composite oxide can be measured by, for example, EDX (energy dispersive X-ray analysis). In addition, it can also be calculated by using valence evaluation of fusion gas analysis and XAFS (X-ray absorption fine structure) analysis together with ICP-MS analysis. Note that the lithium manganese composite oxide refers to an oxide containing at least lithium and manganese, and may also contain one or more elements selected from the group consisting of chromium, cobalt, aluminum, nickel, iron, magnesium, molybdenum, zinc, indium, gallium, copper, titanium, niobium, silicon, and phosphorus.

[0145] {Conductive material}

[0146] The conductive material serves to assist the current path between the active material and the current collector or the current path between multiple active materials. In order to serve such a role, the conductive material preferably contains a material having a lower resistance than the active material. The conductive material is sometimes referred to as a conductive aid or a conductivity imparting agent depending on its role.

[0147] Typically, carbon materials or metal materials are used as the conductive material. For example, as granular conductive materials, there are carbon blacks (furnace black, acetylene black, graphite, etc.). There is a relatively large amount of carbon black having a smaller particle size than the positive electrode active material. In addition, the conductive material can also be fibrous. For example, as fibrous conductive materials, there are carbon nanotubes (CNT) and VGCF (registered trademark). In addition, the conductive material can also be flaky, for example, there is multilayer graphene. In the cross-section of the positive electrode, the flaky conductive aid is sometimes observed as a line.

[0148] The granular conductive material can enter the gap between the positive electrode active material and the like and easily aggregate. Therefore, the granular conductive material can assist the conductive path between the positive electrode active materials disposed near it. Although it has a bending area, the fibrous conductive material is larger than the positive electrode active material. Therefore, the fibrous conductive material can assist the conductive path between the separated positive electrode active materials in addition to the adjacent positive electrode active materials. In this way, the shape of the conductive material preferably mixed is two or more.

[0149] Fig. 7A and Figure 7B The positive electrode active material layer 502 is shown as an example in which a thin sheet of graphene or a graphene compound is included as the conductive material 554. In addition, as the conductive material 553, for example, carbon black can be used. Fig. 7A and Figure 7B In the figure, the conductive material 554 is schematically shown as a thick line, but in fact the conductive material 554 is an extremely thin film having a thickness of a single layer or a multilayer carbon molecule. Since a plurality of graphenes or graphene compounds are formed in a manner covering a portion of a plurality of positive electrode active materials or in a manner attached to the surface of a plurality of positive electrode active materials, a conductive path can be efficiently formed even in a small amount, so the internal resistance can be reduced.

[0150] {Adhesive}

[0151] The adhesive is used as a binder, which does not cover the surface of the active material but ensures the adhesion of the active material in powder state. Considering the expansion of the active material, the adhesive is preferably sufficiently flexible and preferably responds to the state change of the active material. The adhesive also needs to be compatible with the electrolyte. In addition, violent oxidation and reduction reactions occur in secondary batteries, so an adhesive that does not deteriorate or has low reactivity relative to the reaction is required.

[0152] As the adhesive, for example, preferably used are rubber materials such as styrene-butadiene rubber (SBR), styrene-isoprene-styrene rubber, acrylonitrile-butadiene rubber, butadiene rubber, ethylene-propylene-diene copolymer, etc. Fluorine rubber can also be used as the adhesive.

[0153] In addition, as a binder, for example, a water-soluble polymer is preferably used. As a water-soluble polymer, for example, polysaccharides can also be used. As polysaccharides, one or more of cellulose derivatives such as carboxymethyl cellulose (CMC), methyl cellulose, ethyl cellulose, hydroxypropyl cellulose, diacetyl cellulose, regenerated cellulose, and starch can be used. It is more preferred to use these water-soluble polymers and the above-mentioned rubber material in combination.

[0154] Alternatively, as an adhesive, it is preferred to use materials such as polystyrene, polymethyl acrylate, polymethyl methacrylate (PMMA), sodium polyacrylate, polyvinyl alcohol (PVA), polyethylene oxide (PEO), polypropylene oxide, polyimide, polyvinyl chloride, polytetrafluoroethylene, polyethylene, polypropylene, polyisobutylene, polyethylene terephthalate, nylon, polyvinylidene fluoride (PVDF), polyacrylonitrile (PAN), ethylene propylene diene polymer, polyvinyl acetate, and nitrocellulose.

[0155] {Positive electrode current collector}

[0156] As the positive electrode current collector, materials with high conductivity such as stainless steel, gold, platinum, copper, aluminum, titanium and their alloys can be used. In addition, the material used for the positive electrode current collector is preferably not dissolved due to the potential of the positive electrode. In addition, aluminum alloys to which elements such as silicon, titanium, neodymium, scandium, molybdenum and the like are added to improve heat resistance can be used. As the current collector, shapes such as foil, plate, sheet, mesh, punched metal mesh, drawn metal mesh can be appropriately used. The thickness of the current collector is preferably 5 μm or more and 30 μm or less.

[0157] {negative electrode}

[0158] The negative electrode includes a negative electrode active material layer and a negative electrode current collector. The negative electrode active material layer may also include a conductive material and a binder. As the negative electrode active material, for example, alloy materials or carbon materials may be used.

[0159] As the negative electrode active material, an element that can perform a charge and discharge reaction by alloying / de-alloying reaction with lithium can be used. For example, a material containing one or more selected from silicon, tin, gallium, aluminum, germanium, lead, antimony, bismuth, silver, zinc, cadmium and indium can be used. The charge and discharge capacity of this element is larger than that of carbon, and in particular, the theoretical capacity of silicon is large, which is 4200mAh / g. Therefore, silicon is preferably used for the negative electrode active material. In addition, compounds containing these elements can also be used. For example, SiO, Mg2Si, Mg2Ge, SnO, SnO2, Mg2Sn, SnS2, V2Sn3, FeSn2, CoSn2, Ni3Sn2, Cu6Sn5, Ag3Sn, Ag3Sb, Ni2MnSb, CeSb3, LaSn3, La3Co2Sn7, CoSb3, InSb and SbSn can be cited. Elements that can undergo charge and discharge reactions through alloying / de-alloying reactions with lithium, compounds containing the elements, and the like are sometimes referred to as alloy-based materials.

[0160] As the carbon-based material, graphite, easily graphitizable carbon (soft carbon), hardly graphitizable carbon (hard carbon), carbon nanotube, graphene, carbon black, and the like can be used.

[0161] In addition, as the negative electrode active material, oxides such as titanium dioxide (TiO2), lithium titanium oxide (Li4Ti5O 12 ), lithium-graphite intercalation compound (Li x C6), niobium pentoxide (Nb2O5), tungsten oxide (WO2), molybdenum oxide (MoO2), etc.

[0162] In addition, as the negative electrode active material, Li 3 N type structure containing lithium and transition metal nitride can be used. 3-x M x N (M = Co, Ni, Cu). For example, Li 2.6 Co 0.4 N3 shows a large charge and discharge capacity (900 mAh / g, 1890 mAh / cm 3 ), so it is preferred.

[0163] When a nitride containing lithium and a transition metal is used as the negative electrode active material, lithium ions are contained in the negative electrode active material, so the negative electrode active material can be combined with a material that does not contain lithium ions, such as V2O5 and Cr3O8, which is used as a positive electrode active material, so it is preferred. Note that when a material containing lithium ions is used as a positive electrode active material, a nitride containing lithium and a transition metal can also be used as a negative electrode active material by previously removing the lithium ions contained in the positive electrode active material.

[0164] In addition, materials that cause conversion reactions can also be used as negative electrode active materials. For example, transition metal oxides that do not form alloys with lithium, such as cobalt oxide (CoO), nickel oxide (NiO), and iron oxide (FeO), can be used as negative electrode active materials. Materials that cause conversion reactions can also include oxides such as Fe2O3, CuO, Cu2O, RuO2, and Cr2O3, CoS 0.89 , sulfides such as NiS, CuS, nitrides such as Zn3N2, Cu3N, Ge3N4, phosphides such as NiP2, FeP2, CoP3, fluorine compounds such as FeF3, BiF3.

[0165] As the conductive material and the binder which may be contained in the negative electrode active material layer, the same conductive material and the binder which may be contained in the positive electrode active material layer may be used.

[0166] {Negative electrode current collector}

[0167] As the negative electrode current collector, the same material as the positive electrode current collector can be used. In addition, as the negative electrode current collector, it is preferable to use a material that does not alloy with carrier ions such as lithium.

[0168] {Electrolyte}

[0169] The electrolyte includes a solvent and a lithium salt. As the solvent of the electrolyte, an aprotic organic solvent is preferably used, for example, ethylene carbonate (EC), propylene carbonate (PC), butylene carbonate, vinyl chloride carbonate, vinylene carbonate, γ-butyrolactone, γ-valerolactone, dimethyl carbonate (DMC), diethyl carbonate (DEC), ethyl methyl carbonate (EMC), methyl formate, methyl acetate, ethyl acetate, methyl propionate, ethyl propionate, propyl propionate, methyl butyrate, 1,3-dioxane, 1,4-dioxane, ethylene glycol dimethyl ether (DME), dimethyl sulfoxide, diethyl ether, methyl diglyme (methyl diglyme), acetonitrile, benzonitrile, tetrahydrofuran, cyclopentane sulfone, sultone, etc., or two or more of the above can be used in any combination and ratio.

[0170] In addition, as the electrolyte, a mixed organic solvent containing a fluorinated cyclic carbonate or a fluorinated chain carbonate can be used. Both fluorinated cyclic carbonate and fluorinated chain carbonate have electron-withdrawing substituents, so the solvation energy of lithium ions becomes low, and thus they are preferred.

[0171] As fluorinated cyclic carbonate, fluoroethylene carbonate (fluoroethylene carbonate, FEC, F1EC), difluoroethylene carbonate (DFEC, F2EC), trifluoroethylene carbonate (F3EC) or tetrafluoroethylene carbonate (F4EC) etc. can be used. In addition, as DFEC, isomers such as cis-4,5, trans-4,5 can be enumerated. Any fluorocyclic carbonate all has a substituent that presents electron-withdrawing property, and therefore is considered that the solvation energy of lithium ion is low. In addition, as fluorinated chain carbonate, for example, 3,3,3-methyl trifluoropropionate (MTFP) etc. can be used.

[0172] In addition, by using one or more ionic liquids (room temperature molten salts) with flame retardancy and low volatility as the solvent of the electrolyte, even if the internal temperature rises due to the internal short circuit or overcharge of the secondary battery, the rupture and / or ignition of the secondary battery can be prevented. The ionic liquid is composed of cations and anions, including organic cations and anions. As the organic cations for the electrolyte, aliphatic onium cations such as quaternary ammonium cations, tertiary sulfonium cations and quaternary phosphonium cations or aromatic cations such as imidazolium cations and pyridinium cations can be cited. In addition, as the anions for the electrolyte, monovalent amide anions, monovalent methylated anions, fluorosulfonic acid anions, perfluoroalkyl sulfonic acid anions, tetrafluoroborate anions, perfluoroalkyl borate anions, hexafluorophosphate anions or perfluoroalkyl phosphate anions can be cited.

[0173] {Electrolytes}

[0174] As the lithium salt (also referred to as electrolyte) dissolved in the above solvent, for example, LiPF6, LiClO4, LiAsF6, LiBF4, LiAlCl4, LiSCN, LiBr, LiI, Li2SO4, Li2B 10 Cl 10 、Li2B 12 Cl 12 , LiCF3SO3, LiC4F9SO3, LiC(CF3SO2)3, LiC(C2F5SO2)3, LiN(CF3SO2)2, LiN(C4F9SO2)(CF3SO2), LiN(C2F5SO2)2, or two or more of the above can be used in any combination and ratio. The lithium salt in the solvent is set to be above 0.5 mol / L and below 3.0 mol / L. When fluoride LiPF6, LiBF4, etc. are used, the safety of the lithium ion secondary battery is improved.

[0175] In addition, solid electrolytes containing inorganic materials such as sulfides or oxides, solid electrolytes containing polymer materials such as PEO (polyethylene oxide), etc. can be used instead of electrolytes. When a solid electrolyte is used, it is not necessary to set a separator and / or a spacer. In addition, since the entire battery can be solidified, there is no worry about leakage and safety is significantly improved.

[0176] {Isolated Body}

[0177] As the separator, for example, the following materials can be used: paper, nonwoven fabric, glass fiber, ceramic, or synthetic fiber containing nylon (polyamide), vinylon (polyvinyl alcohol-based fiber), polyester, acrylic resin, polyolefin, polyurethane, etc.

[0178] In addition, the separator may have a multilayer structure. For example, a ceramic material, a fluorine material, a polyamide material, or a mixture thereof may be coated on a thin film of an organic material such as polypropylene or polyethylene. As a ceramic material, for example, aluminum oxide particles, silicon oxide particles, etc. may be used. As a fluorine material, for example, PVDF, polytetrafluoroethylene, etc. may be used. As a polyamide material, for example, nylon, aromatic polyamide (meta-aramid, para-aramid), etc. may be used.

[0179] {Outer packaging}

[0180] As the outer packaging body included in the secondary battery, for example, at least one of a metal material such as aluminum and a resin material can be used. In addition, a film-shaped outer packaging body can also be used. As the film, for example, a three-layer structure film can be used: a metal film with excellent flexibility such as aluminum, stainless steel, copper, nickel, etc. is arranged on a film composed of materials such as polyethylene, polypropylene, polycarbonate, ionomer, polyamide, etc., and an insulating synthetic resin film such as a polyamide resin and a polyester resin can also be arranged on the metal film as the outer surface of the outer packaging body.

[0181] The above is the description of the components of the secondary battery.

[0182] [Thermal runaway of secondary batteries]

[0183] Regarding the principle of thermal runaway of secondary batteries, Fig. 8A The figure shows a modified diagram of a part of the graph shown in [Fig. 2-11] on page 69 of Non-Patent Document 6. When the temperature (specifically, the internal temperature) of the secondary battery described above increases during charging, the secondary battery goes through several states and enters thermal runaway. Fig. 8AThis is a graph of the temperature of a secondary battery relative to time. For example, when the temperature of the secondary battery reaches 100°C or thereabouts, (1) the SEI (Solid Electrolyte Interphase) of the negative electrode is destroyed and heat is generated. In addition, when the temperature of the secondary battery exceeds 100°C, (2) reduction and heat generation of the electrolyte caused by the negative electrode (when graphite is used, the negative electrode is C6Li) occur, and (3) oxidation and heat generation of the electrolyte caused by the positive electrode occur. Furthermore, when the temperature of the secondary battery reaches 180°C or thereabouts, (4) thermal decomposition of the electrolyte occurs, and (5) oxygen release from the positive electrode and thermal decomposition of the positive electrode occur (this thermal decomposition includes structural changes in the positive electrode active material). Then, when the temperature of the secondary battery exceeds 200°C, (6) decomposition of the negative electrode occurs, and finally (7) the positive electrode and the negative electrode are in direct contact. After the above-mentioned states, especially after the state of (5), the state of (6) or the state of (7), the secondary battery enters thermal runaway.

[0184] Furthermore, in order to avoid thermal runaway, it is considered that it is preferable to suppress the temperature rise of the secondary battery and to stabilize the components (negative electrode, positive electrode, electrolyte solution, etc.) constituting the secondary battery at high temperatures.

[0185] [Acupuncture test]

[0186] Next, refer to Fig. 9A and Fig. 9B The needle penetration test is described in detail below. The needle penetration test is a test in which the secondary battery 500 is fully charged (States Of Charge: equal to SOC 100%) and a steel needle 1003 having a specified diameter selected from 2 mm to 10 mm is used to penetrate the secondary battery at a specified speed. The needle penetration speed may be, for example, 1 mm / s to 20 mm / s. Fig. 9A 1 is a cross-sectional view showing a state where a secondary battery 500 is pierced with a steel needle 1003. The secondary battery 500 has a structure in which a positive electrode 503, a separator 508, a negative electrode 506, and an electrolyte 530 are contained in an outer packaging body 531. The positive electrode 503 includes a positive electrode collector 501 and a positive electrode active material layer 502 formed on both surfaces of the positive electrode collector 501, and the negative electrode 506 includes a negative electrode collector 504 and a negative electrode active material layer 505 formed on both surfaces of the negative electrode collector 504. In addition, Fig. 9B An enlarged view of the steel needle 1003 and the positive electrode current collector 501 is shown, and the positive electrode active material 561 and the conductive material 553 included in the positive electrode active material layer 502 are also shown.

[0187] like Fig. 9A and Fig. 9BAs shown, when the steel needle 1003 penetrates the positive electrode 503 and the negative electrode 506, an internal short circuit occurs. As a result, the potential of the steel needle 1003 becomes equal to the potential of the negative electrode, and the electron (e - ) flows to the positive electrode 503 through the steel needle 1003 as shown by the arrow, generating Joule heat in the internal short circuit portion and its vicinity. In addition, the carrier ions separated from the negative electrode 506 due to the internal short circuit are typically lithium ions (Li + ) is released into the electrolyte as shown by the white arrow. Here, when the anions in the electrolyte 530 are insufficient, when the lithium ions are separated from the negative electrode 506 into the electrolyte 530, the electrolyte 530 is not electrically neutral, so the electrolyte 530 begins to decompose in order to maintain electrical neutrality. This is one of the electrochemical reactions, and is called a reduction reaction of the electrolyte caused by the negative electrode.

[0188] The temperature of the secondary battery 500 may rise due to Joule heat. At this time, when lithium cobalt oxide is used as the positive electrode active material, the crystal structure of the lithium cobalt oxide changes and heat may be generated.

[0189] Since the electrons (e - ) In the charged lithium cobalt oxide, the tetravalent Co is reduced to trivalent or divalent, and the lithium cobalt oxide releases oxygen due to the reduction reaction. In addition, the electrolyte 530 is decomposed by the oxidation reaction of the oxygen. This is one of the electrochemical reactions, and is called the oxidation reaction of the electrolyte caused by the positive electrode. The flow rate of the current to the positive electrode active material 561, etc. is different depending on the insulation of the positive electrode active material, and it is also believed that the flow rate of the current affects the above-mentioned electrochemical reaction.

[0190] When an internal short circuit occurs in a secondary battery, the temperature is considered to be Figure 8B The graph shown changes. Figure 8B This is a graph that modifies a portion of the graph shown on page 70 [Figure 2-12] of non-patent document 6, and is a graph of the temperature (specifically, internal temperature) of a secondary battery relative to time. When an internal short circuit occurs at (P0), the temperature of the secondary battery rises over time. As shown in (P1), when the heat generated by Joule heat continues until the temperature of the secondary battery reaches approximately 100°C, it exceeds the reference temperature (Ts) of the secondary battery, which is the limit temperature that does not enter thermal runaway. At this time, reduction and heat generation of the electrolyte caused by the negative electrode (the negative electrode is C6Li when graphite is used) occur at (P2), oxidation and heat generation of the electrolyte caused by the positive electrode occur at (P3), and heat generation caused by thermal decomposition of the electrolyte occurs at (P4). Then, the secondary battery enters thermal runaway, and fire or smoke occurs.

[0191] In addition, it can be considered that: in order to avoid smoking, heating, etc. during the puncture test, it is important to suppress the temperature rise of the secondary battery and the components (negative electrode, positive electrode, electrolyte, etc.) constituting the secondary battery are stable at high temperatures. Specifically, the positive electrode active material preferably has a stable structure and does not release oxygen even if exposed to high temperatures. Alternatively, the positive electrode active material preferably has a structure in which the flow rate of the current to the active material is stable. The positive electrode active material 100 of one embodiment of the present invention can have both the above-mentioned stable structure and a structure that stabilizes the speed of the current, which will be described later.

[0192] [Positive electrode active material]

[0193] Next, a positive electrode active material 100 according to one embodiment of the present invention is described. As the positive electrode active material 100, a material that can be used as a carrier ion (typically, a lithium ion (Li + )) can be a compound containing a transition metal and oxygen that is embedded and released. As the transition metal, one or more selected from cobalt (Co), nickel (Ni), manganese (Mn) and iron (Fe) can be used. For example, as a compound using Co as a transition metal, lithium cobalt oxide can be used for the positive electrode active material 100. The positive electrode active material 100 exemplified below can be used for the positive electrode of the above-mentioned secondary battery.

[0194] The positive electrode active material 100 of one embodiment of the present invention preferably includes an insulating region or a high resistance region. It can be said that the positive electrode active material 100 having this region has a structure in which current does not flow rapidly. Note that this region is sometimes referred to as the first region to distinguish it from other regions. The above region preferably exists with a smaller width of more than 1nm and less than 20nm, preferably more than 2nm and less than 10nm, more preferably more than 2nm and less than 5nm when viewed from a cross section, and the above numerical value can be referred to as the thickness or width of the first region when viewed from a cross section. In this specification, etc., the region with a smaller width is sometimes referred to as a "shell". As a cross section, for example, a cross-sectional STEM image can be used.

[0195] The shell is preferably included in the surface layer of the positive electrode active material 100. In such a positive electrode active material 100 including a shell, even if a needle penetration test is performed, the current flowing into the positive electrode active material can be reduced, and fire or smoke can be suppressed, so it is preferred. In order to reduce the current flowing into the positive electrode active material, the shell is preferably located on the outside or surface side of the surface layer of the positive electrode active material 100.

[0196] The shell preferably contains an additional element added to the positive electrode active material 100. As the additional element, magnesium, fluorine, nickel, and aluminum can be cited. In addition, titanium, zirconium, vanadium, iron, manganese, chromium, niobium, arsenic, zinc, silicon, sulfur, phosphorus, boron, bromine, and beryllium can also be cited. Magnesium is one of the elements suitable for the shell, and fluorine is considered to be one of the elements suitable when magnesium is added to the positive electrode active material 100. In addition, the additional element may also be contained in the surface layer. Specifically, the crystal structure of the positive electrode active material 100 can be stabilized.

[0197] The structure of the shell is described using magnesium. In the surface layer of the positive electrode active material 100, magnesium is preferably present in a narrow region of 1 nm or more and 20 nm or less, more preferably in a narrow region of 2 nm or more and 10 nm or less, and further preferably in a narrow region of 2 nm or more and 5 nm or less, and the narrow region is called a shell. The shell preferably further contains cobalt, so that lithium ions (Li + ) is embedded and separated while slowing down the flow rate of the current caused by the internal short circuit. In other words, the surface layer of the positive electrode active material 100 includes a first region and a second region, preferably at least the first region contains magnesium, and the second region may not contain magnesium. Furthermore, the first region is preferably located on the outer side or surface side of the second region close to the positive electrode active material 100. In addition, it can be considered that the first region and the second region can carry out lithium ion (Li + )’s embedding and detachment.

[0198] The shell may be provided to fully cover the entire positive electrode active material 100 or to be thickened in a specific region of the positive electrode active material 100. For example, the shell may be provided to be thick along the surface other than the (001) surface of the layered rock salt type lithium cobalt oxide.

[0199] Note that, as long as there is no ignition in the needle penetration test, there is no restriction on the position of the shell on the positive electrode active material 100 as long as the position of the shell can make the lithium ions (Li + ) can slow down the current flow rate caused by internal short circuit while being embedded and detached, and magnesium can exist in the entire surface area.

[0200] It is preferred that lithium cobalt oxide containing one or more of the above-mentioned additive elements be used for the positive electrode active material 100. The additive element has the function of further stabilizing the positive electrode active material 100, so that the release of oxygen from the lithium cobalt oxide can be suppressed, thereby improving the thermal stability. Specifically, when lithium cobalt oxide containing Mg is used as the positive electrode active material 100, the crystal structure becomes stable, the release of oxygen is suppressed and the thermal stability is improved. In addition, when lithium cobalt oxide containing Mg is used as the positive electrode active material 100, the insulation can be improved and it is not easy to enter thermal runaway. In addition to Mg, F can also be included as an additive element, and the release of oxygen from surfaces other than the (00l) surface is suppressed, which can improve the thermal stability, thereby obtaining a structure that is not easy to enter thermal runaway.

[0201] Study the concentration of the added element. For example, the Mg as an added element is 0.5 atomic % (recorded as at%) or more and 30 at% or less in the surface portion of the lithium cobalt oxide, preferably 1.5 at% or more and 10 at% or less. The above Mg concentration can be identified by line analysis of EDX, etc. When Mg is present in a high concentration in the entire surface portion, the insulation is high, so it is difficult to obtain preferred battery characteristics in charge and discharge cycle tests, etc. On the other hand, when Mg is present in the surface portion in an appropriate concentration, especially in an appropriate area such as a shell, the lithium cobalt oxide can be stabilized, and heat and smoke can be suppressed in the above-mentioned puncture test, etc., so it is preferred. In addition, when Mg is present in the surface portion in an appropriate concentration, it is expected to increase the hardness of the lithium cobalt oxide.

[0202] The location of the added elements is studied. Mg and the like are preferably present in the surface portion at a high concentration. In addition, if Mg is present in the interior at a high concentration compared to the surface portion, there is a concern that the discharge capacity may decrease. Therefore, for example, Mg is preferably at least in the surface portion or the shell. That is, Mg is preferably located on the surface side compared to other added elements.

[0203] Fig. 10A FIG. 1 is a cross-sectional view of a positive electrode active material 100 according to one embodiment of the present invention. Fig. 10A As shown, the positive electrode active material 100 of one embodiment of the present invention preferably includes a shell 100s. The shell 100s preferably exists in a narrow width. Furthermore, the width of the shell 100s is preferably wider than the (001) surface on the surface other than the (001) surface where lithium insertion and extraction can be performed. In other words, by providing the shell 100s on the surface other than the (001) surface, oxygen can sometimes be suppressed from being extracted from the surface other than the (001) surface.

[0204] In addition, in this specification, etc., the (001) plane and the (003) plane are sometimes collectively referred to as the (001) plane. Note that in this specification, etc., the (001) plane is sometimes referred to as the C plane, the basal plane, etc. In addition, lithium has a two-dimensional diffusion path in lithium cobalt oxide. In other words, it can be said that the diffusion path of lithium exists along the basal plane. In this specification, etc., sometimes the surface where the diffusion path of lithium is exposed, that is, the surface where lithium is embedded and detached, specifically, the surface other than the (001) plane is referred to as the edge surface.

[0205] In addition, in the positive electrode active material 100 of one embodiment of the present invention, when Ni is also included as an added element, it is preferred that the region containing Mg overlaps, links or connects with the region containing Ni on the surface where lithium can be embedded and detached, that is, the surface other than (001). In other words, Ni is preferably also present in the shell. By adopting this structure, oxygen can be suppressed from detaching from the positive electrode active material or the structural change of the positive electrode active material can be suppressed.

[0206] FIG. 10B to FIG. 10D Show enlarged Fig. 10A 1 is a conceptual diagram of a quadrangular region B in FIG. Here, an example of lithium cobalt oxide containing Mg is shown as the positive electrode active material 100. Fig. 10B As shown, Mg, one of the added elements, is preferably bonded to oxygen in the shell. Furthermore, the shell preferably contains Co, and Co is preferably bonded to oxygen. It is believed that: Fig. 10B The shell shown can make lithium ions (Li + ) can suppress the rapid current inflow caused by internal short circuit while inserting and removing.

[0207] Next, an example of lithium cobalt oxide containing Mg and F is shown as the positive electrode active material 100. Fig. 10C As shown, F, one of the added elements, may not be present in the shell, but is preferably adsorbed on the surface of the positive electrode active material 100. It is known that fluorine has a high electronegativity, and there are many types of elements that are easy to form stable compounds with it. Inside the battery, the positive electrode active material 100 is immersed in the electrolyte. When fluorine is adsorbed on the surface of the positive electrode active material, it can react with the electrolyte near fluorine, and even if an internal short circuit occurs, the thermal decomposition of the electrolyte can be suppressed.

[0208] In addition, if Fig. 10D As shown, in lithium cobalt oxide containing Mg and F as the positive electrode active material 100, the fluorine compound 100f can also be adsorbed on the surface of the positive electrode active material 100. It is known that fluorine has a high electronegativity, and there are many types of elements that are easy to form stable compounds with it. The positive electrode active material 100 is immersed in the electrolyte. When the fluorine compound 100f is adsorbed on the surface of the positive electrode active material, it can react with the electrolyte near the fluorine compound 100f, and even if an internal short circuit occurs, the thermal decomposition of the electrolyte can be suppressed.

[0209] The above-mentioned adsorption includes chemical adsorption or physical adsorption. Chemical adsorption refers to the formation of chemical bonds due to a chemical reaction between at least one of the added elements and the surface of the positive electrode active material 100, and physical adsorption refers to adsorption using intermolecular forces (van der Waals forces) acting between at least one of the added elements and the surface of the positive electrode active material 100.

[0210] In addition, although not shown, the positive electrode active material 100 may also contain solid-dissolved fluorine, for example, fluorine may also replace a portion of the oxygen in the lithium cobalt oxide. The solid-dissolved fluorine only needs to be present in the surface layer of the lithium cobalt oxide, and may also be present in the shell. When sufficient fluorine is present in the positive electrode active material 100, the fluorine adsorbed on the surface and the fluorine replaced by a portion of the oxygen exist at the same time.

[0211] Fig.10E and Fig.10F This is an example of a positive electrode active material in which the boundary between the surface portion 100a and the bulk 100b is shown by a dotted line. In this way, the surface portion and the interior are distinguished, and the surface portion includes the surface. In this specification, etc., the surface portion of the positive electrode active material 100 refers to an area within 20nm or an area within 50nm from the surface to the inside in a direction perpendicular or approximately perpendicular to the surface. The surface portion is synonymous with the vicinity of the surface and the area near the surface. In addition, vertical or approximately vertical specifically refers to a range of more than 80° and less than 100° from the surface. In addition, an area deeper than the surface portion of the positive electrode active material is referred to as the interior. The interior is synonymous with the bulk or the core.

[0212] Fig.10F This is an example of a grain boundary 101 also shown by a dotted line. Crystals having a layered crystal structure represented by a layered rock salt type have the characteristic of being easily split along a plane parallel to the layer (here, the basal plane). Therefore, the grain boundary 101 is easily formed in a manner parallel to the basal plane. In addition, Fig.10F A crack is formed in the positive electrode active material 100, and the embedded portion 102 formed to fill the crack is shown. In the portion where the crack is formed in the positive electrode active material 100, the cleavage plane (that is, the plane parallel to the basal plane) is easily exposed.

[0213] The positive electrode active material 100 may contain magnesium in the entire surface layer, for example, the surface layer of lithium cobalt oxide may contain more magnesium than the inner portion. Lithium cobalt oxide containing magnesium has a characteristic that its crystal structure is not easily collapsed during high voltage charging.

[0214] The positive electrode active material 100 may also contain nickel. Nickel is sometimes present inside the lithium cobalt oxide. When fluorine and magnesium are present inside the lithium cobalt oxide, the discharge capacity of the positive electrode active material sometimes decreases, but even if nickel is present inside the lithium cobalt oxide, the discharge capacity is not likely to decrease. Therefore, the lithium cobalt oxide containing nickel inside can play the effect that the crystal structure is not easy to collapse when charged at a high voltage and does not reduce the discharge capacity.

[0215] By suppressing the collapse of the crystal structure, oxygen is not easily released from the positive electrode active material, specifically, it is not easily released from lithium cobalt oxide. Therefore, when lithium cobalt oxide containing additive elements such as fluorine is used for the positive electrode of a lithium ion secondary battery, heat generation can be suppressed even if an internal short circuit occurs, thereby achieving an effect of not easily entering thermal runaway.

[0216] Lithium cobalt oxide is composed of a lithium layer (sometimes referred to as a lithium site) and an octahedron of oxygen atoms. The octahedron of oxygen atoms can be said to be an octahedral structure in which cobalt is coordinated to six oxygen atoms, and is sometimes referred to as a CoO2 layer. The lithium layer of lithium cobalt oxide forms a plane on which lithium ions can move according to charge and discharge. The (001) in the accompanying figure represents the (001) plane of lithium cobalt oxide. LiCoO2 belongs to the space group R-3m.

[0217] Examples of fluorides used in lithium ion secondary batteries include LiPF6, LiBF4, etc. as lithium salts and polyvinylidene fluoride (PVDF), etc. as binders, which will be described later. Fluorine from these fluorides can also be adsorbed on the surface of the positive electrode active material 100.

[0218] [Surface of positive electrode active material]

[0219] The surface of the positive electrode active material 100 refers to the surface of the composite oxide including the above-mentioned surface layer 100a and the bulk 100b. Such a surface can be confirmed when viewed from a cross section. Therefore, the surface of the positive electrode active material 100 does not include: substances attached with metal oxides that do not contain lithium sites that contribute to charging and discharging, such as aluminum oxide (Al2O3); carbonates and hydroxyl groups chemically adsorbed after the positive electrode active material is manufactured. In addition, the attached metal oxide refers to, for example, a metal oxide whose crystal orientation is different from that of the bulk 100b.

[0220] The positive electrode active material 100 is a compound containing transition metals and oxygen in which lithium can be embedded and detached, so the interface between the region where there is a transition metal M (e.g., Co, Ni, Mn, Fe, etc.) and oxygen that is oxidized and reduced as lithium is embedded and detached and the region where there is no transition metal M and oxygen is called the surface of the positive electrode active material. When analyzing the positive electrode active material, the surface is sometimes covered with a protective film, but the protective film is not included in the positive electrode active material. As a protective film, a single layer or multilayer film of carbon, metal, oxide, resin, etc. is sometimes used.

[0221] Therefore, the surface of the positive electrode active material in STEM-EDX analysis or the like means that the value of the detected amount of the transition metal M is equal to the average value M of the detected amount inside. AVE and the background average M BG The point where the total of 50% of the oxygen detected is equal to the average value of the internal detection amount OAVE and the background average O BG In addition, it is considered that the fact that the points where the total of the transition metal M and oxygen is different from the background is due to the influence of metal oxides and carbonates containing oxygen attached to the surface, so the average value M of the detected amount inside the transition metal M can be used. AVE and the background average M BG When a positive electrode active material containing a plurality of transition metals M is used, the M of the element with the largest count in the bulk 100b can be used. AVE and M BG Find the surface.

[0222] The average value M of the background of the above transition metal M BG For example, the average value M of the detected amount of the transition metal M can be obtained by averaging the range of 2 nm or more, preferably 3 nm or more outside the portion, avoiding the portion where the detected amount of the transition metal M begins to increase. AVE The average value of the background value of oxygen can be obtained by averaging a range of 2 nm or more, preferably 3 nm or more, in a region where the counts of transition metal M and oxygen are saturated and stable, such as a region where the detection amount of transition metal M begins to increase to a depth of 30 nm or more, preferably to a depth of more than 50 nm. BG and the average value of the internal detection amount of oxygen O AVE It can also be found in the same way.

[0223] In addition, the surface of the positive electrode active material 100 in the cross-sectional STEM (scanning transmission electron microscope) image, etc. refers to: the boundary between the region where the image of the crystal structure derived from the positive electrode active material is observed and the region where the image is not observed, and refers to the outermost side of the region where the atomic column of the nucleus of the metal element having an atomic number greater than lithium in the metal element constituting the positive electrode active material is confirmed. Alternatively, the surface of the positive electrode active material 100 refers to: the intersection of the tangent drawn from the surface to the distribution of the brightness of the bulk in the STEM image and the axis in the depth direction. The surface in the STEM image, etc. can also be judged by referring to an analysis with a higher spatial resolution.

[0224] In addition, the spatial resolution of STEM-EDX is about 1nm. Therefore, the maximum value of the additive element distribution may deviate by about 1nm. For example, if the maximum value of the additive element distribution is outside the surface calculated above, it can be regarded as an error as long as the difference between the maximum value and the surface is less than 1nm.

[0225] In addition, the peak in STEM-EDX line analysis refers to the maximum value of the detection intensity in the distribution of each element or the characteristic X-ray of each element. As noise in STEM-EDX line analysis, the measured value of the half width below the spatial resolution (R), for example, below R / 2, is considered.

[0226] By scanning the same part multiple times under the same conditions, the influence of noise can be reduced. For example, the cumulative value of six scans can be used as the distribution of each element. The number of scans is not limited to six, and more than six scans can be performed and the average is used as the distribution of each element.

[0227] STEM-EDX line analysis can be performed, for example, by the following steps: First, a protective film is deposited on the surface of the positive electrode active material by evaporation, for example, by using an ion sputtering device (MC1000 manufactured by Hitachi High-Technologies Corporation).

[0228] Next, the positive electrode active material is thinned to produce a STEM cross-sectional sample. For example, thinning can be performed by a FIB-SEM device (XVision200TBS manufactured by Hitachi High-Technologies Corporation). At this time, MPS (microprobe system) is used for picking up, and the final processing conditions can be, for example, an accelerating voltage of 10 kV.

[0229] STEM-EDX line analysis uses, for example, a STEM device (HD-2700 manufactured by Hitachi High-Technologies Corporation), and as an EDX detector, an Octane TUltra W manufactured by EDAX Corporation (two are provided). When performing EDX line analysis, the emission current of the STEM device is set to be greater than 6μA and less than 10μA, and the shallow depth and less concave and convex part of the thinned sample is measured. The magnification is, for example, about 150,000 times. The conditions for EDX line analysis are as follows: there is drift correction; the line width is 42nm; the pitch is 0.2nm; the number of frames is six or more.

[0230] In addition, the grain boundary 101 refers to, for example: a portion where the particles of the positive electrode active material 100 are bonded together; a portion where the crystal orientation changes inside the positive electrode active material 100, that is, a portion where the bright lines and dark lines in the STEM image are repeatedly discontinuous, a portion containing multiple crystal defects, a portion with a disordered crystal structure, etc. In addition, a crystal defect refers to a defect observable through a cross-sectional TEM (transmission electron microscope) image or a cross-sectional STEM image, that is, a structure where other atoms enter the lattice, a void, etc. The grain boundary 101 can be said to be a type of surface defect. In addition, the vicinity of the grain boundary 101 refers to an area within 10 nm from the grain boundary 101.

[0231] [Contains elements]

[0232] The positive electrode active material 100 includes lithium, cobalt, oxygen, and an additive element. Alternatively, the positive electrode active material 100 may include lithium cobalt oxide (LiCoO2) to which the additive element is added. Note that the positive electrode active material 100 of one embodiment of the present invention may have a crystal structure described later. Therefore, the composition of lithium cobalt oxide is not strictly limited to Li:Co:O=1:1:2.

[0233] In order to keep the charge neutral during the insertion and removal of lithium ions, the positive electrode active material of the lithium ion secondary battery preferably contains a transition metal that can be oxidized and reduced. Preferably, the positive electrode active material 100 of one embodiment of the present invention mainly uses cobalt as a transition metal that performs redox reactions. In addition to cobalt, at least one or two selected from nickel and manganese can also be used.

[0234] In the transition metal contained in the positive electrode active material 100, cobalt preferably accounts for 75 atomic% or more, preferably 90 atomic% or more, and more preferably 95 atomic% or more. In this case, there are many advantages such as: it can be easily synthesized; it is easy to handle; it has good cycle characteristics; etc. In addition, compared with composite oxides such as lithium nickel oxide (LiNiO2) in which nickel accounts for more than half of the transition metal, when cobalt accounts for 75 atomic% or more, preferably 90 atomic% or more, and more preferably 95 atomic% or more in the transition metal of the positive electrode active material 100, Li x The smaller the x in CoO2, the better the stability. This is because cobalt is less affected by the distortion caused by the Jan-Taylor effect than nickel. The strength of the Jan-Taylor effect in transition metal compounds varies according to the number of electrons in the d orbital of the transition metal. Layered rock salt-type composite oxides such as lithium nickelate, in which octahedrally coordinated low-spin nickel (III) accounts for more than half of the transition metal, are greatly affected by the Jan-Taylor effect, and the layers composed of nickel and oxygen octahedra are prone to distortion. Therefore, concerns about the collapse of the crystal structure during the charge and discharge cycle increase. In addition, nickel ions are larger than cobalt ions and are close to the size of lithium ions. Therefore, in layered rock salt-type composite oxides such as lithium nickelate, in which nickel accounts for more than half of the transition metal, there is a problem of easy mixing of nickel and lithium cations.

[0235] Although the additive elements included in the positive electrode active material 100 have been described, it is preferred to use one or more selected from magnesium, fluorine, nickel, aluminum, titanium, zirconium, vanadium, iron, manganese, chromium, niobium, arsenic, zinc, silicon, sulfur, phosphorus, boron, bromine and beryllium. In addition, the total amount of transition metals in the additive elements is preferably less than 25 atomic%, more preferably less than 10 atomic%, and further preferably less than 5 atomic%.

[0236] That is, the positive electrode active material 100 may include lithium cobalt oxide added with magnesium and fluorine, lithium cobalt oxide added with magnesium, fluorine and titanium, lithium cobalt oxide added with magnesium, fluorine and aluminum, lithium cobalt oxide added with magnesium, fluorine and nickel, lithium cobalt oxide added with magnesium, fluorine, nickel and aluminum, etc.

[0237] The added element may also be dissolved in the positive electrode active material 100, for example, preferably dissolved in the surface of the positive electrode active material 100. Therefore, for example, when performing line analysis of STEM-EDX, the depth at which the detected amount of the added element increases is preferably deeper than the depth at which the detected amount of the transition metal M increases, that is, on the inner side of the positive electrode active material 100.

[0238] In this specification, etc., the depth at which the detection amount of a certain element increases in line analysis by STEM-EDX means a depth at which a measurement value can be continuously obtained, and this measurement value can be determined not to be noise from the viewpoint of intensity and spatial resolution.

[0239] As described below, these additional elements can further stabilize the crystal structure of the positive electrode active material 100, thereby suppressing ignition caused by internal short circuits, etc. Note that in this specification, etc., an additional element is synonymous with a mixture or a part of a raw material.

[0240] As the additive element, it is not necessary to contain magnesium, fluorine, nickel, aluminum, titanium, zirconium, vanadium, iron, manganese, chromium, niobium, arsenic, zinc, silicon, sulfur, phosphorus, boron, bromine or beryllium.

[0241] For example, by manufacturing a positive electrode active material 100 that does not substantially contain manganese, the above advantages such as easier synthesis, easier handling, and good cycle characteristics can be improved. The weight of manganese contained in the positive electrode active material 100 is preferably 600 ppm or less, and more preferably 100 ppm or less.

[0242] [Crystal Structure]

[0243] {Li x When x is 1 in CoO2}

[0244] Preferably, the positive electrode active material 100 of one embodiment of the present invention is in a discharged state, that is, in a Li x When x=1 in CoO2, it has a layered rock salt type crystal structure belonging to the space group R-3m. The layered rock salt type composite oxide has a high discharge capacity and a two-dimensional lithium ion diffusion path, which is suitable for the insertion / extraction reaction of lithium ions and is excellent as a positive electrode active material for secondary batteries. Therefore, the bulk 100b, which occupies most of the volume of the positive electrode active material 100, preferably has a layered rock salt type crystal structure. Fig.11 In the figure, R-3m O3 represents a layered rock salt type crystal structure.

[0245] On the other hand, the surface portion 100a of the positive electrode active material 100 of one embodiment of the present invention preferably strengthens the layered structure composed of octahedrons of transition metal M and oxygen of the bulk 100b to prevent the layered structure from collapsing even if a large amount of lithium is detached from the positive electrode active material 100 due to charging. Alternatively, the surface portion 100a is preferably used as a barrier film for the positive electrode active material 100. Alternatively, the surface portion 100a of the peripheral portion of the positive electrode active material 100 preferably strengthens the positive electrode active material 100. Here, strengthening refers to at least one of suppressing structural changes in the surface portion 100a and the bulk 100b of the positive electrode active material 100, led by oxygen detachment, and suppressing oxidative decomposition of the electrolyte on the surface of the positive electrode active material 100.

[0246] Therefore, the surface portion 100a preferably has a composition and crystal structure different from those of the bulk 100b. In addition, the composition and crystal structure of the surface portion 100a at room temperature (25°C) are preferably more stable than those of the bulk 100b. For example, at least a portion of the surface portion 100a of the positive electrode active material 100 of one embodiment of the present invention preferably has a rock salt type crystal structure. Alternatively, the surface portion 100a preferably has both a layered rock salt type crystal structure and a rock salt type crystal structure. Alternatively, the surface portion 100a preferably has the characteristics of both a layered rock salt type and a rock salt type crystal structure.

[0247] The surface part 100a is the area where lithium ions are first separated during charging, and is also the area where the lithium concentration is easily lower than that of the bulk 100b. In addition, it can also be said that some of the bonds among the atoms on the surface of the positive electrode active material 100 contained in the surface part 100a are cut. Therefore, the surface part 100a is likely to become an unstable area where crystal structure degradation is likely to begin. On the other hand, as long as the surface part 100a can be sufficiently stabilized, the lithium ion concentration in the lithium ion battery can be reduced. x When x in CoO2 is small, for example, when x is less than 0.24, the layered structure of the bulk 100b composed of transition metal M and oxygen octahedra is not easily collapsed. Furthermore, the deviation of the layer composed of transition metal M and oxygen octahedra in the bulk 100b can be suppressed.

[0248] The density of defects such as dislocations in the block 100b of the positive electrode active material 100 is preferably low. In addition, the grain size of the positive electrode active material 100 measured by XRD is preferably large. In other words, the crystallinity of the block 100b is preferably high. In addition, the surface of the positive electrode active material 100 is preferably smooth. These features are important elements that support the reliability of the positive electrode active material 100 when used in a secondary battery. When the reliability of the positive electrode active material is high, the upper limit of the charging voltage of the secondary battery can be increased, and a secondary battery with a large charge and discharge capacity can be realized.

[0249] Dislocations in the bulk 100b can be observed, for example, using TEM. When the density of defects such as dislocations is sufficiently low, sometimes only a specific 1 μm of the sample under observation may be observed. 2 No defects such as dislocations are observed. Dislocations are a type of crystal defect, different from point defects.

[0250] The crystallite size measured by XRD is preferably 300 nm or more. As will be described later, the larger the crystallite size, the greater the x The smaller the x in CoO2 is, the easier it is to maintain the O3' type structure, and the reduction in length along the c-axis is more likely to be suppressed.

[0251] It is considered that the fewer defects such as dislocations observed by TEM, the larger the grain size measured by XRD.

[0252] The XRD diffraction pattern used when calculating the grain size is preferably obtained in a state where there is only a positive electrode active material, but it can also be obtained in a state where the positive electrode also includes a current collector, a binder, and a conductive material in addition to the positive electrode active material. Note that in the positive electrode state, the particles of the positive electrode active material may be affected by the pressurization in the manufacturing process and oriented in a manner in which the crystal planes of the particles of the positive electrode active material are consistent in one direction. When the degree of orientation is large, it may not be possible to accurately calculate the grain size, so it is more preferable to obtain the XRD diffraction pattern by the following method: remove the positive electrode active material layer from the positive electrode, use a solvent to remove the binder in the positive electrode active material layer to a certain extent, and fill it into a sample holder, etc. In addition, there is also the following method: apply grease on a silicon non-reflective plate to attach a powder sample of the positive electrode active material to the silicon non-reflective plate.

[0253] In the calculation of the grain size, for example, the diffraction pattern obtained under the conditions of using Bruker D8ADVANCE, using CuKα as the X-ray source, 2θ being 15° or more and 90° or less, increment being 0.005, and detector being LYNXEYE XE-T, and ICSD coll.code.172909 as the literature value of lithium cobalt oxide can be used. DIFFRAC.TOPAS ver.6 can be used as the crystal structure analysis software for analysis, and for example, the following settings can be used.

[0254] Emission Profile: CuKa5.lam

[0255] Background: Chebychev polynomial, 5 times

[0256] Instrument

[0257] Primary radius: 280mm

[0258] Secondary radius: 280mm

[0259] Linear PSD

[0260] 2Th angular range: 2.9

[0261] FDS angle: 0.3

[0262] Full Axial Convolution

[0263] Filament length: 12mm

[0264] Sample length: 15mm

[0265] Receiving Slit length: 12mm

[0266] Primary Sollers: 2.5

[0267] Secondary Sollers: 2.5

[0268] Corrections

[0269] Specimen displacement:Refine

[0270] LP Factor: 0

[0271] It is preferable to use the LVol-IB value of the crystallite size calculated by the above method as the crystallite size. Note that when the calculated Preferred Orientation is less than 0.8, too many particles in the sample have the same orientation, so the sample may not be suitable for calculation of the grain size.

[0272] {About the distribution of added elements}

[0273] The distribution of the added elements of the positive electrode active material 100 is explained by taking the discharge state as an example. In order to make the surface portion 100a have a stable composition and crystal structure, the surface portion 100a preferably contains an added element, and more preferably contains a plurality of added elements. In addition, the concentration of one or more selected from the added elements in the surface portion 100a is preferably higher than that in the bulk 100b. In addition, one or more selected from the added elements contained in the positive electrode active material 100 preferably have a concentration gradient. In addition, it is more preferred that the distribution of the added elements in the positive electrode active material 100 is different. For example, it is more preferred that the depth of the added element concentration peak from the surface is different. Here, the concentration peak refers to the maximum value of the detected amount in the surface portion 100a or the range below 50nm from the surface.

[0274] For example, some of the additive elements such as magnesium, fluorine, nickel, titanium, silicon, phosphorus, boron, calcium, etc. preferably have a concentration gradient that increases from the bulk 100b toward the surface. The element having such a concentration gradient is referred to as additive element X.

[0275] Preferably, other additive elements such as aluminum and manganese have a concentration gradient and a concentration peak in a deeper region. The concentration peak may exist in the surface portion 100a or in a region deeper than the surface portion 100a. For example, it is preferred that a peak exists in a region that is vertical or substantially vertical to the surface and is 5 nm or more and 30 nm or less. An element having such a concentration gradient is referred to as an additive element Y.

[0276] Magnesium, which is one of the added elements X, is divalent. In the layered rock salt type crystal structure, magnesium ions are more stable in the lithium position than in the transition metal M position in the layered rock salt type crystal structure, and thus easily enter the lithium position. When magnesium is present at an appropriate concentration at the lithium position of the surface portion 100a, the layered rock salt type crystal structure can be easily maintained. This is because magnesium present at the lithium position is used as a support between CoO2 layers. In addition, when magnesium is present, for example, in Li x When x in CoO2 is 0.24 or less, the oxygen around magnesium can be suppressed from being released. In addition, it can be expected that the density of the positive electrode active material 100 is improved when magnesium is present. In addition, when the magnesium concentration of the surface portion 100a is high, it can be expected that the corrosion resistance to hydrofluoric acid generated by the decomposition of the electrolyte can be improved.

[0277] If magnesium has an appropriate concentration, it has no negative effect on the insertion and removal of lithium accompanying charge and discharge, so the above advantages can be obtained. However, excess magnesium may have a negative effect on the insertion and removal of lithium. In addition, the effect of contributing to the stabilization of the crystal structure is sometimes reduced. This is because magnesium not only enters the lithium position but also enters the transition metal M position. In addition, there is also the following concern: unnecessary magnesium compounds (such as oxides, fluorides, etc.) that are not substituted at the lithium position or the transition metal M position are segregated on the surface of the positive electrode active material and become the resistance component of the secondary battery. In addition, the increase in the magnesium concentration of the positive electrode active material sometimes reduces the discharge capacity of the positive electrode active material. This is because the excess magnesium enters the lithium position and the amount of lithium contributing to charge and discharge is reduced.

[0278] Therefore, it is preferred that an appropriate amount of magnesium is included in the positive electrode active material 100 as a whole. For example, in the positive electrode active material 100 of one embodiment of the present invention, the magnesium ratio (Mg / Co) relative to the sum of the transition metals M is preferably 0.25% or more and 5% or less, more preferably 0.5% or more and 2% or less, and further preferably about 1%. Here, the amount of magnesium in the positive electrode active material 100 as a whole can be, for example, a value obtained by analyzing all elements of the positive electrode active material 100 using GD-MS, ICP-MS, etc., or a value based on the coordination value of the raw materials in the manufacturing process of the positive electrode active material 100.

[0279] In addition, nickel, which is one of the added elements X, may be present at the transition metal M site or the lithium site. When nickel is present at the transition metal M site, the redox potential is lowered compared to cobalt, and the discharge capacity is increased, which is preferred.

[0280] In addition, when nickel is present at the lithium position, the deviation of the layered structure composed of the transition metal M and the octahedron of oxygen is suppressed. In addition, the volume change caused by charging and discharging is also suppressed. In addition, the elastic modulus is improved, that is, it becomes hard. This is because the nickel present at the lithium position is also used as a support between the CoO2 layers. Therefore, it can be expected that the crystal structure is more stable, especially when charged at a high temperature of 45°C or above, so it is preferred.

[0281] On the other hand, when the amount of nickel is too large, the influence of distortion due to the Jan-Teller effect may increase. In addition, when the amount of nickel is too large, it may have a negative impact on the insertion and extraction of lithium.

[0282] Therefore, it is preferred that an appropriate amount of nickel is included in the positive electrode active material 100 as a whole. For example, the number of nickel atoms contained in the positive electrode active material 100 is preferably greater than 0% of the number of cobalt atoms and less than 7.5%, more preferably greater than 0.05% and less than 4%, further preferably greater than 0.1% and less than 2%, and further preferably greater than 0.2% and less than 1%. Alternatively, it is preferably greater than 0% and less than 4%. Alternatively, it is preferably greater than 0% and less than 2%. Alternatively, it is preferably greater than 0.05% and less than 7.5%. Alternatively, it is preferably greater than 0.05% and less than 2%. Alternatively, it is preferably greater than 0.1% and less than 7.5%. Alternatively, it is preferably greater than 0.1% and less than 4%. The amount of nickel shown here can be, for example, a value obtained by elemental analysis of the positive electrode active material as a whole using GD-MS, ICP-MS, etc., or a value obtained by mixing raw materials in the manufacturing process of the positive electrode active material.

[0283] In addition, aluminum, one of the added elements Y, may exist in the position of the transition metal M in the layered rock salt type crystal structure. Aluminum is a typical trivalent element and its valence remains unchanged, so the lithium around aluminum is not easy to migrate during charging and discharging. Therefore, aluminum and the lithium around it may be used as pillars to suppress changes in the crystal structure. In addition, aluminum has the effect of suppressing the dissolution of the surrounding transition metal M and improving the continuous charging tolerance. In addition, the Al-O bond is stronger than the Co-O bond, so the oxygen around aluminum can be suppressed from detaching. Through the above effects, thermal stability is improved. Therefore, when aluminum is included as an added element Y, the safety of the positive electrode active material 100 when used in a secondary battery can be improved. In addition, a positive electrode active material 100 that is not prone to crystal structure collapse even after repeated charging and discharging can be achieved.

[0284] On the other hand, when the amount of aluminum is too large, there is a possibility that the insertion and extraction of lithium may be adversely affected.

[0285] Therefore, it is preferred that an appropriate amount of aluminum is included in the positive electrode active material 100 as a whole. For example, the number of aluminum atoms in the positive electrode active material 100 as a whole is preferably greater than 0.05% and less than 4% of the number of cobalt atoms, more preferably greater than 0.1% and less than 2%, and further preferably greater than 0.3% and less than 1.5%. Alternatively, it is preferably greater than 0.05% and less than 2%. Alternatively, it is preferably greater than 0.1% and less than 4%. The amount in the positive electrode active material 100 as a whole shown here can be, for example, a value obtained by elemental analysis of the positive electrode active material 100 as a whole using GD-MS, ICP-MS, etc., or a value obtained based on the mixing of raw materials in the manufacturing process of the positive electrode active material 100.

[0286] In addition, fluorine, one of the added elements X, is a monovalent anion, and when part of the oxygen in the surface portion 100a is replaced by fluorine, the lithium detachment energy is reduced. This is because the valence change of the cobalt ion accompanying the lithium detachment is different depending on the presence or absence of fluorine, for example, from trivalent to tetravalent in the absence of fluorine, and from divalent to trivalent in the presence of fluorine, and the redox potential is different. Therefore, when part of the oxygen in the surface portion 100a of the positive electrode active material 100 is replaced by fluorine, it can be said that the detachment and insertion of lithium ions near fluorine occur smoothly. Therefore, the charge and discharge characteristics, current characteristics, etc. can be improved when the positive electrode active material 100 is used in a secondary battery. In addition, by having fluorine in the surface portion 100a of the surface including the portion in contact with the electrolyte, the corrosion resistance to hydrofluoric acid can be effectively improved. In addition, when the melting point of fluorides such as lithium fluoride is lower than the melting point of other added element sources, it can be used as a flux (also known as a solubility aid) to lower the melting point of other added element sources.

[0287] In addition, it is known that the oxide of titanium, which is one of the added elements X, has super hydrophilicity. Therefore, by manufacturing the positive electrode active material 100 containing titanium oxide in the surface layer 100a, it is sometimes possible to have good wettability to a solvent with high polarity. When manufacturing a secondary battery, the positive electrode active material 100 has good contact with the interface of the electrolyte with high polarity, and sometimes the increase of the internal resistance can be suppressed.

[0288] In addition, by including phosphorus, which is one of the additional elements X, in the surface layer portion 100a, it is possible to maintain the Li x When x in CoO 2 is small, short circuit can be suppressed, which is preferable. For example, it is preferable that it exists in the surface layer portion 100 a as a compound containing phosphorus and oxygen.

[0289] When the positive electrode active material 100 contains phosphorus, hydrogen fluoride generated by decomposition of the electrolyte reacts with phosphorus to reduce the concentration of hydrogen fluoride in the electrolyte, which is preferable.

[0290] In the case where the electrolyte contains LiPF6, hydrogen fluoride is sometimes produced by hydrolysis. In addition, hydrogen fluoride is sometimes produced by the reaction of polyvinylidene fluoride (PVDF) used as a constituent element of the positive electrode with an alkali. By reducing the concentration of hydrogen fluoride in the electrolyte, corrosion of the current collector and / or peeling of the coating can be suppressed. In addition, the reduction in adhesion caused by the gelation and / or insolubility of PVDF can sometimes be suppressed.

[0291] When the positive electrode active material 100 contains phosphorus in addition to magnesium, xCoO2 is preferred because its stability is extremely high when x is small. When the positive electrode active material 100 contains phosphorus, the number of phosphorus atoms is preferably 1% or more and 20% or less of the number of cobalt atoms, more preferably 2% or more and 10% or less, and further preferably 3% or more and 8% or less. Alternatively, it is preferably 1% or more and 10% or less. Alternatively, it is preferably 1% or more and 8% or less. Alternatively, it is preferably 2% or more and 20% or less. Alternatively, it is preferably 2% or more and 8% or less. Alternatively, it is preferably 3% or more and 20% or less. Alternatively, it is preferably 3% or more and 10% or less. In addition, the number of magnesium atoms is preferably 0.1% or more and 10% or less of the number of cobalt atoms, more preferably 0.5% or more and 5% or less, and further preferably 0.7% or more and 4% or less. Alternatively, it is preferably 0.1% or more and 5% or less. Alternatively, it is preferably 0.1% or more and 4% or less. Alternatively, it is preferably 0.5% or more and 10% or less. Alternatively, it is preferably 0.5% or more and 4% or less. Alternatively, it is preferably 0.7% or more and 10% or less. Alternatively, it is preferably 0.7% or more and 5% or less. The concentrations of phosphorus and magnesium shown here may be values ​​obtained by elemental analysis of the entire positive electrode active material 100 using GC-MS, ICP-MS, etc., or values ​​obtained based on raw material mixing during the manufacturing process of the positive electrode active material 100.

[0292] When the positive electrode active material 100 has cracks, if phosphorus, more specifically, a compound containing phosphorus and oxygen, exists inside the positive electrode active material on the surface of the cracks, such as in the embedded portion 102 , the expansion of the cracks may be suppressed.

[0293] In addition, when the surface layer 100a contains both magnesium and nickel, it is possible that divalent magnesium exists more stably near divalent nickel. x When x in CoO 2 is small, the dissolution of magnesium is also suppressed. Thus, magnesium and nickel contribute to the stabilization of the surface layer portion 100 a.

[0294] In addition, when adding elements X and Y with different distributions are used at the same time, the crystal structure of a wider area can be stabilized, so it is preferred. For example, when the positive electrode active material 100 contains magnesium and nickel, which are part of the added element X, and aluminum, which is one of the added elements Y, the crystal structure of a wider area can be stabilized compared to the case where only one of the added elements X and Y is included. In this way, when the positive electrode active material 100 contains both the added element X and the added element Y, the added element X such as magnesium can fully stabilize the surface, so the added element Y such as aluminum is not required on the surface. On the contrary, aluminum is preferably widely distributed in a deeper area, such as an area with a depth of more than 5nm and less than 50nm from the surface, so that the crystal structure of a wider area can be stabilized.

[0295] When a plurality of additive elements are included as described above, each additive element synergistically contributes to further stabilization of the surface layer portion 100a. In particular, when magnesium, nickel, and aluminum are included, the effect of achieving a stable composition and crystal structure is high, and therefore, it is preferred.

[0296] Note that when the surface portion 100a only has a compound of an added element and oxygen, lithium is not easily inserted and removed, so it is not preferred. For example, a surface portion 100a having only MgO, a structure in which MgO and NiO(II) are solid-dissolved, and / or a structure in which MgO and CoO(II) are solid-dissolved is not preferred. Therefore, the surface portion 100a needs to contain at least cobalt, also contain lithium in the discharge state, and have a path for the insertion and removal of lithium.

[0297] In order to fully ensure the path for the insertion and removal of lithium, the cobalt concentration of the surface portion 100a is preferably higher than the magnesium concentration. For example, the ratio Mg / Co of the number of atoms of magnesium Mg to the number of atoms of cobalt Co is preferably 0.62 or less. In addition, the cobalt concentration of the surface portion 100a is preferably higher than the nickel concentration. In addition, the cobalt concentration of the surface portion 100a is preferably higher than the aluminum concentration. In addition, the cobalt concentration of the surface portion 100a is preferably higher than the fluorine concentration.

[0298] If nickel is too much, the diffusion of lithium may be blocked, so the magnesium concentration of the surface layer 100a is preferably higher than the nickel concentration. For example, the number of nickel atoms is preferably 1 / 6 or less of the number of magnesium atoms.

[0299] In addition, the concentration of a part of the added elements, especially magnesium, nickel and aluminum, in the surface part 100a is preferably higher than that in the bulk 100b, but they are preferably also present irregularly and in small amounts in the bulk 100b. When magnesium and aluminum are present at appropriate concentrations at the lithium position of the bulk 100b, it has the same effect as described above, such as easily maintaining the layered rock salt type crystal structure. In addition, when nickel is present at an appropriate concentration in the bulk 100b, the deviation of the layered structure composed of the octahedron of the transition metal M and oxygen is suppressed, as described above. In addition, in the case of simultaneously containing magnesium and nickel, divalent magnesium may also be more stably present near divalent nickel, so a synergistic effect of suppressing the dissolution of magnesium can be expected.

[0300] In addition, it is preferable that the crystal structure changes continuously from the bulk 100b to the surface due to the concentration gradient of the added element. Alternatively, it is preferable that the crystal orientations of the surface layer portion 100a and the bulk 100b are substantially the same.

[0301] For example, it is preferred that the crystal structure changes continuously from the bulk 100b of the layered rock salt type to the surface and the surface layer 100a of the rock salt type or having both the characteristics of the rock salt type and the layered rock salt type. Alternatively, it is preferred that the orientation of the surface layer 100a of the rock salt type or having both the characteristics of the rock salt type and the layered rock salt type is roughly consistent with that of the bulk 100b of the layered rock salt type.

[0302] In addition, in this specification, etc., the layered rock salt type crystal structure belonging to the space group R-3m of the composite oxide containing transition metal M such as lithium and cobalt refers to the following crystal structure: a rock salt type ion arrangement with alternating arrangement of cations and anions, and the transition metal M and lithium are regularly arranged to form a two-dimensional plane, so that lithium can diffuse in two dimensions. In addition, defects such as vacancies of cations or anions may also be included. Strictly speaking, the layered rock salt type crystal structure is sometimes a structure formed by deformation of the lattice of rock salt type crystals.

[0303] In addition, the rock salt type crystal structure has a cubic crystal structure such as space group Fm-3m, in which cations and anions are arranged alternately. In addition, vacancies of cations or anions may also be included.

[0304] In addition, whether or not the crystal has the characteristics of both the layered rock salt type crystal structure and the rock salt type crystal structure can be determined by electron diffraction, TEM images, cross-sectional STEM images, and the like.

[0305] There is no difference in the position of cations in the rock salt type crystal structure, but in the layered rock salt type crystal structure, there are two types of cation positions, one is the position where lithium occupies most of the position and the other is the position where the transition metal M occupies. Both the rock salt type and the layered rock salt type have a stacked structure in which the two-dimensional planes of cations and the two-dimensional planes of anions are arranged alternately. In the bright spots of the electron diffraction image of the crystal plane forming the above-mentioned two-dimensional plane, when the central spot (transmitted spot) is taken as the origin 000, the bright spot closest to the central spot is, for example: the bright spot of the (111) plane of the ideal rock salt type crystal structure or the bright spot of the (003) plane of the ideal layered rock salt type crystal structure. For example, when comparing the electron diffraction images of rock salt type MgO and layered rock salt type LiCoO2, the bright spot of the (003) plane of LiCoO2 is observed at a distance about half the distance between the bright spots of the (111) plane of MgO. Therefore, for example, when the analysis area includes two phases of rock salt type MgO and layered rock salt type LiCoO2, there are plane orientations in which bright spots of stronger brightness and bright spots of weaker brightness are arranged alternately in the electron diffraction image. Bright spots common to the rock salt type and the layered rock salt type have high brightness, while bright spots occurring only in the layered rock salt type have low brightness.

[0306] In addition, in cross-sectional STEM images, when observing the layered rock salt type crystal structure from a direction perpendicular to the c-axis, layers with higher brightness and layers with lower brightness are observed alternately. The position of the cations of the rock salt type is the same, so the above characteristics are not observed. When a crystal structure having characteristics of both the rock salt type and the layered rock salt type is adopted, when observing from a specific crystal orientation, layers with higher brightness and layers with lower brightness are observed alternately in cross-sectional STEM images, and a metal having an atomic number greater than lithium exists in a part of the lower brightness layer, that is, the lithium layer.

[0307] The anions of the layered rock salt type crystal and the rock salt type crystal form a cubic closest packing structure (face-centered cubic lattice structure) respectively. It can be considered that the anions of the O3' type crystal described later also form a cubic closest packing structure. Therefore, when the layered rock salt type crystal contacts the rock salt type crystal, there are crystal planes with the same orientation of the cubic closest packing structure formed by the anions.

[0308] In addition, it can be explained as follows. The anions on the {111} plane of the cubic crystal structure have a triangular lattice. The layered rock salt type has a rhombus structure belonging to the space group R-3m, but in order to facilitate the understanding of the structure, it is usually expressed as a composite hexagonal lattice, and the (0001) plane of the layered rock salt type has a hexagonal lattice. The triangular lattice of the {111} plane of the cubic crystal has the same atomic arrangement as the hexagonal lattice of the (0001) plane of the layered rock salt type. The state in which the lattices of the two are integrated can be said to be a state in which the orientation of the cubic closest packing structure is consistent.

[0309] Note that the space group of the layered rock salt type crystal and the O3' type crystal is R-3m, which is different from the space group Fm-3m (the space group of the general rock salt type crystal) of the rock salt type crystal, so the Miller index of the crystal plane that satisfies the above conditions is different between the layered rock salt type crystal and the O3' type crystal and the rock salt type crystal. In this specification, sometimes the state of the orientation of the cubic closest packing structure formed by the anions in the layered rock salt type crystal, the O3' type and the rock salt type crystal is consistent, which means that the orientation of the crystal is roughly consistent, in a topological derivative (topotaxy) or in a face derivative (epitaxy).

[0310] Topological derivation refers to a state in which the orientation of crystals is roughly the same and has three-dimensional structural similarity or the same orientation crystallographically. In addition, epitaxy refers to the structural similarity of a two-dimensional interface.

[0311] By using TEM (Transmission Electron Microscope: Transmission Electron Microscope) images, STEM (Scanning Transmission Electron Microscope: Scanning Transmission Electron Microscope) images, HAADF-STEM (High-angle Annular Dark Field Scanning TEM: High-angle annular dark field) images, ABF-STEM (Annular Bright-Field Scanning Transmission Electron Microscope: Annular Bright Field Scanning Transmission Electron Microscope) images, eHCI-TEM (enhanced Hollow-Cone Illumination-TEM: Improved Hollow Cone Illumination Transmission Electron Microscope) images, electron diffraction patterns, TEM images, STEM images, and other FFT patterns, it can be determined that the orientation of the crystals in the two regions is roughly the same. In addition, X-ray diffraction (XRD: X-ray Diffraction), electron diffraction, neutron diffraction, etc. can be used as a basis for judgment.

[0312] Fig.13 An example of a TEM image showing that the orientations of the layered rock salt type crystals LRS and the rock salt type crystals RS are substantially consistent is shown. TEM images, STEM images, HAADF-STEM images, ABF-STEM images, etc. can be used to obtain images reflecting the crystal structure.

[0313] For example, the contrast derived from the crystal plane can be obtained from the high-resolution images of TEM. Due to the diffraction and interference of the electron beam, for example, when the electron beam is incident on the c-axis perpendicular to the layered rock salt type composite hexagonal lattice, the repetition of high contrast bands (bright band lines) and dark bands (dark band lines) derived from the (0003) plane can be obtained. Therefore, the repetition of bright lines and dark lines is observed in the TEM image, and between the bright lines (for example, Fig.13 When the angle between the LRS and LLRS in the image is greater than 0 degrees and less than 5 degrees or greater than 0 degrees and less than 2.5 degrees, it can be judged that the crystal planes are roughly consistent, that is, the orientations of the crystals are roughly consistent. Similarly, when the angle between the dark lines is less than 5 degrees or less than 2.5 degrees, it can also be judged that the orientations of the crystals are roughly consistent. Note that, in general, it is difficult to clearly distinguish between "completely consistent" and "roughly consistent". Therefore, in this specification, "consistent" includes both the case of complete consistency (for example, the case where the angle between the bright lines is 0 degrees) and the case of roughly consistent.

[0314] In addition, in the HAADF-STEM image, a contrast ratio proportional to the atomic number is obtained, and the larger the atomic number of the element, the brighter it is observed. For example, when using a layered rock salt type lithium cobalt oxide belonging to the space group R-3m, the atomic number of cobalt (atomic number 27) is the largest, so the electron beam is scattered more strongly at the position of the cobalt atom, so that the arrangement of the cobalt atoms is observed as an arrangement of bright lines or high-brightness points. Therefore, when observing lithium cobalt oxide with a layered rock salt type crystal structure in a direction perpendicular to the c-axis, the arrangement of cobalt atoms is observed as bright lines or arrangements of higher-brightness points in the direction perpendicular to the c-axis, and the arrangement of lithium atoms and oxygen atoms is observed as dark lines or areas with lower brightness. The same is true when fluorine (atomic number 9) and magnesium (atomic number 12) are included as additive elements for lithium cobalt oxide.

[0315] Therefore, in the HAADF-STEM image, the repetition of bright and dark lines is observed in two regions with different crystal structures. When the angle between the bright lines is less than 5 degrees or less than 2.5 degrees, it can be judged that the atomic arrangement is roughly consistent, that is, the crystal orientation is roughly consistent. Similarly, when the angle between the dark lines is less than 5 degrees or less than 2.5 degrees, it can also be judged that the orientation of the crystal is roughly consistent.

[0316] In addition, in ABF-STEM, the smaller the atomic number, the brighter the element is observed, but the contrast corresponding to the atomic number can be obtained in the same way as HAADF-STEM, so the orientation of the crystal can be determined in the same way as the HAADF-STEM image.

[0317] Fig.14A An example of a STEM image showing that the orientations of the layered rock salt type crystals LRS and the rock salt type crystals RS are substantially consistent with each other. Fig. 14B FFT of the region showing rock salt type crystal RS, Fig. 14C FFT of a region showing layered rock-salt type crystalline LRS. Fig. 14B and Fig. 14C The left side shows the composition, the JCPDS (Joint Committee on Powder Diffraction Standard) card number, and the d value and angle calculated from the number. The right side shows the measured value. The spot with O indicates zero-order diffraction, and X is attached to the center of the half point.

[0318] exist Fig. 14B The spots marked with A in the figure come from the 11-1 reflection of the cubic crystal. Fig. 14C The spots marked with A in the figure are from the 0003 reflection of the layered rock salt type. Fig. 14B and Fig. 14C It can be seen that the orientation of the 11-1 reflection of the cubic crystal is roughly consistent with the orientation of the 0003 reflection of the layered rock salt type. Fig. 14BThe straight line of AO and the Fig. 14C The straight lines of AO are substantially parallel. The "substantially consistent" and "substantially parallel" described here refer to the case where the angle is greater than 0 degrees and less than 5 degrees or greater than 0 degrees and less than 2.5 degrees.

[0319] As described above, in FFT and electron diffraction, the orientations of layered rock salt type crystals and rock salt type crystals are sometimes roughly consistent, and the orientations of layered rock salt type crystals are also similar. <0003> The orientation is roughly consistent with the <11-1> orientation of the rock salt type. At this time, their reciprocal points are preferably spot-shaped, that is, not continuous with other reciprocal points. The reciprocal points are spot-shaped and not continuous with other reciprocal points, which means that the crystallinity is high.

[0320] In addition, as described above, when the orientation of the 11-1 reflection of the cubic crystal is roughly the same as the orientation of the 0003 reflection of the layered rock salt type, a spot that does not originate from the 0003 reflection of the layered rock salt type is sometimes observed in a reciprocal space different from the orientation of the 0003 reflection of the layered rock salt type, depending on the incident orientation of the electron beam. Fig. 14C The spot with B in the figure is from the 10-14 reflection of the layered rock salt type. This spot is sometimes at the inverse grid point ( Fig. 14C A) is 52° to 56° (i.e., ∠AOB is 52° to 56°) and d is 0.19nm to 0.21nm. Note that the above index is only an example and does not need to be consistent with the index. For example, the equivalent reciprocal grid points in each may also be used.

[0321] Similarly, a spot not derived from the 11-1 reflection of a cubic crystal is sometimes observed in a reciprocal space different from the orientation at which the 11-1 reflection of a cubic crystal is observed. Fig. 14B The spots in the figure are from the 200 reflection of the cubic crystal. Sometimes, the reflections of 11-1 ( Fig. 14B The diffraction spots are observed at locations where the difference in azimuth between A) is greater than 54° and less than 56° (i.e., ∠AOB is greater than 54° and less than 56°). Note that the above index is only an example and does not need to be consistent with the index. For example, the equivalent reciprocal lattice points in each may also be used.

[0322] Note that when determining the consistency of the crystal orientation, it is preferable to thin the sample to easily observe the (0003) plane of the layered rock salt type. Therefore, in TEM or the like, it is preferable to thin the observation sample using FIB or the like so that the electron beam is incident at [1-210]. It is known that layered rock salt type positive electrode active materials such as lithium cobaltate are likely to exhibit crystal planes on the (0003) plane and equivalent planes thereof and the (10-14) plane and equivalent planes thereof. Therefore, when carefully observing the shape of the positive electrode active material using SEM or the like, the observation sample can be thinned to easily observe the (0003) plane.

[0323] {Li x in a state where x in CoO2 is small}

[0324] The positive electrode active material 100 of one embodiment of the present invention has the above-described distribution of additive elements and crystal structure in the discharged state, and thus the crystal structure of the Li x in CoO2 in a state where x is small is different from that of the conventional positive electrode active material. Note that here, x being small means the case where 0.1 < x ≤ 0.24.

[0325] Hereinafter, the conventional positive electrode active material and the positive electrode active material 100 of one embodiment of the present invention will be compared to illustrate the change in the crystal structure accompanying the change in x in Li x CoO2.

[0326] Fig.12 Show the change in the crystal structure of the conventional positive electrode active material. Fig.12 The shown conventional positive electrode active material is lithium cobaltate (LiCoO2) that does not contain additive elements. Non-Patent Documents 1 to 4 and the like describe the change in the crystal structure of lithium cobaltate that does not contain additive elements.

[0327] In Fig.12 is attached with R-3m O3 to represent the crystal structure of lithium cobaltate with x = 1 in Li x CoO2. In this crystal structure, the unit cell includes three CoO2 layers, and lithium is located between the CoO2 layers. In addition, lithium occupies the octahedral position of six coordinated oxygen atoms. Therefore, this crystal structure is sometimes referred to as the O3 type structure. Note that the CoO2 layer refers to a structure in which octahedral structures of cobalt coordinated to six oxygen atoms are continuously shared by edges on a plane. Sometimes this structure is referred to as a layer composed of octahedrons of cobalt and oxygen. R-3m O3 can represent the coordinates of lithium, cobalt, and oxygen in the unit cell as Li(0, 0, 0)Co(0, 0, 0.5)O(0, 0, 0.23951).

[0328] In addition, it is known that the symmetry of lithium in existing cobalt oxide increases when x=0.5, and the cobalt oxide has a monoclinic crystal structure belonging to the space group P2 / m. In this structure, the unit cell includes one CoO2 layer. Therefore, it is sometimes called an O1-type structure or a monoclinic O1-type structure.

[0329] The positive electrode active material when x=0 has a trigonal crystal structure belonging to the space group P-3m1, and the unit cell also includes a CoO2 layer. Therefore, this crystal structure is sometimes called an O1-type structure or a trigonal O1-type structure. In addition, the trigonal system is sometimes converted into a composite hexagonal lattice and called a hexagonal O1-type.

[0330] In addition, the existing lithium cobalt oxide has a crystal structure belonging to the space group R-3m when x=0.12. It can also be said that the structure is a structure in which CoO2 structures such as the trigonal O1 type structure and LiCoO2 structures such as those belonging to R-3m O3 are alternately stacked. Therefore, this crystal structure is sometimes called an H1-3 type structure. Note that in practice, the insertion and extraction of lithium will occur unevenly, so in experiments, an H1-3 type crystal structure is observed from about x=0.25. In addition, in reality, the number of cobalt atoms in each unit cell of the H1-3 type structure is twice that of other structures. However, in the case of Fig.12 In this specification, in order to facilitate comparison with other crystal structures, the c-axis of the H1-3 type crystal structure is 1 / 2 of the unit cell.

[0331] As an example of an H1-3 type structure, as shown in non-patent document 3, the coordinates of cobalt and oxygen in the unit cell can be represented by Co (0, 0, 0.42150 ± 0.00016), O1 (0, 0, 0.27671 ± 0.00045), and O2 (0, 0, 0.11535 ± 0.00045). O1 and O2 are both oxygen atoms. For example, Rietveld analysis using an XRD pattern can determine which unit cell is used to represent the crystal structure of the positive electrode active material. At this time, a unit cell with a small GOF (goodness of fit) value can be used.

[0332] When repeated Li x When x in CoO2 is 0.24 or less, the crystal structure of conventional lithium cobalt oxide changes repeatedly between the H1-3 type structure and the structure belonging to R-3m O3 in the discharge state (ie, non-equilibrium phase transition) during charging and discharging.

[0333] However, the CoO2 layers of the above two crystal structures deviate greatly. Fig.12As shown by the dotted line and arrow in the figure, in the H1-3 type crystal structure, the CoO2 layer deviates greatly from the R-3m O3 structure in the discharge state. Such dynamic structural changes will have an adverse effect on the stability of the crystal structure.

[0334] Furthermore, the volume difference between the two crystal structures is also large. When comparing the same number of cobalt atoms, the volume difference between the H1-3 structure and the R-3m O3 structure in the discharged state exceeds 3.5%, typically 3.9% or more.

[0335] In addition to the above, the structure of the H1-3 type structure having a continuous CoO2 layer like that of the trigonal O1 type is likely to be unstable.

[0336] Therefore, when charging and discharging are repeated until x becomes less than 0.24, the crystal structure of the existing lithium cobalt oxide collapses. The collapse of the crystal structure causes the deterioration of the cycle characteristics. This is because the collapse of the crystal structure reduces the number of sites where lithium can exist stably, and the insertion and removal of lithium become difficult.

[0337] Fig.11 The crystal structure of the positive electrode active material 100 according to one embodiment of the present invention is shown. x The crystal structure of the bulk 100b of the positive electrode active material 100 when x in CoO2 is about 1 and 0.2. The bulk 100b occupies most of the volume of the positive electrode active material 100 and has a great influence on charging and discharging, so it can be said that it is the part with the greatest influence caused by the deviation of the CoO2 layer and the change in volume.

[0338] In the positive electrode active material 100 of one embodiment of the present invention, Li x The change in the crystal structure between the discharge state where x is 1 and the state where x is less than 0.24 in CoO2 is less than that of the existing positive electrode active materials. More specifically, the deviation of the CoO2 layer between the state where x is 1 and the state where x is less than 0.24 can be reduced. In addition, the volume change when comparing each cobalt atom can be reduced. Therefore, even if the positive electrode active material 100 of one embodiment of the present invention is repeatedly charged and discharged with x being less than 0.24, it is not easy to cause the crystal structure to collapse and good cycle characteristics can be achieved. In addition, the positive electrode active material 100 of one embodiment of the present invention is not easy to cause the crystal structure to collapse and good cycle characteristics can be achieved. In addition, the positive electrode active material 100 of one embodiment of the present invention is not easy to cause the crystal structure to collapse and good cycle characteristics can be achieved. In addition, the positive electrode active material 100 of one embodiment of the present invention is not easy to cause the crystal structure to collapse and the ... x When x in CoO2 is 0.24 or less, it can have a more stable crystal structure than the existing positive electrode active material. x When x in CoO2 is 0.24 or less, short circuit is less likely to occur. In this case, the safety of the secondary battery is further improved, which is preferred.

[0339] The positive electrode active material 100 has the same R-3m O3 type structure as the existing lithium cobalt oxide when x = 1. However, when x is less than 0.24, for example, about 0.2 or about 0.12, the positive electrode active material 100 has a crystal structure different from the above structure.

[0340] When x=0.2, the positive electrode active material 100 of one embodiment of the present invention has a crystal structure belonging to the space group R-3m belonging to the trigonal system. The symmetry of the CoO2 layer of this structure is the same as that of O3. Therefore, this crystal structure is called O3' type structure. Fig.11 The crystal structure is indicated by appending R-3m O3'.

[0341] The coordinates of cobalt and oxygen in the unit cell of the O3' structure can be represented by Co(0, 0, 0.5) and O(0, 0, x) respectively, and are within the range of 0.20≤x≤0.25. In addition, the lattice constants of the unit cell are as follows: the a-axis is preferably 0.2797nm≤a≤0.2837nm, more preferably 0.2807nm≤a≤0.2827nm, and typically a=0.2817nm. The c-axis is preferably 1.3681nm≤c≤1.3881nm, more preferably 1.3751nm≤c≤1.3811nm, and typically c=1.3781nm.

[0342] In the O3' type structure, ions of cobalt, nickel, magnesium, etc. occupy the positions coordinated to six oxygen atoms. In addition, light elements such as lithium may occupy the positions coordinated to four oxygen atoms.

[0343] like Fig.11 In the figure, the dotted line indicates that there is almost no deviation between the CoO2 layer of the R-3m(O3) type crystal structure and the O3' type crystal structure in the discharged state.

[0344] In addition, the difference in volume of the same number of cobalt atoms between the R-3m (O3) type structure and the O3' type structure in the discharged state is 2.5% or less, more specifically 2.2% or less, and typically 1.8%.

[0345] Thus, in the positive electrode active material 100 of one embodiment of the present invention, Li xWhen x in CoO2 is smaller, that is, when more lithium is released, the change in the crystal structure is suppressed compared with the existing positive active material. In addition, the change in volume when compared by the same number of cobalt atoms is also suppressed. Therefore, the crystal structure of the positive active material 100 is not easy to collapse even if x is repeatedly charged and discharged to be less than 0.24. Therefore, the decrease in the charge and discharge capacity of the positive active material 100 caused by the charge and discharge cycle is suppressed. In addition, a larger amount of lithium can be stably used than the existing positive active material, so the discharge capacity per unit weight and unit volume of the positive active material 100 is larger. Therefore, by using the positive active material 100, a secondary battery with a higher discharge capacity per unit weight and unit volume can be manufactured.

[0346] In addition, it was confirmed that the positive electrode active material 100 x When x in CoO2 is 0.15 or more and 0.24 or less, it sometimes has an O3' structure, and it is also considered to have an O3' structure when x exceeds 0.24 and is 0.27 or less. x In addition to x in CoO2, it is also affected by the number of charge and discharge cycles, charge and discharge current, temperature, electrolyte, etc., and is therefore not limited to the above range of x.

[0347] Therefore, the positive electrode active material 100 in Li x When x in CoO 2 exceeds 0.1 and is equal to or less than 0.24, the entire bulk body 100 b of the positive electrode active material 100 does not need to have an O3′ type structure.

[0348] In addition, it may have another crystal structure or may be partially amorphous.

[0349] In addition, in order to achieve Li x In the case of CoO2 with a small x value, a high charging voltage is generally required for charging. x The state in which x in CoO2 is smaller is referred to as a state of charging at a high charging voltage. For example, when CC / CV charging is performed at a voltage of 4.6V or more based on the potential of lithium metal in an environment of 25°C, an H1-3 type structure is presented in the existing positive electrode active material. Therefore, it can be said that a charging voltage of 4.6V or more based on the potential of lithium metal is a high charging voltage. In addition, in this specification, etc., unless otherwise specified, the charging voltage is expressed based on the potential of lithium metal.

[0350] Therefore, it can be said that the positive electrode active material 100 of one embodiment of the present invention can maintain a crystal structure having R-3m O3 symmetry even when charged at a high charging voltage of 4.6V or higher at 25°C, so it is preferred. In addition, it can be said that it can have an O3' type structure when charged at a higher charging voltage of 4.65V or higher and 4.7V or lower at 25°C, so it is preferred.

[0351] The positive electrode active material 100 sometimes has an H1-3 type structure only when the charging voltage is further increased. In addition, as described above, the crystal structure is affected by the number of charge and discharge cycles, charge and discharge current, temperature, electrolyte, etc., so when the charging voltage is lower, for example, even at 25°C and the charging voltage is 4.5V or more and less than 4.6V, the positive electrode active material 100 of one embodiment of the present invention sometimes has an O3' type structure.

[0352] In addition, for example, when graphite is used as the negative electrode active material of the secondary battery, the voltage of the secondary battery is lower than the above voltage by the difference between the potential of graphite and the potential of lithium metal. The potential of graphite is about 0.05V to 0.2V based on the potential of lithium metal. Therefore, the secondary battery using graphite as the negative electrode active material has the same crystal structure as the case where the voltage is obtained by subtracting the potential of graphite from the above voltage.

[0353] In addition, Fig.11 In the O3' type crystal structure, lithium exists in all lithium positions with equal probability, but the present invention is not limited to this. It can also exist in a concentrated manner in a part of the lithium positions, for example, it can also have a Fig.12 The monoclinic O1 crystal structure (Li 0.5 The distribution of lithium can be analyzed, for example, by neutron diffraction.

[0354] In addition, although the O3' type structure contains lithium irregularly between the layers, it can also have a crystal structure similar to the CdCl2 type crystal structure. This crystal structure similar to the CdCl2 type crystal structure is similar to the crystal structure of lithium nickel oxide charged to become Li 0.06 However, pure lithium cobalt oxide or layered rock salt-type positive electrode active materials containing a large amount of cobalt generally do not have a CdCl2-type crystal structure.

[0355] In addition, the concentration gradient of the added element preferably has the same gradient in multiple regions of the surface portion 100a of the positive electrode active material 100. In other words, the barrier film derived from the added element preferably exists homogeneously in the surface portion 100a. Even if a part of the surface portion 100a is reinforced, if there is a part without reinforcement, stress may be concentrated in this part. When stress is concentrated in a part of the positive electrode active material 100, defects such as cracks may occur from this part, thereby causing the positive electrode active material to rupture and the discharge capacity to decrease.

[0356] [Grain Boundary]

[0357] Preferably, in addition to the distribution described above, at least a part of the additional element in the positive electrode active material 100 according to one embodiment of the present invention is unevenly distributed in the grain boundary 101 and its vicinity.

[0358] In this specification, etc., "non-uniformly distributed" means that the concentration of an element in an arbitrary region is different from that in other regions. "Non-uniformly distributed" is synonymous with "segregation", "precipitation", "non-uniform", "deviation" and "mixture of high-concentration regions and low-concentration regions".

[0359] For example, the magnesium concentration in the grain boundary 101 and its vicinity of the positive electrode active material 100 is preferably higher than that in other regions of the block 100b. In addition, the fluorine concentration in the grain boundary 101 and its vicinity is preferably higher than that in other regions of the block 100b. In addition, the nickel concentration in the grain boundary 101 and its vicinity is also preferably higher than that in other regions of the block 100b. In addition, the aluminum concentration in the grain boundary 101 and its vicinity is also preferably higher than that in other regions of the block 100b.

[0360] The grain boundary 101 is a type of surface defect. Therefore, it tends to be unstable and easily starts to change the crystal structure like the particle surface. Therefore, the higher the concentration of the added element in the grain boundary 101 and its vicinity, the more effectively the change of the crystal structure can be suppressed.

[0361] In addition, when the magnesium and fluorine concentrations in the grain boundary 101 and its vicinity are high, even if cracks are generated along the grain boundary 101 of the positive electrode active material 100 of one embodiment of the present invention, the magnesium and fluorine concentrations in the vicinity of the surface generated by the cracks become high. Therefore, the corrosion resistance of the positive electrode active material to hydrofluoric acid after the cracks are generated can also be improved.

[0362] [Particle size]

[0363] When the particle size of the positive electrode active material 100 in one embodiment of the present invention is too large, there are the following problems: the diffusion of lithium becomes difficult; when applied on the current collector, the surface of the active material layer is too rough, etc. On the other hand, when the particle size of the positive electrode active material 100 is too small, there are the following problems: excessive reaction with the electrolyte, etc. Therefore, the median particle size (D50) is preferably greater than 1 μm and less than 100 μm, more preferably greater than 2 μm and less than 40 μm, and further preferably greater than 5 μm and less than 30 μm. Alternatively, it is preferably greater than 1 μm and less than 40 μm. Alternatively, it is preferably greater than 1 μm and less than 30 μm. Alternatively, it is preferably greater than 2 μm and less than 100 μm. Alternatively, it is preferably greater than 2 μm and less than 30 μm. Alternatively, it is preferably greater than 5 μm and less than 100 μm. Alternatively, it is preferably greater than 5 μm and less than 40 μm.

[0364] In addition, by mixing particles of different particle sizes and using them for the positive electrode, the electrode density can be increased, and a secondary battery with high energy density can be realized, so it is preferred. The positive electrode active material 100 with a relatively small particle size is expected to have high charge and discharge rate characteristics. The positive electrode active material 100 with a relatively large particle size is expected to have high charge and discharge cycle characteristics and can maintain a large discharge capacity.

[0365] In addition, when particles with different median particle sizes (D50) are mixed and used in the positive electrode, considering the phenomenon that lithium is sequentially separated from the surface of the positive electrode active material, the Li 100 of the positive electrode active material with a relatively small particle size is x The speed at which x in CoO2 decreases is faster than that of the positive electrode active material 100 having a relatively large particle size. Therefore, when powder XRD measurement is performed on a positive electrode active material obtained by mixing particles of different particle sizes, both the O3' type structure and the monoclinic O1(15) type structure may be detected.

[0366] [Analysis method]

[0367] {Evaluation of crystal structure}

[0368] In order to determine whether a positive electrode active material is in Li x The positive electrode active material 100 of one embodiment of the present invention, which has an O3' type structure and / or a monoclinic O1(15) type structure when x in CoO2 is small, can contain Li x The positive electrode of the positive electrode active material having a smaller x in CoO2 is determined by analysis using XRD, electron diffraction, neutron diffraction, electron spin resonance (ESR), nuclear magnetic resonance (NMR) or the like.

[0369] In particular, XRD is preferred because of the following advantages: the symmetry of transition metals such as cobalt in the positive electrode active material can be analyzed with high resolution; the height of crystallinity and the orientation of crystallinity can be compared; the periodic distortion of the lattice and the grain size can be analyzed; sufficient accuracy can be obtained when directly measuring the positive electrode obtained by disassembling a secondary battery, etc. Through XRD, especially powder XRD, a diffraction peak reflecting the crystal structure of the bulk 100b of the positive electrode active material 100 that occupies most of the volume of the positive electrode active material 100 can be obtained.

[0370] When analyzing the crystal size by powder XRD, it is preferable to perform the measurement without affecting the orientation due to pressure, etc. For example, it is preferable to take out the positive electrode active material from the positive electrode obtained by disassembling the secondary battery as a powder sample for measurement.

[0371] As described above, the positive electrode active material 100 according to one embodiment of the present invention is characterized in that: x When x in CoO2 is 1 or 0.24 or less, the crystal structure changes less. When charged at a high voltage, materials with a crystal structure that changes greatly by 50% or more cannot withstand repeated high-voltage charging and discharging, so they are not preferred.

[0372] Note that sometimes, the O3' type structure or the monoclinic O1(15) type structure cannot be obtained by simply adding additive elements. For example, even under the same conditions of lithium cobalt oxide containing magnesium and fluorine or lithium cobalt oxide containing magnesium and aluminum, depending on the concentration and distribution of the additive elements in Li x When x in CoO2 is 0.24 or less, the O3' type structure and / or the monoclinic O1(15) type structure may account for 60% or more, or the H1-3 type structure may account for 50% or more.

[0373] In addition, when x is too small such as 0.1 or less or when the charging voltage exceeds 4.9 V, an H1-3 type or trigonal O1 type structure is also generated in the positive electrode active material 100 of one embodiment of the present invention. Therefore, in order to determine whether it is a positive electrode active material 100 of one embodiment of the present invention, analysis of the crystal structure such as XRD and information such as the charging capacity or the charging voltage are required.

[0374] However, sometimes the positive electrode active material in a state where x is small changes its crystal structure when exposed to air. For example, sometimes it changes from an O3'-type structure and a monoclinic O1(15)-type structure to an H1-3-type structure. Therefore, all samples used in analyzing the crystal structure are preferably treated in an inert atmosphere such as an argon atmosphere.

[0375] In addition, by analyzing by XPS, Energy Dispersive X-ray Spectroscopy (EDX), Electron Probe Microanalysis (EPMA), or the like, it can be determined whether the distribution of the additive element contained in a positive electrode active material is in the above-mentioned state.

[0376] The crystal structure of the surface layer portion 100 a , the grain boundary 101 , and the like can be analyzed by performing electron diffraction or the like on a cross section of the positive electrode active material 100 .

[0377] {Powder resistance measurement}

[0378] The positive electrode active material 100 of one embodiment of the present invention has a stable crystal structure even at a high charging voltage. The crystal structure of the positive electrode active material in the charged state is stable, so the reduction in charge and discharge capacity due to repeated charge and discharge can be suppressed. As a feature of the positive electrode active material 100 having the above-mentioned excellent characteristics, the following can be cited: x When x in CoO2 is small, it has an O3' type and / or monoclinic O1(15) type crystal structure (to be described later in {XRD}). In addition, when the positive electrode active material 100 is subjected to STEM-EDX analysis, it can be cited that there is a preferred distribution of the added element X and the added element Y ((to be described later in {EDX}). In addition, the positive electrode active material 100 of one embodiment of the present invention also has characteristics in terms of powder volume resistivity.

[0379] As a feature of the positive electrode active material 100 of one embodiment of the present invention, the powder volume resistivity of the positive electrode active material 100 at a pressure of 64 MPa is preferably 1.0×10 4 Ω·cm or more, more preferably 1.0×10 5 Ω·cm or more, more preferably 1.0×10 6 Ω·cm or more. In addition, when the pressure is 64MPa, it is preferably 1.0×10 9 Ω·cm or less, more preferably 1.0×10 8 Ω·cm or less, more preferably 1.0×10 7 Ω·cm or less.

[0380] The positive electrode active material 100 having the above volume resistivity has a stable crystal structure even at a high voltage, and can be used as an indicator that the surface layer 100a is well formed, which is very important for the stability of the crystal structure of the positive electrode active material in a charged state. In other words, the surface layer 100a preferably has a high resistance.

[0381] However, when the high resistance region exists thicker from the surface to the inside of the positive electrode active material 100, the battery reaction may be blocked. Therefore, it is more preferred that only a thin region near the surface of the surface portion 100a has high resistance. That is, in the surface portion 100a, the high resistance region preferably exists thinner from the surface to the inside. For example, the region where Mg in the surface portion 100a exists at a high concentration will become a high resistance region. Therefore, Mg is preferably located in the surface portion 100a.

[0382] A method for measuring the powder volume resistivity of the positive electrode active material 100 according to one embodiment of the present invention will be described.

[0383] In order to measure the volume resistivity of the powder, it is preferable to set a mechanical part including a terminal for resistance measurement and a mechanism for applying pressure to the powder as the measurement object. As a measuring device including a terminal for resistance measurement and a mechanism for applying pressure to the powder (sample) as the measurement object, for example, MCP-PD51 manufactured by Mitsubishi Chemical Analysis Technology Co., Ltd. can be used. As a resistance meter, Loresta-GP or Hiresta-GP can be used. Loresta-GP can be used for the measurement of low-resistance samples using the four-probe method, and Hiresta-UP can be used for the measurement of high-resistance samples using the two-probe method. Note that a stable environment such as a dry room is preferably used as the measurement environment, but a general laboratory environment can also be used. As a dry room environment, for example, an environment with a temperature of 20°C or more and 25°C or less and a dew point of -40°C or less is preferred. As a general laboratory environment, it can also be an environment with a temperature of 15°C or more and 30°C or less and a humidity of 30% or more and 70% or less.

[0384] The measurement of the powder volume resistivity using the above-mentioned measuring device is described. First, a powder sample is placed in a measuring unit. The measuring unit has a structure in which the powder sample is in contact with a terminal for resistance measurement, and has a structure in which pressure can be applied to the powder sample. In addition, the measuring unit also has a structure for measuring the thickness of the powder sample. Specifically, the above-mentioned measuring unit has a cylindrical space in which the powder sample is placed.

[0385] In the measurement of the thickness resistivity of the powder, the resistance and thickness of the powder are measured while pressure is applied to the powder. Pressure can be applied to the powder under various conditions. For example, the resistance and thickness of the powder are measured under pressure conditions of 13MPa, 25MPa, 38MPa, 51MPa, and 64MPa. The volume resistivity of the powder can be calculated based on the measured values ​​of the resistance and thickness of the powder.

[0386] The calculation method of volume resistivity is explained. When measuring by the two-probe method using Hiresta-UP, the volume resistivity is obtained by multiplying the resistance of the powder by the area of ​​the electrode pressurizing the powder and then dividing it by the thickness of the powder. In addition, when measuring by the four-terminal method using Loresta-GP, the volume resistivity is obtained by multiplying the resistance of the powder by the correction factor and then dividing it by the thickness of the powder. The correction factor is a value that varies depending on the sample shape, size and measurement position, and can be obtained using the calculation software built into Loresta-GP.

[0387] When the above measurement is performed, the powder volume resistivity of the positive electrode active material 100 of one embodiment of the present invention under a pressure of 64 MPa is preferably 1.0×10 4 Ω·cm or more, more preferably 1.0×10 5 Ω·cm or more, more preferably 1.0×10 6 Ω·cm or more. In addition, when the pressure is 64MPa, it is preferably 1.0×10 9 Ω·cm or less, more preferably 1.0×10 8 Ω·cm or less, more preferably 1.0×10 7 Ω·cm or less. A battery including the positive electrode active material 100 exhibiting such a volume resistivity exhibits a preferred cycle characteristic in a charge-discharge cycle test under high voltage conditions. In addition, a battery that is not easily ignited in an internal short circuit test such as a needle penetration test can be realized.

[0388] {Charging method}

[0389] As charging for determining whether a certain composite oxide is the positive electrode active material 100 of one embodiment of the present invention, for example, a coin battery (CR2032 type, 20 mm in diameter, 3.2 mm in height) using lithium metal as a counter electrode can be manufactured and charged.

[0390] More specifically, as the positive electrode, a positive electrode obtained by applying a slurry obtained by mixing a positive electrode active material, a conductive material, and a binder to a positive electrode current collector of an aluminum foil can be used.

[0391] As described above, lithium metal can be used for the counter electrode, but materials other than lithium metal can also be used. When materials other than lithium metal are used, the potential of the secondary battery is different from the potential of the positive electrode. Unless otherwise specified, the voltage and potential in this specification, etc. are the potential of the positive electrode.

[0392] As the lithium salt contained in the electrolyte, 1 mol / L lithium hexafluorophosphate (LiPF6) is used. As the electrolyte, a solution of ethylene carbonate (EC) and diethyl carbonate (DEC) in a volume ratio of EC:DEC=3:7 and 2 wt% vinylene carbonate (VC) can be used.

[0393] As the separator, a polypropylene porous film having a thickness of 25 μm can be used.

[0394] The positive electrode can and the negative electrode can may be formed of stainless steel (SUS).

[0395] The coin cell manufactured under the above conditions is charged at any voltage (for example, 4.5V, 4.55V, 4.6V, 4.65V, 4.7V, 4.75V or 4.8V). There is no limitation on the charging method as long as it can be charged at any voltage and for a sufficient time. For example, when charging with CCCV, the current in CC charging can be set to be greater than 20mA / g and less than 100mA / g. CV charging can be performed until it is greater than 2mA / g and less than 10mA / g. In order to observe the phase change of the positive electrode active material, it is preferred to charge at the above-mentioned smaller current value. In order to observe the phase change of the positive electrode active material, it is preferred to charge at the above-mentioned smaller current value. It is difficult to perform XRD measurement below 0°C, so the temperature is set to 25°C. Note that the temperature of 25°C is just an example. After charging in this way, the coin cell is disassembled in a glove box in an argon atmosphere and the positive electrode is taken out, thereby obtaining a positive electrode active material of any charging capacity. When various analyses are performed later, in order to prevent reaction with external components, it is preferably sealed under an argon atmosphere. For example, XRD can be performed under the condition of a sealed container sealed in an argon atmosphere. In addition, it is preferred to take out the positive electrode immediately after charging for analysis. Specifically, it is preferably performed within 1 hour after charging, and more preferably within 30 minutes after charging.

[0396] In addition, when analyzing the crystal structure of the charged state after multiple charge and discharge, the multiple charge and discharge conditions may also be different from the above-mentioned charging conditions. For example, charging can be performed at a current value of 20 mA / g or more and 100 mA / g or less to perform constant current charging to any voltage (for example, 4.6 V, 4.65 V, 4.7 V, 4.75 V or 4.8 V), and then constant voltage charging can be performed at a current value of 2 mA / g or more and 10 mA / g or less, and discharging can be performed at a constant current discharge to 2.5 V at a current value of 20 mA / g or more and 100 mA / g or less.

[0397] Furthermore, when analyzing the crystal structure in a discharged state after multiple charge and discharge, for example, constant current discharge to 2.5 V may be performed at a current value of 20 mA / g or more and 100 mA / g or less.

[0398] {XRD}

[0399] There is no limitation on the apparatus and conditions for XRD measurement as long as there is appropriate adjustment and calibration. For example, the measurement can be performed with the following apparatus and conditions.

[0400] XRD device: D8 ADVANCE manufactured by Bruker AXS

[0401] X-ray: CuKα1

[0402] Output: 40kV, 40mA

[0403] Emission Angle: Div. Slit, 0.5°

[0404] Detector: LynxEye

[0405] Scanning mode: 2θ / θ continuous scanning

[0406] Measuring range (2θ): 15° to 90°

[0407] Step width (2θ): set to 0.01°

[0408] Counting time: 1 second / step

[0409] Sample stage rotation: 15rpm

[0410] As a standard sample for adjustment and calibration, for example, a standard sintered alumina plate SRM 1976 of NIST (National Institute of Standards and Technology) or the like can be used.

[0411] When the sample to be measured is a powder, the sample can be mounted by placing it in a glass sample holder, or by sprinkling the sample on a silicon non-reflective plate coated with grease, etc. When the sample to be measured is a positive electrode, the positive electrode active material layer can be mounted according to the measurement surface required by the device by attaching the positive electrode to the substrate with double-sided tape.

[0412] The monochromatization of characteristic X-rays can be performed using a filter or the like, or using XRD data analysis software after obtaining the XRD pattern. For example, DEFFRAC.EVA (XRD data analysis software manufactured by Bruker) can be used to remove the peaks passing through CuKα2 rays and extract only the peaks passing through CuKα1 rays. In addition, the software can also be used to perform background removal, etc.

[0413] In this specification, etc., when the value of 2θ of a certain diffraction peak is mentioned, it means the value of 2θ of the peak top of the diffraction peak that appears in the XRD pattern after fitting the calculation model. There is no particular limitation on the crystal structure analysis software used for fitting, for example, TOPASver.3 (crystal structure analysis software manufactured by Bruker Corporation) can be used.

[0414] Fig.15 The diffraction distributions of the O3 type structure, the O3' type structure, and the monoclinic O1(15) type structure when CuKα1 is used as X-ray are shown. Fig.16 Also shown are an ideal powder XRD pattern obtained by CuKα1 radiation calculated from a model of the H1-3 type structure and an ideal XRD pattern obtained by CuKα1 radiation calculated from a trigonal O1 type structure of x=0. Fig.17A and Fig. 17B All of the above XRD patterns are shown. Note that in the accompanying drawings, the range of 2θ is 18° to 21°, and the range of 2θ is 42° to 46°. The patterns of LiCoO2(O3) and CoO2(O1) were prepared using Reflex Powder Diffraction, one of the modules of Materials Studio (BIOVIA), using crystal structure information obtained from ICSD (Inorganic Crystal Structure Database) (see non-patent document 5). At this time, the range of 2θ was set to 15° to 75°, Step size = 0.01, and wavelength λ = 1.54×10 -10 m, Monochromator is set to single. The pattern of the H1-3 type structure is similarly prepared with reference to the crystal structure information described in non-patent document 3. The patterns of the O3' type structure and the monoclinic O1(15) type structure are prepared by the following method: the crystal structure is inferred from the XRD pattern of the positive electrode active material 100 of one embodiment of the present invention and fitted using TOPAS ver.3 (crystal structure analysis software manufactured by Bruker).

[0415] like Fig.15 , Fig.17A and Fig. 17B As shown, in the O3'-type structure, diffraction peaks appear at 2θ of 19.25±0.12° (19.13° or more and less than 19.37°) and 2θ of 45.47±0.10° (45.37° or more and less than 45.57°).

[0416] In the monoclinic O1(15) type structure, diffraction peaks appear at 2θ of 19.47±0.10° (19.37° or more and 19.57° or less) and 2θ of 45.62±0.05° (45.57° or more and 45.67° or less).

[0417] However, if Fig.16 , Fig.17A and Fig. 17B As shown, in the H1-3 type structure and the trigonal O1 type structure, the peak does not appear at the above position. x The presence of peaks at 19.13° to less than 19.37° and / or 19.37° to 19.57° and 45.37° to less than 45.57° and / or 45.57° to 45.67° in a state where x in CoO2 is small is a characteristic of the positive electrode active material 100 of one embodiment of the present invention.

[0418] It can be said that the positions of the diffraction peaks observed by XRD are close to those of the crystal structure when x=1 and the crystal structure when x≤0.24. More specifically, the difference in 2θ between the peaks appearing at 42° or more and 46° or less in the main diffraction peaks of the crystal structure when x=1 and the crystal structure when x≤0.24 is 0.7° or less, preferably 0.5° or less.

[0419] In addition, the positive electrode active material 100 of one embodiment of the present invention is Li x When x in CoO2 is small, it has an O3' type structure and / or a monoclinic O1(15) type structure, but it is not necessary for all particles to have an O3' type structure and / or a monoclinic O1(15) type structure. In addition, it may have other crystal structures or partially be amorphous. Note that when performing Rietveld analysis on the XRD pattern, the O3' type structure and / or the monoclinic O1(15) type structure is preferably 50% or more, more preferably 60% or more, and further preferably 66% or more. When the O3' type structure and / or the monoclinic O1(15) type structure is 50% or more, more preferably 60% or more, and further preferably 66% or more, a positive electrode active material with sufficiently excellent cycle characteristics can be achieved.

[0420] Furthermore, the O3' type structure and / or the monoclinic O1(15) type structure as determined by Rietveld analysis after 100 or more charge and discharge cycles from the start of measurement is preferably 35% or more, more preferably 40% or more, and even more preferably 43% or more.

[0421] In addition, when the Rietveld analysis is similarly performed, the H1-3 type structure and the O1 type structure are preferably 50% or less. Alternatively, they are preferably 34% or less. Alternatively, they are more preferably substantially not observed.

[0422] In addition, the sharpness of the diffraction peak in the XRD pattern indicates the height of crystallinity. Therefore, each diffraction peak after charging is preferably sharp, that is, the half width (e.g., half maximum full width) is preferably narrow. The half width of the peak of the same crystalline phase varies according to the measurement conditions of XRD and the value of 2θ. When the above-mentioned measurement conditions are adopted, for example, the half maximum full width of the peak observed at 2θ of 43° or more and 46° or less is preferably 0.2° or less, more preferably 0.15° or less, and further preferably 0.12° or less. Note that it is not necessary for all peaks to meet the above conditions. As long as a part of the peaks meet the above conditions, it can be said that the crystallinity of its crystalline phase is higher. The above-mentioned higher crystallinity fully contributes to the stabilization of the crystal structure after charging.

[0423] In addition, the grain size of the O3' type structure and the monoclinic O1(15) type structure of the positive electrode active material 100 is reduced to only about 1 / 20 of that of LiCoO2(O3) in the discharged state. Therefore, even under the same XRD measurement conditions as the positive electrode before charge and discharge, the Li x When x in CoO2 is small, a clear peak of O3' type structure and / or monoclinic O1(15) type structure is confirmed. On the other hand, even if a part of the existing LiCoO2 may have a structure similar to O3' type structure and / or monoclinic O1(15) type structure, the grain size will become smaller and its peak will become wider and smaller. The grain size can be obtained from the half width of the XRD peak.

[0424] As described above, the positive electrode active material 100 of one embodiment of the present invention preferably has a small influence of the Jan-Teller effect. In addition to cobalt, a transition metal such as nickel or manganese may be contained as an additive element as long as the influence of the Jan-Teller effect is small.

[0425] By performing XRD analysis, the ratio of nickel and manganese and the range of the lattice constant, which are estimated to be less affected by the Jahn-Teller effect in the positive electrode active material, were examined.

[0426] FIG. 18 shows the results of calculating the lattice constants of the a-axis and the c-axis by XRD when the positive electrode active material 100 according to one embodiment of the present invention has a layered rock salt type crystal structure and contains cobalt and nickel. Fig.18A , Fig.18B The results for the a-axis and c-axis are shown respectively. The XRD patterns used for these calculations are the powders after the positive electrode active material is synthesized and before being assembled into the positive electrode. The nickel concentration on the horizontal axis represents the nickel concentration when the sum of the number of atoms of cobalt and nickel is 100%.

[0427] Fig. 18C The results showing the lattice constants are shown in Fig.18A and Fig.18BThe value obtained by dividing the a-axis lattice constant of the positive electrode active material by the c-axis lattice constant (a-axis / c-axis).

[0428] from Fig. 18C It can be seen that the a-axis / c-axis changes significantly between the nickel concentration of 5% and 7.5%, and the a-axis becomes more skewed when the nickel concentration is 7.5%. This distortion may be caused by the Jan-Teller distortion of trivalent nickel. When the nickel concentration is lower than 7.5%, an excellent positive electrode active material with small Jan-Teller distortion can be obtained.

[0429] In addition, the above-mentioned nickel concentration range does not necessarily apply to the surface portion 100a. That is, the nickel concentration of the surface portion 100a may be higher than the above-mentioned concentration.

[0430] In summary, when examining the preferred range of the lattice constant, it can be seen that in the positive electrode active material of one embodiment of the present invention, the lattice constant of the a-axis in the layered rock salt type crystal structure of the positive electrode active material 100 in the non-charged or discharged state, which can be inferred from the XRD pattern, is preferably greater than 2.814×10 -10 m and less than 2.817×10 -10 m, and the lattice constant of the c-axis is preferably greater than 14.05×10 -10 m and less than 14.07×10 -10 m. The state without charge and discharge may refer to, for example, the state of powder before the positive electrode of the secondary battery is produced.

[0431] Alternatively, the value of the a-axis lattice constant divided by the c-axis lattice constant (a-axis / c-axis) in the layered rock salt type crystal structure of the positive electrode active material 100 in the non-charged or discharged state is preferably greater than 0.20000 and less than 0.20049.

[0432] Alternatively, in the layered rock salt type crystal structure possessed by the positive electrode active material 100 in a state without charge and discharge or in a discharged state, when XRD analysis is performed, a first peak at 2θ of 18.50° or more and 19.30° or less is sometimes observed, and a second peak at 2θ of 38.00° or more and 38.80° or less is observed.

[0433] {XPS}

[0434] X-ray photoelectron spectroscopy (XPS) can analyze the depth range of about 2nm to 8nm (generally less than 5nm) from the surface when analyzing inorganic oxides and using monochromated aluminum Kα line as X-ray, so the concentration of each element in about half of the depth direction of the surface part 100a can be quantitatively analyzed. In addition, by performing narrow scan analysis, the bonding state of the elements can be analyzed. The measurement accuracy of XPS is about ±1 atomic% in many cases. Although it depends on the element, the detection limit is about 1 atomic%.

[0435] In the positive electrode active material 100 of one embodiment of the present invention, the concentration of one or more selected from the added elements in the surface portion 100a is preferably higher than the concentration in the bulk 100b. That is, the concentration of one or more selected from the added elements in the surface portion 100a is preferably higher than the average concentration of the positive electrode active material 100 as a whole. Therefore, for example, it can be said that the concentration of one or more selected from the added elements in the surface portion 100a measured by XPS or the like is preferably higher than the average concentration of the positive electrode active material 100 as a whole measured by ICP-MS (inductively coupled plasma mass spectrometry) or GD-MS (glow discharge mass spectrometry analysis). For example, it is preferred that the concentration of magnesium in at least a portion of the surface portion 100a measured by XPS or the like is higher than the average magnesium concentration of the positive electrode active material 100 as a whole. In addition, it is preferred that the concentration of nickel in at least a portion of the surface portion 100a is higher than the average nickel concentration of the positive electrode active material 100 as a whole. In addition, it is preferred that the concentration of aluminum in at least a portion of the surface portion 100a is higher than the average aluminum concentration of the positive electrode active material 100 as a whole. In addition, it is preferable that the fluorine concentration of at least a portion of the surface layer portion 100 a is higher than the average fluorine concentration of the entire positive electrode active material 100 .

[0436] Note that the surface and surface layer 100a of the positive electrode active material 100 of one embodiment of the present invention do not include carbonates, hydroxyls, etc. chemically adsorbed after the positive electrode active material 100 is manufactured. In addition, it does not include electrolytes, adhesives, conductive materials, or compounds derived from them attached to the surface of the positive electrode active material 100. Therefore, when quantifying the elements contained in the positive electrode active material, the following correction can also be performed, that is, removing carbon, hydrogen, excess oxygen, excess fluorine, etc. that may be detected by surface analysis such as XPS. For example, XPS can identify the type of bonding by analysis, and can also perform corrections to remove CF bonds derived from the adhesive.

[0437] In addition, the samples of the positive electrode active material and the positive electrode active material layer can be washed before various analyses to remove the electrolyte, adhesive, conductive material or compounds derived from them attached to the surface of the positive electrode active material. At this time, sometimes lithium is dissolved in the solvent used for washing, but the added element is not easy to dissolve, so it has no effect on the atomic ratio of the added element.

[0438] In addition, the concentration of the added element can also be compared with the ratio of cobalt. By using the ratio with cobalt, the influence of carbonates chemically adsorbed after manufacturing the positive electrode active material can be reduced for comparison, so it is preferred. For example, the ratio of the number of atoms of magnesium and cobalt obtained by XPS analysis is preferably 0.4 or more and 1.5 or less. On the other hand, the Mg / Co obtained by ICP-MS analysis is preferably 0.001 or more and 0.06 or less.

[0439] Similarly, in order to fully ensure the path for the insertion and removal of lithium, the concentration of lithium and cobalt in the surface portion 100a of the positive electrode active material 100 is preferably higher than the concentration of each added element. This can be said that the concentration of lithium and cobalt in the surface portion 100a is preferably higher than the concentration of one or more of the added elements selected from the added elements contained in the surface portion 100a measured by XPS, etc. For example, the concentration of cobalt in at least a portion of the surface portion 100a measured by XPS, etc. is preferably higher than the concentration of magnesium in at least a portion of the surface portion 100a measured by XPS, etc. Similarly, the concentration of lithium is preferably higher than the concentration of magnesium. In addition, the concentration of cobalt is preferably higher than the concentration of nickel. Similarly, the concentration of lithium is preferably higher than the concentration of nickel. In addition, the concentration of cobalt is preferably higher than the concentration of aluminum. Similarly, the concentration of lithium is preferably higher than the concentration of aluminum. In addition, the concentration of cobalt is preferably higher than the concentration of fluorine. Similarly, the concentration of lithium is preferably higher than the concentration of fluorine.

[0440] In addition, the added element Y such as aluminum is more preferably widely distributed in a deeper region, for example, a region with a depth of 5 nm or more and within 50 nm from the surface. Therefore, the added element Y such as aluminum is detected in the overall analysis of the positive electrode active material 100 using ICP-MS, GD-MS, etc., but it is more preferred that the concentration of the added element Y such as aluminum in XPS, etc. is below the detection limit.

[0441] Furthermore, when the positive electrode active material 100 of one embodiment of the present invention is subjected to XPS analysis, the number of atoms of magnesium relative to the number of atoms of cobalt is preferably 0.4 times or more and 1.2 times or less, and more preferably 0.65 times or more and 1.0 times or less. In addition, the number of atoms of nickel relative to the number of atoms of cobalt is preferably 0.15 times or less, and more preferably 0.03 times or more and 0.13 times or less. In addition, the number of atoms of aluminum relative to the number of atoms of cobalt is preferably 0.12 times or less, and more preferably 0.09 times or less. In addition, the number of atoms of fluorine relative to the number of atoms of cobalt is preferably 0.3 times or more and 0.9 times or less, and more preferably 0.1 times or more and 1.1 times or less. It can also be said that the above range means that the above-mentioned added element is not attached to the narrow range of the surface of the positive electrode active material 100, but is widely distributed in the surface layer 100a of the positive electrode active material 100 at a preferred concentration.

[0442] When performing XPS analysis, for example, monochromatized aluminum Kα rays are used as X-rays. In addition, for example, the extraction angle is 45°. For example, the measurement can be performed with the following apparatus and conditions.

[0443] Measuring device: Quantera II manufactured by PHI

[0444] X-ray: monochromated aluminum Kα (1486.6 eV)

[0445] Detection area:

[0446] Detection depth: about 4nm to 5nm (extraction angle is 45°)

[0447] Measurement spectrum: wide scan, narrow scan for each detected element

[0448] In addition, when the positive electrode active material 100 of one embodiment of the present invention is analyzed by XPS, it is preferred that the peak of the bonding energy between fluorine and other elements is 682 eV or more and less than 685 eV, more preferably about 684.3 eV. This value is different from the bonding energy of lithium fluoride of 685 eV and the bonding energy of magnesium fluoride of 686 eV.

[0449] In addition, when the positive electrode active material 100 of one embodiment of the present invention is analyzed by XPS, it is preferred that the peak of the bonding energy between magnesium and other elements is 1302 eV or more and less than 1304 eV, and more preferably about 1303 eV. This value is different from the bonding energy of magnesium fluoride of 1305 eV, and is close to the bonding energy value of magnesium oxide.

[0450] {EDX}

[0451] One or two of the selected added elements contained in the positive electrode active material 100 preferably have a concentration gradient. In addition, the positive electrode active material 100 is more preferably different according to the depth of the added element concentration peak from the surface. The concentration gradient of the added element can be evaluated by, for example, exposing the cross section of the positive electrode active material 100 by FIB (Focused Ion Beam) or the like and analyzing the cross section using energy dispersive X-ray spectrometry (EDX), EPMA (electron probe microanalysis), etc.

[0452] In EDX measurement, the method of measuring while scanning in the region for two-dimensional evaluation is called EDX surface analysis. In addition, the method of evaluating the atomic concentration distribution in the positive electrode active material by linear scanning and measurement is called line analysis. Sometimes the method of extracting the data of the linear region from the surface analysis of EDX is called line analysis. In addition, the method of measuring without scanning is called point analysis.

[0453] By EDX surface analysis (e.g., element mapping), the concentration of added elements in the surface layer 100a, bulk 100b, and near the grain boundary 101 of the positive electrode active material 100 can be quantitatively analyzed. In addition, by EDX line analysis, the concentration distribution and maximum value of the added element can be analyzed. In addition, in the analysis of the sample thinning such as STEM-EDX, the concentration distribution in the depth direction from the surface of the positive electrode active material in a specific area to the center can be analyzed without being affected by the distribution in the depth direction, so it is preferred.

[0454] Therefore, when EDX surface analysis or EDX point analysis is performed on the positive electrode active material 100 of one embodiment of the present invention, the concentration of each additional element, especially the additional element X, is preferably higher in the surface layer portion 100 a than in the bulk portion 100 b .

[0455] For example, when performing EDX surface analysis or EDX point analysis on the positive electrode active material 100 containing magnesium as an added element, the magnesium concentration of the surface portion 100a is preferably higher than the magnesium concentration of the bulk 100b. In addition, when performing EDX line analysis, the magnesium concentration peak of the surface portion 100a preferably appears within a depth range of 3nm from the surface of the positive electrode active material 100 to the center, more preferably within a depth range of 1nm, and further preferably within a depth range of 0.5nm. In addition, the concentration of magnesium is preferably reduced to less than 60% of the peak concentration at a point from the peak top to a depth of 1nm. In addition, it is preferably reduced to less than 30% of the peak concentration at a point from the peak top to a depth of 2nm. The concentration peak described here is the maximum value of the concentration.

[0456] In the positive electrode active material 100 containing magnesium and fluorine as additive elements, the distribution of fluorine preferably overlaps with the distribution of magnesium. For example, the difference in the depth direction between the fluorine concentration peak and the magnesium concentration peak is preferably within 10 nm, more preferably within 3 nm, and further preferably within 1 nm.

[0457] In addition, when performing EDX line analysis, the fluorine concentration peak of the surface portion 100a preferably appears within a depth range of 3nm from the surface of the positive electrode active material 100 to the center, more preferably within a depth range of 1nm, and further preferably within a depth range of 0.5nm. In addition, the fluorine concentration peak is preferably slightly closer to the surface side than the magnesium concentration peak, and the resistance to fluorine is improved at this time, so it is preferred. For example, the fluorine concentration peak is preferably closer to the surface side by more than 0.5nm than the magnesium concentration peak, and more preferably closer to the surface side by more than 1.5nm than the magnesium concentration peak.

[0458] In addition, in the positive electrode active material 100 containing nickel as an added element, the nickel concentration peak of the surface portion 100a preferably appears within a depth range of 3nm from the surface to the center of the positive electrode active material 100, more preferably within a depth range of 1nm, and further preferably within a depth range of 0.5nm. In addition, in the positive electrode active material 100 containing magnesium and nickel, the distribution of nickel preferably overlaps with the distribution of magnesium. For example, the difference in the depth direction of the nickel concentration peak and the magnesium concentration peak is preferably within 10nm, more preferably within 3nm, and further preferably within 1nm.

[0459] In addition, when the positive electrode active material 100 includes aluminum as an additive element, when performing EDX line analysis, the concentration peak of magnesium, nickel or fluorine is closer to the surface than the aluminum concentration peak of the surface portion 100a. For example, the aluminum concentration peak preferably appears in the range of a depth of 0.5 nm or more and 50 nm or less from the surface of the positive electrode active material 100 to the center, and more preferably appears in the range of a depth of 5 nm or more and 50 nm or less.

[0460] In addition, when the positive electrode active material 100 is subjected to EDX line analysis, surface analysis or point analysis, the ratio of the number of atoms of magnesium Mg to cobalt Co in the magnesium concentration peak (Mg / Co) is preferably 0.05 or more and 0.6 or less, more preferably 0.1 or more and 0.4 or less. The ratio of the number of atoms of aluminum Al to cobalt Co in the aluminum concentration peak (Al / Co) is preferably 0.05 or more and 0.6 or less, more preferably 0.1 or more and 0.45 or less. The ratio of the number of atoms of nickel Ni to cobalt Co in the nickel concentration peak (Ni / Co) is preferably 0 or more and 0.2 or less, more preferably 0.01 or more and 0.1 or less. The ratio of the number of atoms of fluorine F to cobalt Co in the fluorine concentration peak (F / Co) is preferably 0 or more and 1.6 or less, more preferably 0.1 or more and 1.4 or less.

[0461] From the EDX line analysis results, the surface of the positive electrode active material 100 can be estimated as follows: The point where the amount of an element uniformly present in the bulk 100b of the positive electrode active material 100, such as oxygen or cobalt, becomes 1 / 2 of the detected amount of the bulk 100b is the surface.

[0462] The positive electrode active material 100 is a composite oxide, so the surface can be estimated using the detected amount of oxygen. Specifically, first, the average value of the oxygen concentration is obtained from the region where the detected amount of oxygen in the bulk 100b is stable. ave At this time, when oxygen O due to chemical adsorption or background is detected in a region that can be judged to be clearly outside the surface, bg When O is subtracted from the measured value bg To find the average oxygen concentration O ave It can be inferred that the average value O ave The value of 1 / 2 is closest to 1 / 2O ave The measurement point of the measured value is the surface of the positive electrode active material.

[0463] In addition, the surface can be estimated in the same manner as described above using the detected amount of cobalt. Alternatively, the surface can be estimated in the same manner using the sum of the detected amounts of multiple transition metals. The detected amount of transition metals such as cobalt is not easily affected by chemical adsorption, which is very suitable for surface estimation.

[0464] When the positive electrode active material 100 is subjected to line analysis or surface analysis, the ratio of the number of atoms of the added element A to cobalt Co near the grain boundary 101 (A / Co) is preferably greater than 0.020 and less than 0.50. More preferably, it is greater than 0.025 and less than 0.30. Further preferably, it is greater than 0.030 and less than 0.20. Alternatively, it is preferably greater than 0.020 and less than 0.30. Alternatively, it is preferably greater than 0.020 and less than 0.20. Alternatively, it is preferably greater than 0.025 and less than 0.50. Alternatively, it is preferably greater than 0.025 and less than 0.20. Alternatively, it is preferably greater than 0.030 and less than 0.50. Alternatively, it is preferably greater than 0.030 and less than 0.30.

[0465] For example, when the added element is magnesium, when the positive electrode active material 100 is subjected to line analysis or surface analysis, the ratio of the number of atoms of magnesium to cobalt near the grain boundary 101 (Mg / Co) is preferably greater than 0.020 and less than 0.50. More preferably, it is greater than 0.025 and less than 0.30. Further preferably, it is greater than 0.030 and less than 0.20. Alternatively, it is preferably greater than 0.020 and less than 0.30. Alternatively, it is preferably greater than 0.020 and less than 0.20. Alternatively, it is preferably greater than 0.025 and less than 0.50. Alternatively, it is preferably greater than 0.025 and less than 0.20. Alternatively, it is preferably greater than 0.030 and less than 0.50. Alternatively, it is preferably greater than 0.030 and less than 0.30. When multiple portions of the positive electrode active material 100, for example three or more portions, are within the above range, it can be said that the additional element is not attached to a narrow range on the surface of the positive electrode active material 100 but is widely distributed in the surface layer 100a of the positive electrode active material 100 at an appropriate concentration.

[0466] {EPMA}

[0467] EPMA can also quantify elements. In surface analysis, the distribution of each element can be analyzed.

[0468] As with the analysis results of EDX, when the cross section of the positive electrode active material 100 of one embodiment of the present invention is subjected to EPMA surface analysis, one or more of the added elements preferably have a concentration gradient. In addition, it is more preferred that the depth of the concentration peak from the surface is different according to the added element. The preferred range of the concentration peak of each added element is also the same as that of the EDX analysis.

[0469] Note that in EPMA, the area at a depth of about 1 μm from the surface is analyzed. Therefore, sometimes the quantitative value of each element is different from the measurement result measured by other analysis methods. For example, when analyzing the surface of the positive electrode active material 100 by EPMA, sometimes the concentration of each added element present in the surface layer 100a is lower than the result measured by XPS.

[0470] {Raman spectroscopy}

[0471] As described above, at least a part of the surface layer portion 100a of the positive electrode active material 100 of one embodiment of the present invention preferably has a rock salt type crystal structure. Therefore, when analyzing the positive electrode active material 100 and the positive electrode including the positive electrode active material 100 by Raman spectroscopy, a crystal structure of a cubic system such as a rock salt type crystal structure is preferably observed in addition to the layered rock salt type crystal structure. In the STEM image and the nano-beam electron diffraction pattern described later, unless cobalt substituting for the lithium position and cobalt present at the oxygen tetracoordination position exist at a certain frequency in the depth direction during observation, bright spots cannot be detected in the STEM image and the nano-beam electron diffraction pattern. On the other hand, Raman spectroscopy is an analysis for detecting the vibration mode of bonds such as Co-O, so sometimes a peak of the wave number of the corresponding vibration mode is observed even when the amount of the corresponding Co-O bond present is small. And Raman spectroscopy can measure a range of about several μm in area and about 1 μm in depth of the surface layer portion, so a state where the Co-O bond exists only on the particle surface can be detected with high sensitivity. 2 , a state where the Co-O bond exists only on the particle surface can be detected with high sensitivity.

[0472] For example, when the laser wavelength is 532 nm, in LiCoO2 having a layered rock salt type crystal structure, peaks are observed at 470 cm -1 to 490 cm -1 , 580 cm -1 to 600 cm -1 (vibration mode: E g , A 1g ). On the other hand, in cubic system CoO x (0 < x < 1) (rock salt type crystal structure Co 1-y O (0 < y < 1) or spinel type crystal structure Co3O4), a peak is observed at 665 cm -1 to 685 cm -1 (vibration mode: A 1g ).

[0473] Therefore, when the integrated intensities of the peaks in the range of 470 cm -1 to 490 cm -1 , the peaks in the range of 580 cm -1 to 600 cm -1 , and the peaks in the range of 665 cm -1 to 685 cm -1 are denoted as I1, I2, and I3, respectively, I3 / I2 is preferably 1% or more and 10% or less, and more preferably 3% or more and 9% or less.

[0474] When a crystal structure of a cubic system such as a rock salt type is observed within the above range, it can be said that the surface layer portion 100a of the positive electrode active material 100 has a rock salt type crystal structure within an appropriate range.

[0475] {Nanobeam electron diffraction pattern}

[0476] As with Raman spectroscopy, it is preferred that the characteristics of the layered rock salt type crystal structure and the rock salt type crystal structure are also observed from the nanobeam electron diffraction image. Note that in the STEM image and the nanobeam electron diffraction pattern, in view of the above-mentioned difference in sensitivity, it is preferred that the characteristics of the rock salt type crystal structure on the surface portion 100a, especially on the outermost surface (for example, from the surface to a depth of 1nm) are not too obvious. This is because compared with the case where the outermost surface is covered with a rock salt type crystal structure, the diffusion path of lithium can be further ensured and the function of stabilizing the crystal structure can be stronger when the layered rock salt type crystal structure is maintained and the lithium layer has added elements such as magnesium.

[0477] Therefore, for example, when obtaining a nanobeam electron diffraction pattern of a region at a depth of 1 nm or less from the surface and a nanobeam electron diffraction pattern of a region at a depth of 3 nm to 10 nm, the smaller the difference in lattice constant that can be calculated therefrom is, the better.

[0478] For example, the difference in lattice constants calculated between the measured portion at a depth of 1 nm or less from the surface and the measured portion at a depth of 3 nm or more and 10 nm or less is preferably such that the a-axis is 0.01 nm or less and the c-axis is 0.1 nm or less. In addition, it is more preferred that the a-axis is 0.005 nm or less and the c-axis is 0.06 nm or less. In addition, it is further preferred that the a-axis is 0.004 nm or less and the c-axis is 0.03 nm or less.

[0479] [Additional Features]

[0480] The positive electrode active material 100 may have concave portions, cracks, recessed portions, V-shaped cross sections, etc. These are defects, and when charging and discharging are repeated, cobalt may be dissolved, the crystal structure may collapse, the positive electrode active material 100 may be broken, oxygen may be released, etc. However, in the case of embedding these defects, Fig.10F When the embedded portion 102 is formed as shown, dissolution of cobalt can be suppressed. Therefore, a positive electrode active material 100 having improved reliability and cycle characteristics can be realized.

[0481] As described above, when the positive electrode active material 100 contains excess added elements, there is a concern that the insertion and extraction of lithium may have a negative impact. In addition, there is also a concern that the internal resistance increases and the charge and discharge capacity decreases when the positive electrode active material 100 is used in a secondary battery. On the other hand, when the added elements are insufficient, the added elements are not distributed throughout the surface portion 100a, and it is possible that the effect of fully suppressing the degradation of the crystal structure cannot be obtained. In this way, although the added elements in the positive electrode active material 100 need to have an appropriate concentration, it is not easy to adjust their concentration.

[0482] Thus, when the positive electrode active material 100 has a region where the additive element is concentratedly distributed, a portion of the atoms of the excess additive element is removed from the bulk 100b of the positive electrode active material 100, and a suitable concentration of the additive element can be achieved in the bulk 100b. Thus, the internal resistance increase and the charge and discharge capacity decrease during the manufacture of the secondary battery can be suppressed. The ability to suppress the increase in the internal resistance of the secondary battery is a particularly preferred characteristic in charge and discharge with a large current, for example, charge and discharge with a current of 400 mA / g or more.

[0483] In addition, in the positive electrode active material 100 having a region where the additive element is concentratedly distributed, a certain amount of excess additive element can be mixed in the manufacturing process. This is preferable because the degree of freedom in production is increased.

[0484] Alternatively, a coating may be attached to at least a portion of the surface of the positive electrode active material 100 . Fig.19 FIG. 2 shows an example of a positive electrode active material 100 to which a coating portion 104 is attached. Fig.19 In the embodiment, the covering portion 104 is provided so as to cover the surface layer portion 100a. Note that when the surface of the positive electrode active material 100 has uneven portions, cracks or Fig.10F In the case of the embedded portion 102 shown, the covering portion 104 may be provided in a manner to cover the unevenness, cracks or embedded portion 102 .

[0485] For example, the coating 104 is preferably formed by the deposition of decomposition products of lithium salt and organic electrolyte, etc., as the charge and discharge are repeated. x When x in CoO2 becomes less than 0.24 during charging, by having a covering portion derived from an organic electrolyte on the surface of the positive electrode active material 100, it can be expected that the charge and discharge cycle characteristics will be improved. This is because there are the following reasons: suppressing the increase in impedance on the surface of the positive electrode active material; or suppressing the dissolution of cobalt; etc. The covering portion 104 preferably contains carbon, oxygen and fluorine, for example. In addition, it is easy to obtain a high-quality covering portion when LiBOB and / or SUN (Suberonitrile) is used as an electrolyte. Therefore, the covering portion 104 containing at least one or more than two selected from boron, nitrogen, sulfur and fluorine is sometimes a high-quality covering portion, so it is preferred. In addition, the covering portion 104 may not cover the entire positive electrode active material 100. For example, it is sufficient to cover more than 50% of the surface of the positive electrode active material 100, preferably more than 70%, and more preferably more than 90%. In the portion without a covering portion, fluorine can also be adsorbed on the surface of the positive electrode active material 100.

[0486] At least a part of this embodiment mode can be implemented in combination with other embodiment modes described in this specification as appropriate.

[0487] (Implementation Method 2)

[0488] In this embodiment, an example of a method for producing the positive electrode active material 100 according to one embodiment of the present invention is described.

[0489] In order to produce the positive electrode active material 100 as described in the above embodiment, the method of adding the additive element is important. In addition, it is also important that the bulk 100 b has good crystallinity.

[0490] As a manufacturing process of the positive electrode active material 100, there is a method in which lithium cobalt oxide is synthesized, and then an additive element source is mixed and heat-treated. In addition, a method of synthesizing lithium cobalt oxide containing an additive element by mixing an additive element source together with a cobalt source and a lithium source can also be used. In addition, when not only the lithium cobalt oxide and the additive element source are mixed but also heated, the additive element can be dissolved in the lithium cobalt oxide, so it is preferred. In addition, in order to distribute the additive element well, it is preferably heated sufficiently. Therefore, the heat treatment after mixing the additive element source is important. The heat treatment after mixing the additive element source is sometimes called roasting or annealing.

[0491] However, when the heating temperature is too high, cation mixing occurs and the possibility of magnesium and other additive elements entering the cobalt site increases. x When x in CoO2 is small, the effect of maintaining the R-3m layered rock salt type crystal structure is maintained. In addition, when the heating temperature is too high, there is a concern that cobalt is reduced to become divalent, lithium evaporates, and other adverse effects may occur.

[0492] Therefore, it is preferred to use a material used as a flux together with or as a mixture of an additive element source. A flux is a substance having a lower melting point than lithium cobalt oxide, and the substance has a function as a flux. As a flux, fluorine compounds such as lithium fluoride are preferred. When the flux is added, the melting points of the additive element source and lithium cobalt oxide decrease. By performing a melting point decrease, the additive element can be easily distributed well at a temperature where cation mixing is not likely to occur.

[0493] [Initial heating]

[0494] In addition, it is more preferable to heat the lithium cobalt oxide after synthesizing it and before mixing the additive elements. This heating is sometimes referred to as initial heating.

[0495] By performing the initial heating, lithium is released from a part of the surface layer portion 100 a of the lithium cobalt oxide, so that the distribution of the additive element is improved.

[0496] More specifically, it is believed that the distribution of each additive element is easily made different by initial heating through the following mechanism. First, lithium is separated from a portion of the surface portion 100a by initial heating. Next, lithium cobalt oxide including the surface portion 100a lacking lithium and additive element sources such as a nickel source, an aluminum source, and a magnesium source are mixed and heated. Magnesium among the additive elements is a typical divalent element, and nickel is a transition metal but easily becomes a divalent ion. Therefore, a portion of the surface portion 100a containing Mg is formed. 2+ and Ni 2+ and Co reduced due to lithium deficiency 2+ Note that this phase is formed in a part of the surface layer portion 100a, so it may not be clearly confirmed in an electron microscope such as STEM or an electron diffraction pattern.

[0497] The nickel in the additive element is easily dissolved and diffused into the block 100b when the surface portion 100a of the lithium cobalt oxide is a layered rock salt type, but it is easy to remain in the surface portion 100a when a part of the surface portion 100a is a rock salt type. Therefore, by performing initial heating, the divalent additive elements such as nickel can be easily retained in the surface portion 100a. The effect of this initial heating is particularly large on the surface other than the (001) orientation of the positive electrode active material 100 and its surface portion 100a.

[0498] In addition, in these rock salt types, the bonding distance between metal Me and oxygen (Me—O distance) tends to be longer than that of the layered rock salt type.

[0499] For example, rock salt Ni 0.5 Mg 0.5 The Me-O distance in NiAl2O4 is 0.209nm, and the Me-O distance in rock salt type MgO is 0.211nm. In addition, if a spinel phase is formed in a part of the surface layer 100a, the Me-O distance of spinel NiAl2O4 is 0.20125nm, and the Me-O distance of spinel MgAl2O4 is 0.202nm. The Me-O distances are all over 0.2nm.

[0500] On the other hand, the bonding distance between metals other than lithium and oxygen in the layered rock salt type is shorter than the above distance. For example, the Al-O distance in the layered rock salt type LiAlO2 is 0.1905nm (the Li-O distance is 0.211nm). In addition, the Co-O distance in the layered rock salt type LiCoO2 is 0.19224nm (the Li-O distance is 0.20916nm).

[0501] In addition, according to Shannon ionic radius (see Non-Patent Document 8), the ionic radius of hexacoordinated aluminum is 0.0535 nm, the ionic radius of hexacoordinated oxygen is 0.14 nm, and the total of these is 0.1935 nm.

[0502] Therefore, it can be considered that aluminum exists more stably at sites other than lithium in the layered rock salt type than in the rock salt type. Therefore, aluminum is more easily distributed in deeper regions and / or bulk 100b having layered rock salt than in regions close to the surface having rock salt phases in the surface portion 100a.

[0503] In addition, the initial heating can also be expected to improve the crystallinity of the layered rock salt type crystal structure of the bulk 100 b .

[0504] Therefore, in particular, in order to manufacture x When x in CoO 2 is, for example, 0.15 or more and 0.17 or less, the positive electrode active material 100 having a monoclinic O1(15) type structure preferably undergoes the initial heating.

[0505] However, initial heating is not necessarily required. By controlling the atmosphere, temperature, time, etc. in other heating steps, it is sometimes possible to produce Li x When x in CoO 2 is small, the positive electrode active material 100 has an O3′ type structure and / or a monoclinic O1(15) type structure.

[0506] [Method for producing positive electrode active material 1]

[0507] Next, refer to FIG. 20A to FIG. 20C A method 1 for producing the positive electrode active material 100 that has been initially heated will be described.

[0508] <Step S11>

[0509] exist Fig. 20A In step S11 shown in the figure, a lithium source (Li source) and a cobalt source (Co source) are prepared as starting materials of lithium and transition metal, respectively.

[0510] As the lithium source, a compound containing lithium is preferably used, for example, lithium carbonate, lithium hydroxide, lithium nitrate, lithium fluoride, etc. The purity of the lithium source is preferably high, for example, a material with a purity of 99.99% or more is preferably used.

[0511] As the cobalt source, a compound containing cobalt is preferably used, and for example, cobalt oxide (typically, tricobalt tetraoxide), cobalt hydroxide (typically, cobalt hydroxide), etc. can be used.

[0512] The purity of the cobalt source is preferably high, for example, preferably a material with a purity of 3N (99.9%) or more, preferably 4N (99.99%) or more, more preferably 4N5 (99.995%) or more, and further preferably 5N (99.999%) or more. By using a high-purity material, impurities in the positive electrode active material can be controlled. As a result, the capacity of the secondary battery is improved and / or the reliability of the secondary battery is improved.

[0513] Furthermore, the crystallinity of the cobalt source is preferably high, for example, it preferably has single crystal particles. As a method for evaluating the crystallinity of the cobalt source, there can be cited: evaluation using TEM (transmission electron microscope) images, STEM (scanning transmission electron microscope) images, HAADF-STEM (high angle annular dark field-scanning transmission electron microscopy) images, ABF-STEM (annular bright field scanning transmission electron microscope) images, etc.; or evaluation using X-ray diffraction (XRD), electron diffraction, neutron diffraction, etc. The above-mentioned method for evaluating crystallinity can also be used for evaluating other crystallinities in addition to the cobalt source.

[0514] <Step S12>

[0515] Then, as Fig. 20A In step S12 shown, the lithium source and the cobalt source are crushed and mixed to produce a mixed material. The crushing and mixing can be performed by a dry method or a wet method. The wet method can grind smaller, so it is preferred. When the crushing and mixing are performed by the wet method, a solvent is prepared. As the solvent, ketones such as acetone, alcohols such as ethanol and isopropanol, ether, dioxane, acetonitrile, N-methyl-2-pyrrolidone (NMP), etc. can be used. It is preferred to use a non-protonic solvent that does not react easily with lithium. In this embodiment, dehydrated acetone with a purity of 99.5% or more is used. Preferably, the lithium source and the cobalt source are mixed with dehydrated acetone with a moisture content suppressed to less than 10 ppm and a purity of 99.5% or more for grinding and mixing. By using dehydrated acetone of the above purity, impurities that may be mixed in can be reduced.

[0516] As a unit for crushing and mixing, a ball mill or a sand mill can be used. When using a ball mill, alumina balls or zirconia balls are preferably used as the crushing medium. Zirconia balls are preferred because they have less impurities discharged. In addition, when using a ball mill or a sand mill, in order to suppress contamination from the medium, the circumferential speed is preferably set to 100 mm / s or more and 2000 mm / s or less. In the present embodiment, the circumferential speed is preferably set to 838 mm / s (the number of rotations is 400 rpm, and the diameter of the ball mill is 40 mm) for crushing and mixing.

[0517] <Step S13>

[0518] Then, as Fig. 20AIn step S13 shown, the mixed material is heated. The heating is preferably performed at a temperature of 800°C or higher and 1100°C or lower, more preferably 900°C or higher and 1000°C or lower, and further preferably about 950°C. When the temperature is too low, there is a concern that the decomposition and melting of the lithium source and the cobalt source are insufficient. On the other hand, when the temperature is too high, defects may occur due to the following reasons: lithium evaporates from the lithium source; and / or cobalt is excessively reduced; etc. For example, cobalt changes from trivalent to divalent, causing oxygen defects, etc.

[0519] If the heating time is too short, lithium cobalt oxide is not synthesized, but if the heating time is too long, productivity decreases. For example, the heating time is preferably 1 hour to 100 hours, more preferably 2 hours to 20 hours.

[0520] Although it varies depending on the temperature reached by the heating temperature, the heating rate is preferably 80° C. / h or more and 250° C. / h or less. For example, when heating at 1000° C. for 10 hours, the heating rate is preferably 200° C. / h.

[0521] The heating is preferably performed in an atmosphere with less water such as dry air, for example, preferably in an atmosphere with a dew point of -50°C or less, more preferably in an atmosphere with a dew point of -80°C or less. In the present embodiment, the heating is performed in an atmosphere with a dew point of -93°C. In addition, in order to suppress impurities that may be mixed into the material, the impurity concentrations of CH4, CO, CO2, H2, etc. in the heating atmosphere are preferably all below 5 ppb (parts per billion).

[0522] The heating atmosphere is preferably an oxygen-containing atmosphere. For example, a method of continuously introducing dry air into the reaction chamber can be cited. In this case, the flow rate of the dry air is preferably 10 L / min. A method of continuously introducing oxygen into the reaction chamber so that the oxygen flows through the reaction chamber is called "flowing".

[0523] When an oxygen-containing atmosphere is used as the heating atmosphere, a non-flowing method may also be used. For example, a method may be used in which the reaction chamber is first depressurized and then filled with oxygen (also referred to as "purging") to prevent the oxygen from entering or leaving the reaction chamber. For example, the reaction chamber may be depressurized to -970 hPa and then continuously filled with oxygen until the pressure reaches 50 hPa.

[0524] After heating, the material may be cooled naturally. The cooling time from the specified temperature to room temperature is preferably within a range of 10 hours to 50 hours, for example, preferably 80°C / h to 250°C / h, more preferably 180°C / h to 210°C / h. Note that it is not necessary to cool to room temperature, but only to a temperature allowed by the next step.

[0525] The heating in this step can be performed using a rotary kiln or a roller hearth kiln. Heating using a continuous or batch-type rotary kiln can be performed while stirring.

[0526] The crucible used for heating is preferably an alumina crucible. The alumina crucible is made of a material that does not easily release impurities. In this embodiment, an alumina crucible with a purity of 99.9% is used. It is preferred to heat the crucible with a lid on. This can prevent the volatilization or sublimation of the material. As for covering the lid, as long as the volatilization or sublimation of the material can be prevented during the heating and cooling of this step, it is not necessary to seal the crucible with a lid. For example, as described above, this step can also be performed by filling oxygen into the reaction chamber without sealing the crucible.

[0527] In addition, compared with a new crucible, a half-new crucible is preferably used as a crucible. In this specification, etc., a new crucible refers to a crucible in which a material containing lithium, transition metal M and / or an additive element is placed and heated for less than two times. In addition, a half-new crucible refers to a crucible that has been heated by placing a material containing lithium, transition metal M and / or an additive element for more than three times. This is because: when a new crucible is used, there is a concern that a part of the material such as lithium fluoride is absorbed or diffused, moved and / or attached to the sagger during heating. Thus, when a part of the material is lost due to the above reasons, the possibility that the element distribution of the surface layer of the positive active material is not within the preferred range increases. On the other hand, this possibility is very low in a half-new crucible.

[0528] After the heating is completed, it can also be crushed and screened as needed. When recovering the heated material, it can also be moved from the crucible to the mortar first, and then the heated material can be recovered. In addition, the mortar is preferably an alumina mortar. An alumina mortar is not easy to release impurities. Specifically, a mortar with an alumina purity of 90% or more, preferably 99% or more, is used. In addition, the same heating conditions as step S13 can be used in the heating process described later other than step S13.

[0529] <Step S14>

[0530] Through the above steps, it is possible to synthesize Fig. 20A When the median particle size (D50) is used as the particle size of the lithium cobalt oxide, the lithium cobalt oxide is preferably pulverized in order to obtain a positive electrode active material 100 having a relatively small median particle size (D50).

[0531] As shown in steps S11 to S14, an example of producing the composite oxide by a solid phase method is shown, but the composite oxide may also be produced by a coprecipitation method. Alternatively, the composite oxide may also be produced by a hydrothermal method.

[0532] <Step S15>

[0533] Then, as Fig. 20A In step S15 shown, lithium cobalt oxide is heated. This heating is the first heating of lithium cobalt oxide, so the heating in step S15 is sometimes called initial heating. Alternatively, this heating is performed before step S20 shown below, so it is sometimes called preheating treatment or pretreatment. The crucible and / or lid used in this step are the same as those used in step S13. Although the following effects can be expected by initial heating, initial heating is not necessary when obtaining a positive electrode active material in one embodiment of the present invention.

[0534] As described above, lithium is separated from a portion of the surface layer 100a of the lithium cobalt oxide by initial heating. In addition, the effect of improving the crystallinity of the block 100b can be expected. In addition, impurities are sometimes mixed in the lithium source and / or cobalt source prepared in step S11, etc. By performing initial heating, impurities in the lithium cobalt oxide completed in step S14 can be reduced.

[0535] After the initial heating, the surface of the lithium cobalt oxide is also smoothed. A smooth surface means that there are fewer bumps and the composite oxide is curved as a whole and the corners are curved. In addition, a state in which there are fewer foreign matters attached to the surface is called "smooth". It is believed that foreign matters are the cause of bumps and bumps, and preferably do not attach to the surface.

[0536] In the above-mentioned initial heating, it is not necessary to prepare a lithium source, or it is not necessary to prepare an additive element source, or it is not necessary to prepare a material used as a flux.

[0537] When the heating time of this step is too short, the full effect cannot be obtained, but when the heating time is too long, the productivity decreases. For example, it can be implemented by selecting from the heating conditions described in step S13. Supplementary explanation of the heating conditions: In order to maintain the crystal structure of the composite oxide, the heating temperature of this step is preferably lower than the temperature of step S13. In addition, in order to maintain the crystal structure of the composite oxide, the heating time of this step is preferably shorter than the heating time of step S13. For example, it is preferred to heat at a temperature of 700°C or more and 1000°C or less for 2 hours or more and 20 hours or less.

[0538] The effect of improving the crystallinity of the bulk body 100 b refers to, for example, an effect of alleviating distortion, deviation, and the like caused by a difference in shrinkage of the lithium cobalt oxide produced in step S13 .

[0539] In lithium cobalt oxide, a temperature difference sometimes occurs between the surface and the inside of the lithium cobalt oxide due to the heating in step S13. Sometimes the temperature difference causes a shrinkage difference. It can also be considered that the shrinkage difference occurs because the fluidity between the surface and the inside is different according to the temperature difference. Due to the energy related to the shrinkage difference, a difference in internal stress occurs in the lithium cobalt oxide. The difference in internal stress is also called distortion, and this energy is sometimes called distortion energy. It can be considered that the internal stress is removed by the initial heating in step S15, in other words, the distortion energy is uniformized by the initial heating in step S15. When the distortion energy is uniformized, the distortion of the lithium cobalt oxide is alleviated. Therefore, the surface of the lithium cobalt oxide may become smooth. It can also be said that the surface is improved. In other words, it can be considered that the shrinkage difference in the lithium cobalt oxide generated by step S15 is relaxed, so that the surface of the composite oxide becomes smooth.

[0540] In addition, the shrinkage difference sometimes leads to the generation of small deviations in the above-mentioned lithium cobalt oxide, such as the generation of crystal deviations. In order to reduce this deviation, it is preferred to perform this process. Through this process, it is possible to make the deviation of the above-mentioned composite oxide uniform. When the deviation is uniformized, the surface of the composite oxide may become smooth. It can also be said that the crystal particles are arranged. In other words, it can be considered that: through step S15, the deviation of crystals etc. generated in the composite oxide is alleviated, so that the surface of the composite oxide becomes smooth.

[0541] By using lithium cobalt oxide having a smooth surface as a positive electrode active material, deterioration during charge and discharge as a secondary battery is reduced, and cracking of the positive electrode active material can be prevented.

[0542] In addition, pre-synthesized lithium cobalt oxide may be used in step S14. In this case, steps S11 to S13 may be omitted. By performing step S15 on the pre-synthesized lithium cobalt oxide, lithium cobalt oxide with a smooth surface may be obtained.

[0543] <Step S20>

[0544] Next, as shown in step S20, it is preferred to add the additive element A to the initially heated lithium cobalt oxide. When the additive element A is added to the initially heated lithium cobalt oxide, the additive element A can be added uniformly. Therefore, it is preferred to perform the initial heating first and then add the additive element A. Fig. 20B and Fig. 20C Describe the steps for adding the additional element A.

[0545] <Step S21>

[0546] exist Fig. 20B In step S21 shown, a source of an additive element A (source A) to be added to lithium cobalt oxide is prepared. In addition to the source of the additive element A, a lithium source may also be prepared.

[0547] As the additive element A, the additive elements described in the above embodiment, such as the additive element X and the additive element Y, can be used. Specifically, one or more selected from magnesium, fluorine, nickel, aluminum, titanium, zirconium, vanadium, iron, manganese, chromium, niobium, arsenic, zinc, silicon, sulfur, phosphorus and boron can be used. In addition, one or two selected from bromine and beryllium can also be used.

[0548] When magnesium is selected as the additive element, the additive element source may be referred to as a magnesium source. As the magnesium source, magnesium fluoride, magnesium oxide, magnesium hydroxide, magnesium carbonate, etc. may be used. In addition, a plurality of the above magnesium sources may be used.

[0549] When fluorine is selected as an additive element, the additive element source may be referred to as a fluorine source. As the fluorine source, for example, lithium fluoride (LiF), magnesium fluoride (MgF2), aluminum fluoride (AlF3), titanium fluoride (TiF4), cobalt fluoride (CoF2, CoF3), nickel fluoride (NiF2), zirconium fluoride (ZrF4), vanadium fluoride (VF5), manganese fluoride, iron fluoride, chromium fluoride, niobium fluoride, zinc fluoride (ZnF2), calcium fluoride (CaF2), sodium fluoride (NaF), potassium fluoride (KF), barium fluoride (BaF2), cerium fluoride (CeF3, CeF4), lanthanum fluoride (LaF3) or sodium aluminum hexafluoride (Na3AlF6) may be used. Among them, lithium fluoride has a relatively low melting point of 848°C and is easily melted in the heating process described later, so it is preferred.

[0550] Magnesium fluoride can be used as both a fluorine source and a magnesium source. In addition, lithium fluoride can also be used as a lithium source. As another lithium source used in step S21, there is lithium carbonate.

[0551] In addition, the fluorine source may be a gas, and fluorine (F2), carbon fluoride, sulfur fluoride or oxyfluoride (OF2, O2F2, O3F2, O4F2, O5F2, O6F2, O2F) or the like may be mixed in the atmosphere in the heating step described later. In addition, a plurality of the above fluorine sources may be used.

[0552] In the present embodiment, lithium fluoride (LiF) is prepared as a fluorine source, and magnesium fluoride (MgF2) is prepared as a fluorine source and a magnesium source. When lithium fluoride and magnesium fluoride are mixed at a molar ratio of about LiF:MgF2=65:35, it is most effective in lowering the melting point. On the other hand, when there is more lithium fluoride, there is too much lithium and the cycle characteristics may be deteriorated. Therefore, the molar ratio of lithium fluoride and magnesium fluoride is preferably LiF:MgF2=x:1 (0≤x≤1.9), more preferably LiF:MgF2=x:1 (0.1≤x≤0.5), and further preferably LiF:MgF2=x:1 (near x=0.33). In addition, in this specification, etc., near refers to a value greater than 0.9 times and less than 1.1 times its value.

[0553] <Step S22>

[0554] Then, in Fig. 20B In step S22, the magnesium source and the fluorine source are pulverized and mixed. This step can be performed by selecting from the pulverization and mixing conditions described in step S12.

[0555] <Step S23>

[0556] Then, in Fig. 20B In step S23, the pulverized and mixed materials can be recovered to obtain a source of the additive element A (source A). The source of the additive element A shown in step S23 includes a plurality of starting materials and can be called a mixture.

[0557] The median particle size (D50) of the particle size of the above mixture is preferably 600 nm or more and 10 μm or less, more preferably 1 μm or more and 5 μm or less. The median particle size (D50) when one material is used as an additive element source is also preferably 600 nm or more and 10 μm or less, more preferably 1 μm or more and 5 μm or less.

[0558] When the above-mentioned micronized mixture (including the case where the additive element is one) is used, it is easy to uniformly adhere the mixture to the surface of the lithium cobalt oxide particles when mixed with lithium cobalt oxide in the subsequent process. When the mixture is uniformly attached to the surface of the lithium cobalt oxide particles, it is easy to uniformly distribute or diffuse the additive element in the surface layer 100a of the lithium cobalt oxide after heating, so it is preferred.

[0559] <Step S21>

[0560] use Fig. 20C Description and Fig. 20B Different processes. Fig. 20C In step S21 shown, four sources of additive elements are prepared to be added to lithium cobalt oxide. That is, Fig. 20C The type of added element source and Fig. 20B In addition to adding element sources, you can also prepare a lithium source.

[0561] As four sources of additive elements, a magnesium source (Mg source), a fluorine source (F source), a nickel source (Ni source) and an aluminum source (Al source) are prepared. The magnesium source and the fluorine source can be obtained from Fig. 20B As the nickel source, nickel oxide, nickel hydroxide, etc. can be used. As the aluminum source, aluminum oxide, aluminum hydroxide, etc. can be used.

[0562] <Step S22 and Step S23>

[0563] Fig. 20C Steps S22 and S23 shown in FIG. Fig. 20B The steps described in are the same.

[0564] <Step S31>

[0565] Then, in Fig. 20A In step S31, lithium cobalt oxide and additive element source A source (A source) are mixed. The ratio of the number of atoms of cobalt Co in lithium cobalt oxide to the number of atoms of magnesium Mg in additive element source A is preferably Co:Mg=100:y (0.1≤y≤6), and more preferably M:Mg=100:y (0.3≤y≤3).

[0566] In order not to damage the shape of the lithium cobalt oxide particles, the mixing of step S31 is preferably performed under milder conditions than the mixing of step S12. For example, it is preferably performed under conditions with fewer rotations or shorter time than the mixing of step S12. In addition, it can be said that the dry method is a milder condition than the wet method. For example, a ball mill, a sand mill, etc. can be used for mixing. When a ball mill is used, for example, zirconia balls are preferably used as the medium.

[0567] In the present embodiment, the mixing is performed by a dry method at 150 rpm for 1 hour using a ball mill using zirconia balls having a diameter of 1 mm. The mixing is performed in a dry room having a dew point of -100°C or higher and -10°C or lower.

[0568] <Step S32>

[0569] Then, in Fig. 20A In step S32, the mixed materials are recovered to obtain a mixture 903. When recovered, the materials may be sieved after being crushed as needed.

[0570] Note that FIG. 20A to FIG. 20C The manufacturing method of adding the additive element after the initial heating is described in the above, but the present invention is not limited to the above method. The additive element can be added at other time sequences or added in multiple times. In addition, the time sequence can also be changed according to the additive element.

[0571] For example, FIG. 21A to FIG. 21C As shown, the additional element may be added to the lithium source and the cobalt source at the stage of step S11, that is, at the stage of the starting material of the composite oxide. Fig.21A A flow chart of adding a magnesium source to a lithium source and a cobalt source is shown. Fig.21B A flow chart of adding a magnesium source and an aluminum source to a lithium source and a cobalt source is shown. Fig. 21C A flow chart of adding a magnesium source and a nickel source to a lithium source and a cobalt source is shown. FIG. 21A to FIG. 21C The added element sources shown are examples only.

[0572] After step S12, lithium cobalt oxide containing the additive element can be obtained in step S13. The distribution of the additive element can be controlled according to the addition sequence of the additive element. FIG. 21A to FIG. 21CThe additional element added in this way is expected to be located inside the positive electrode active material 100. FIG. 21A to FIG. 21C In the process shown in FIG. 1 , there is no need to separate the process of step S11 to step S14 and the process of step S21 to step S23, so the above method can be said to be simple and highly productive. FIG. 21A to FIG. 21C In the process shown, a new additional element may also be added in step S20.

[0573] Alternatively, lithium cobalt oxide to which a part of the additive element has been added in advance may be used. For example, when lithium cobalt oxide to which magnesium and fluorine have been added is used, steps S11 to S14 and part of step S20 may be omitted. The above method can be said to be a simple method with high productivity.

[0574] Alternatively, the lithium cobalt oxide to which magnesium and fluorine have been added in advance may be heated in step S15, and then a magnesium source and a fluorine source or a magnesium source, a fluorine source, a nickel source, and an aluminum source may be added as in step S20.

[0575] <Step S33>

[0576] Then, in Fig. 20A In step S33 shown, the mixture 903 is heated. The heating conditions described in step S13 can be selected and implemented. The heating time is preferably more than 2 hours. At this time, in order to increase the oxygen partial pressure of the heating atmosphere, the pressure in the furnace can also be greater than the atmospheric pressure. This is because: when the oxygen partial pressure of the heating atmosphere is insufficient, cobalt and the like are reduced, and lithium cobaltate and the like may not be able to maintain the layered rock salt type crystal structure.

[0577] Here, the heating temperature is supplemented. The lower limit of the heating temperature in step S33 needs to be above the temperature at which the reaction between lithium cobalt oxide and the additive element source progresses. The reaction progress temperature can be set to the temperature at which the mutual diffusion of the elements contained in the lithium cobalt oxide and the additive element source occurs, and can also be lower than the melting temperature of the above-mentioned materials. Taking oxide as an example, it is known that from the melting temperature T m 0.757 times (Taman temperature T d ) solid phase diffusion occurs. Therefore, the heating temperature in step S33 can be set to 650°C or above.

[0578] Of course, the reaction is more likely to proceed when the temperature is set above the temperature at which one or more of the materials selected from the mixture 903 are melted. For example, when LiF and MgF2 are included as the additive element source, the eutectic point of LiF and MgF2 is around 742°C, so the lower limit of the heating temperature in step S33 is preferably set to 742°C or above.

[0579] In addition, a mixture 903 obtained by mixing LiCoO2:LiF:MgF2=100:0.33:1 (molar ratio) observed an endothermic peak at around 830° C. in differential scanning calorimetry (DSC measurement). Therefore, the lower limit of the heating temperature is more preferably set to 830° C. or more.

[0580] A higher heating temperature is preferred because the reaction proceeds more easily, the heating time is shortened, and the productivity is improved.

[0581] The upper limit of the heating temperature is set to be lower than the decomposition temperature of lithium cobalt oxide (1130°C). At a temperature near the decomposition temperature, slight decomposition of lithium cobalt oxide may occur. Therefore, it is more preferably 1000°C or lower, further preferably 950°C or lower, and further preferably 900°C or lower.

[0582] In summary, the heating temperature of step S33 is preferably 650°C or higher and 1130°C or lower, more preferably 650°C or higher and 1000°C or lower, further preferably 650°C or higher and 950°C or lower, and further preferably 650°C or higher and 900°C or lower. In addition, it is preferably 742°C or higher and 1130°C or lower, more preferably 742°C or higher and 1000°C or lower, further preferably 742°C or higher and 950°C or lower, and further preferably 742°C or higher and 900°C or lower. In addition, it is preferably 800°C or higher and 1100°C or lower, preferably 830°C or higher and 1130°C or lower, further preferably 830°C or higher and 1000°C or lower, further preferably 830°C or higher and 950°C or lower, and further preferably 830°C or higher and 900°C or lower. In addition, the heating temperature of step S33 is preferably lower than the heating temperature of step S13.

[0583] Here, use Fig.24 An example of a heating furnace used in step S33 will be described.

[0584] Fig.24The heating furnace 220 shown includes a space 202 in the heating furnace, a hot plate 204, a pressure gauge 221, a heater part 206 and a heat insulator 208. It is more preferable to cover the container 216 equivalent to a crucible or a sagger with a lid 218 for heating. By adopting this structure, the atmosphere in the space 219 formed by the container 216 and the lid 218 can be an atmosphere containing fluoride. By covering the lid during heating to keep the concentration of the gasified fluoride in the space 219 constant or prevent the concentration of the fluoride from decreasing, fluorine and magnesium can be contained near the surface of the particles. The volume of the space 219 is smaller than the space 202 in the heating furnace, so when a small amount of fluoride volatilizes, the atmosphere in the space 219 can be an atmosphere containing fluoride. That is, the reaction system can be made into an atmosphere containing fluoride and the amount of fluoride contained in the mixture 903 can be prevented from being greatly reduced. Therefore, LiMO2 can be efficiently generated. In addition, by using the lid 218, the mixture 903 can be simply and cheaply heated in an atmosphere containing fluoride.

[0585] In addition, before heating in the heating furnace space 202, a process of making the atmosphere of the heating furnace space 202 an oxygen-containing atmosphere and a process of placing the container 216 containing the mixture 903 in the heating furnace space 202 are performed. By adopting the order of this process, the mixture 903 can be heated in an atmosphere containing oxygen and fluoride. For example, the gas is made to flow (flow) during heating. The gas can be introduced from the bottom surface of the heating furnace space 202 and discharged to the top surface. In addition, during heating, the heating furnace space 202 can also be sealed to become a closed space to prevent the gas from being transported to the outside (purge).

[0586] There is no limitation on the method of making the atmosphere of the heating furnace space 202 an oxygen-containing atmosphere. For example, there can be mentioned: a method of exhausting the air in the heating furnace space 202 and then introducing an oxygen-containing gas such as oxygen gas or dry air; a method of allowing an oxygen-containing gas such as oxygen gas or dry air to flow for a certain period of time. Among them, it is preferred to introduce oxygen gas (oxygen replacement) after exhausting the air in the heating furnace space 202. In addition, the air in the heating furnace space 202 can also be regarded as an oxygen-containing atmosphere.

[0587] Alternatively, fluoride or the like adhering to the inner wall of the container 216 and the lid 218 may be re-scattered by heating and adhere to the mixture 903 .

[0588] There is no limitation on the process of heating the heating furnace 220. Heating can be performed using a heating mechanism provided in the heating furnace 220.

[0589] In addition, there is no particular limitation on the method of placing the mixture 903 in the container 216, but Fig.24As shown, it is preferred that the top surface of the mixture 903 is flat with respect to the bottom surface of the container 216, that is, the mixture 903 is arranged in such a manner that the height of the top surface of the mixture 903 is uniform.

[0590] The heating in step S31 is preferably performed while controlling the pressure in the furnace using a pressure gauge 221. The furnace is preferably in an atmospheric pressure state or a pressurized state. For example, it is considered that the surface of lithium cobalt oxide melts when exposed to a pressurized state. That is, the surface of lithium cobalt oxide heated together with LiF and MgF2 may be melted by pressurization.

[0591] After the heating in the above step S33, natural cooling can be performed. The cooling time from the specified temperature to room temperature is preferably in the range of more than 10 hours and less than 50 hours. For example, the cooling rate (hereinafter also referred to as the cooling rate) is preferably more than 80°C / h and less than 250°C / h, and more preferably more than 180°C / h and less than 210°C / h. The cooling rate of this step S33 is preferably faster than that of step S13. A fast cooling rate is called rapid cooling. By rapid cooling after the above melting, a shell can be appropriately manufactured. Specifically, a shell with a small width can be manufactured. Note that the temperature at the end of the cooling does not necessarily need to be cooled to room temperature, and it is sufficient to cool to a temperature allowed by the next step.

[0592] In addition, when heating the mixture 903, it is preferred to control the partial pressure of fluorine or fluorine compounds caused by a fluorine source or the like within an appropriate range. The partial pressure can also be controlled by covering the crucible used in this step with a lid and heating it. As described above, the lid can prevent the volatilization or sublimation of the material. Therefore, as long as the volatilization or sublimation of the material can be prevented during the heating to cooling process of this step, it is not necessary to seal the crucible with a lid. For example, this step can also be performed by filling oxygen into the reaction chamber where the crucible is placed without sealing the crucible. A positive electrode active material that appropriately contains fluorine or a fluorine compound can prevent heat and smoke even if an internal short circuit occurs, so it is preferred.

[0593] In the manufacturing method described in this embodiment, some materials such as LiF as a fluorine source are sometimes used as a flux. Through the above function, the heating temperature can be reduced to a temperature lower than the decomposition temperature of lithium cobalt oxide, for example, above 742°C and below 950°C, and additive elements such as magnesium can be distributed in the surface layer, thereby manufacturing a positive electrode active material with good characteristics.

[0594] However, the specific gravity of gaseous LiF is lighter than that of oxygen, so it is possible that LiF volatilizes by heating, and when LiF volatilizes, the LiF in the mixture 903 decreases. At this time, the function of LiF as a flux is reduced. Therefore, it is necessary to suppress the volatilization of LiF while heating. In addition, even if LiF is not used as a fluorine source, it is possible that Li on the surface of LiCoO2 reacts with F as a fluorine source to generate LiF and the LiF volatilizes. Therefore, even if a fluorine compound having a melting point higher than LiF is used, it is also necessary to suppress volatilization.

[0595] Therefore, it is preferable to heat the mixture 903 in an atmosphere containing LiF, that is, to heat the mixture 903 in a state where the partial pressure of LiF in the heating furnace is high. By heating as described above, it is possible to suppress the volatilization of LiF in the mixture 903. In order to suppress the volatilization of LiF, it is preferable to cover the crucible with a lid.

[0596] The heating in this step is preferably performed in a manner that does not cause the particles of the mixture 903 to stick together. When the particles of the mixture 903 stick together during heating, the area of ​​the particles in contact with oxygen in the atmosphere is reduced, and the diffusion path of the added element (such as fluorine) is blocked, so that the added element (such as magnesium and fluorine) may not be easily distributed in the surface layer. In order to promote the reaction with oxygen in the atmosphere, the crucible may not be sealed with a lid.

[0597] In addition, it is considered that when the added element (such as fluorine) is evenly distributed in the surface layer, a smooth and less concave-convex positive electrode active material can be obtained. Therefore, in order to maintain the surface smooth state of the heating through step S15 or further smoothen in this process, it is preferred that the mixture 903 particles are not bonded together.

[0598] In addition, when heating is performed using a rotary kiln, it is preferred to control the flow rate of the oxygen-containing atmosphere in the kiln for heating. For example, it is preferred to reduce the flow rate of the oxygen-containing atmosphere; first purge the atmosphere to introduce the oxygen atmosphere into the kiln, and then stop the atmosphere from flowing; etc. When the oxygen is flowing, the fluorine source may evaporate, which is not preferred in order to maintain the smoothness of the surface.

[0599] When heating is performed using a roller kiln, for example, by covering the container containing the mixture 903 with a lid, the mixture 903 can be heated in a LiF-containing atmosphere. This is similar to the case of covering the crucible with a lid.

[0600] Supplementary description of the heating time. The heating time varies depending on the heating temperature, the size of the lithium cobalt oxide in step S14, the composition, etc. When the lithium cobalt oxide is small, it is sometimes more preferable to heat at a lower temperature or for a shorter time than when the lithium cobalt oxide is large.

[0601] exist Fig. 20AWhen the median particle size (D50) of the lithium cobalt oxide in step S14 is about 12 μm, the heating temperature is preferably set to 650° C. or more and 950° C. or less, for example. The heating time is preferably set to 3 hours or more and 60 hours or less, more preferably 10 hours or more and 30 hours or less, and further preferably about 20 hours. In addition, the cooling time after heating is preferably set to 10 hours or more and 50 hours or less, for example.

[0602] On the other hand, when the median particle size (D50) of the lithium cobalt oxide in step S14 is about 5 μm, the heating temperature is preferably set to 650° C. or more and 950° C. or less, for example. The heating time is preferably set to 1 hour or more and 10 hours or less, and more preferably about 5 hours. In addition, the cooling time after heating is preferably set to 10 hours or more and 50 hours or less, for example.

[0603] <Step S34>

[0604] Then, in Fig. 20A In step S34 shown, the heated material is recovered and ground as needed to obtain the positive electrode active material 100. At this time, it is preferred that the recovered particles are also screened. Through the above steps, the positive electrode active material 100 of one embodiment of the present invention can be manufactured. The surface of the positive electrode active material of one embodiment of the present invention is smooth.

[0605] [Method for producing positive electrode active material 2]

[0606] Next, use Figures 22 to 23C A method 2 for producing a positive electrode active material that is different from the method 1 for producing a positive electrode active material according to one embodiment of the present invention is described. The method 2 for producing a positive electrode active material differs from the method 1 mainly in the number of times the additional element is added and the mixing method. The other descriptions may refer to the description of the method 1.

[0607] exist Fig. 22 In, with Fig. 20A Steps S11 to S15 are performed similarly to prepare lithium cobalt oxide that has been initially heated.

[0608] <Step S20a>

[0609] Next, as shown in step S20a, the additive element A1 is preferably added to the lithium cobalt oxide that has been initially heated.

[0610] <Step S21>

[0611] exist Fig.23A In step S21 shown in the figure, a first source of additional elements is prepared. As the first source of additional elements, it can be obtained from Fig. 20BThe additive element A1 is selected from the additive element A described in step S21. For example, any one or more selected from magnesium, fluorine and calcium can be suitably used as the additive element A1. Fig.23A The case where a magnesium source (Mg source) and a fluorine source (F source) are used as the first additional element source is shown.

[0612] Fig.23A Steps S21 to S23 shown can be Fig. 20B The same conditions are applied to steps S21 to S23 as shown. As a result, an added element source (A1 source) can be obtained in step S23.

[0613] in addition, Fig. 22 Steps S31 to S33 shown in FIG. Fig. 20A The same process is performed from step S31 to step S33 shown.

[0614] <Step S34a>

[0615] Next, the material heated in step S33 is recovered to produce lithium cobalt oxide containing the additive element A1. In order to distinguish it from the composite oxide in step S14, this composite oxide is also referred to as a second composite oxide.

[0616] <Step S40>

[0617] exist Fig. 22 In step S40, an additional element source A2 is added. Fig. 23B and Fig.23C Provide explanation.

[0618] <Step S41>

[0619] exist Fig. 23B Step S41 shown in the figure, prepare a second source of additional elements. As the second source of additional elements, it can be obtained from Fig. 20B The additive element A2 is selected from the additive element A described in step S21. For example, any one or more selected from nickel, titanium, boron, zirconium and aluminum can be suitably used as the additive element A2. Fig. 23B The case where nickel (Ni source) and an aluminum source (Al source) are used as the second additional element source is shown.

[0620] Fig. 23B Steps S41 to S43 shown can be Fig. 20B The same conditions are applied to steps S21 to S23 as shown in the figure. As a result, an added element source (A2 source) can be obtained in step S43.

[0621] in addition, Fig.23C Show use Fig. 23B A variation of the steps described. Fig.23CIn step S41 shown, a nickel source (Ni source) and an aluminum source (Al source) are prepared, and they are pulverized independently in step S42a. As a result, a plurality of second additional element sources (A2 sources) are prepared in step S43. Fig.23C Steps and Fig. 23B The difference is that the additional elements are pulverized separately and independently in step S42a.

[0622] <Step S51 to Step S53>

[0623] then, Fig. 22 Steps S51 to S53 shown in FIG. Fig. 20A The steps S31 to S34 are performed under the same conditions as shown. In addition, the conditions of step S53 related to the heating process can be as follows: the heating temperature is lower than that of step S33 and the heating time is shorter than that of step S33. Through the above process, the positive electrode active material 100 of one embodiment of the present invention can be manufactured in step S54. The surface of the positive electrode active material of one embodiment of the present invention is smooth.

[0624] like Figures 22 to 23C As shown, in manufacturing method 2, the additive element is divided into additive element A1 and additive element A2 and introduced into lithium cobalt oxide. By introducing the additive elements separately, the distribution of each additive element in the depth direction can be changed. For example, the additive element A1 can be distributed in a manner that the concentration in the surface layer is higher than that in the interior, and the additive element A2 can be distributed in a manner that the concentration in the interior is higher than that in the surface layer.

[0625] Through the initial heating described in this embodiment, a positive electrode active material having a smooth surface can be obtained.

[0626] The initial heating shown in this embodiment is performed on lithium cobalt oxide. Therefore, the initial heating preferably adopts the following conditions: the heating temperature is lower than the heating temperature used to obtain lithium cobalt oxide and the heating time is shorter than the heating time used to obtain lithium cobalt oxide. The process of adding additive elements to lithium cobalt oxide is preferably performed after the initial heating. The addition process can be performed in two or more times. The above process sequence can maintain the smoothness of the surface obtained by the initial heating, so it is preferred.

[0627] The positive electrode active material 100 with a smooth surface may be more resistant to physical damage caused by pressure than the positive electrode active material with a rough surface. For example, the positive electrode active material 100 is less likely to be damaged in a test accompanied by pressure such as a needle penetration test, and as a result, safety may be improved.

[0628] At least a part of this embodiment mode can be implemented in combination with other embodiment modes described in this specification as appropriate.

[0629] (Implementation method 3)

[0630] In this embodiment, refer to FIG. 25A to FIG. 25C An example of an electronic device using the secondary battery described in the above embodiment will be described.

[0631] Fig.25A An example of a wearable device is shown. A secondary battery is used as a power source of the wearable device. In addition, in order to improve the splash-proof, waterproof or dust-proof performance when the user uses the wearable device in daily life or outdoors, the user not only wants the wearable device to be able to be charged by wire with the connector part exposed for connection, but also wants to be able to be charged wirelessly.

[0632] For example, the secondary battery of one embodiment of the present invention can be installed in Fig.25A The eyeglass-type device 4000 is shown. The eyeglass-type device 4000 includes a frame 4000a and a display unit 4000b. By installing a secondary battery in the temple portion of the curved frame 4000a, a light-weight, well-balanced eyeglass-type device 4000 with a long continuous use time can be realized. By using a secondary battery of one embodiment of the present invention, the required saving of the frame can be achieved.

[0633] In addition, the secondary battery of one embodiment of the present invention can be installed in the earphone type device 4001. The earphone type device 4001 includes at least a microphone part 4001a, a flexible tube 4001b, and an earphone part 4001c. In addition, a secondary battery can be provided in the flexible tube 4001b and / or in the earphone part 4001c. By using the secondary battery of one embodiment of the present invention, the saving required for the miniaturization of the frame can be achieved.

[0634] The secondary battery of one embodiment of the present invention may be mounted on a device 4002 that can be directly mounted on the body. The secondary battery 4002b may be provided in a thin housing 4002a of the device 4002. By using the secondary battery of one embodiment of the present invention, the housing can be reduced in size.

[0635] The secondary battery of one embodiment of the present invention may be mounted on the device 4003 that can be mounted on clothing. The secondary battery 4003b may be provided in the thin housing 4003a of the device 4003. By using the secondary battery of one embodiment of the present invention, it is possible to realize the saving required for miniaturization of the housing.

[0636] In addition, the secondary battery of one embodiment of the present invention can be mounted on the belt-type device 4006. The belt-type device 4006 includes a belt portion 4006a and a wireless power supply and reception portion 4006b, and the secondary battery can be mounted inside the belt portion 4006a. By using the secondary battery of one embodiment of the present invention, the required saving required for miniaturization of the housing can be achieved.

[0637] In addition, the secondary battery of one embodiment of the present invention can be mounted on the wristwatch type device 4005. The wristwatch type device 4005 includes a display portion 4005a and a strap portion 4005b, and the secondary battery can be set on the display portion 4005a or the strap portion 4005b. By using the secondary battery of one embodiment of the present invention, the saving required for the miniaturization of the frame can be achieved.

[0638] The display unit 4005a can display various information such as e-mails and incoming phone calls in addition to the time.

[0639] In addition, since the wristwatch type device 4005 is a wearable device that is directly wrapped around the wrist, it can also be equipped with sensors for measuring the user's pulse, blood pressure, etc. Thus, the user's exercise volume and health-related data can be stored for health management.

[0640] Fig.25B A perspective view of the wristwatch type device 4005 is shown removed from the wrist.

[0641] in addition, Fig.25C A side view is shown. Fig.25C The case where a secondary battery 913 is built in is shown. The secondary battery 913 is the secondary battery described in Embodiment Mode 4. The secondary battery 913 is provided at a position overlapping with the display portion 4005a, and is small and lightweight.

[0642] Fig.25D An example of wireless earphones is shown. Here, a wireless earphone including a pair of main body 4100a and main body 4100b is shown, but the main body does not need to be a pair.

[0643] The main body 4100a and the main body 4100b include a driver unit 4101, an antenna 4102, and a secondary battery 4103. In addition, a display portion 4104 may be included. In addition, it is preferable to include a substrate on which a circuit such as a wireless IC is mounted, a charging terminal, etc. In addition, a microphone may be included.

[0644] The storage box 4110 includes a secondary battery 4111. In addition, it is preferable to include a substrate on which circuits such as a wireless IC and a charging control IC are mounted, and a charging terminal. In addition, a display unit, buttons, and the like may also be included.

[0645] The main body 4100a and the main body 4100b can communicate with other electronic devices such as smartphones wirelessly. Therefore, the sound data received from other electronic devices can be reproduced on the main body 4100a and the main body 4100b. In addition, when the main body 4100a and the main body 4100b include a microphone, the sound obtained by the microphone can be transmitted to other electronic devices for processing by the electronic devices, and then the sound data can be transmitted to the main body 4100a and the main body 4100b for reproduction. Thus, for example, it can be used as a translation machine.

[0646] In addition, the secondary battery 4103 included in the main body 4100a can be charged from the secondary battery 4111 included in the storage box 4110. As the secondary battery 4111 and the secondary battery 4103, the coin-type secondary battery, the cylindrical secondary battery, etc. of the above-mentioned embodiment can be used. The secondary battery using the positive electrode active material 100 that can be obtained in the embodiment 1 for the positive electrode has a high energy density. By using the positive electrode active material 100 for the secondary battery 4103 and the secondary battery 4111, a space-saving structure that can cope with the miniaturization of wireless headphones can be achieved.

[0647] Fig.26A An example of a sweeping robot is shown. The sweeping robot 6300 includes a display unit 6302 disposed on the surface of a frame 6301, a plurality of cameras 6303 disposed on the side, a brush 6304, an operation button 6305, a secondary battery 6306, various sensors, etc. Although not shown in the figure, the sweeping robot 6300 also has wheels, a suction port, etc. The sweeping robot 6300 can walk automatically, detect garbage 6310, and can suck up garbage from the suction port set below.

[0648] For example, the sweeping robot 6300 can determine whether there are obstacles such as walls, furniture, or steps by analyzing the image captured by the camera 6303. In addition, when objects such as wires that may be entangled with the brush 6304 are found through image analysis, the rotation of the brush 6304 can be stopped. The sweeping robot 6300 is equipped with a secondary battery 6306 and a semiconductor device or an electronic component according to one embodiment of the present invention. By using the secondary battery 6306 according to one embodiment of the present invention in the sweeping robot 6300, the sweeping robot 6300 can be made into an electronic device with a long driving time and high reliability.

[0649] Fig.26B An example of a robot is shown. Fig.26B The robot 6400 shown includes a secondary battery 6409, an illumination sensor 6401, a microphone 6402, an upper camera 6403, a speaker 6404, a display unit 6405, a lower camera 6406, an obstacle sensor 6407, a moving mechanism 6408, a computing device, and the like.

[0650] The microphone 6402 has a function of sensing the user's voice and surrounding sounds, etc. In addition, the speaker 6404 has a function of emitting sound. The robot 6400 can communicate with the user through the microphone 6402 and the speaker 6404.

[0651] The display unit 6405 has the function of displaying various information. The robot 6400 can display the information required by the user on the display unit 6405. The display unit 6405 can also be equipped with a touch panel. In addition, the display unit 6405 can be a detachable information terminal, and by setting it at a fixed position of the robot 6400, it can be charged and send and receive data.

[0652] The upper camera 6403 and the lower camera 6406 have the function of photographing the surrounding environment of the robot 6400. In addition, the obstacle sensor 6407 can detect whether there is an obstacle in the direction of the robot 6400 when it moves forward using the moving mechanism 6408. The robot 6400 can confirm the surrounding environment using the upper camera 6403, the lower camera 6406, and the obstacle sensor 6407 and move safely.

[0653] The robot 6400 includes a secondary battery 6409 according to one embodiment of the present invention and a semiconductor device or an electronic component. By using the secondary battery according to one embodiment of the present invention in the robot 6400, the robot 6400 can be made into an electronic device with a long driving time and high reliability.

[0654] Fig.26C An example of a flying object is shown. Fig.26C The flying object 6500 shown includes a propeller 6501, a camera 6502, a secondary battery 6503, etc., and has an autonomous flight function.

[0655] For example, the image data captured by the camera 6502 is stored in the electronic component 6504. The electronic component 6504 can determine whether there is an obstacle during movement by analyzing the image data. In addition, the electronic component 6504 can be used to infer the remaining power of the battery from the change in the storage capacity of the secondary battery 6503. The flying body 6500 is equipped with a secondary battery 6503 according to one embodiment of the present invention. By using the secondary battery according to one embodiment of the present invention in the flying body 6500, the flying body 6500 can be made into an electronic device with a long driving time and high reliability.

[0656] At least a part of this embodiment mode can be implemented in combination with other embodiment modes described in this specification as appropriate.

[0657] (Implementation 4)

[0658] In this embodiment, an example in which a secondary battery according to one embodiment of the present invention is mounted on a vehicle is described.

[0659] When a secondary battery is installed in a vehicle, a next-generation clean energy vehicle such as a hybrid vehicle (HV), an electric vehicle (EV), or a plug-in hybrid vehicle (PHV) can be realized.

[0660] FIG. 27 shows a vehicle using a secondary battery according to one embodiment of the present invention. Fig.27A The car 8400 shown is an electric car that uses an electric motor as a power source for traveling. Alternatively, the car 8400 is a hybrid car that can use an electric motor or an engine as a power source for traveling. By using one embodiment of the present invention, a vehicle with a long driving distance can be realized. In addition, the car 8400 has a secondary battery. As a secondary battery, Fig.25C and Fig.25D The secondary battery modules shown in FIG. 26 are arranged in the floor portion of the vehicle for use. In addition, a battery pack composed of a plurality of secondary batteries shown in FIG. 26 can be set in the floor portion of the vehicle. The secondary battery not only drives the electric motor 8406, but also supplies power to light-emitting devices such as the headlights 8401 and interior lights (not shown).

[0661] Furthermore, the secondary battery can supply electric power to a display device such as a speedometer and a tachometer included in the automobile 8400. Furthermore, the secondary battery can supply electric power to a semiconductor device such as a navigation system included in the automobile 8400.

[0662] exist Fig.27B In the illustrated automobile 8500 , the secondary battery included in the automobile 8500 can be charged by receiving electric power from an external charging device using a plug-in method and / or a contactless power supply method. Fig.27B The case where a secondary battery 8024 installed in a car 8500 is charged from a ground-mounted charging device 8021 through a cable 8022 is shown. When charging, the charging method and the specifications of the connector, etc., can be appropriately performed in accordance with the provisions of CHAdeMO (registered trademark) or the combined charging system "Combined Charging System". As the charging device 8021, a charging station set up in a commercial facility or a home power supply can also be used. For example, by supplying power from the outside using plug-in technology, the secondary battery 8024 installed in the car 8500 can be charged. Charging can be performed by converting AC power into DC power through a conversion device such as an AC / DC converter.

[0663] In addition, although not shown, the power receiving device can also be installed in the vehicle and the power can be supplied non-contactly from the power transmission device on the ground for charging. When the non-contact power supply method is used, by assembling the power transmission device in the road and / or the outer wall, charging can be performed not only when the vehicle is parked but also when it is driving. In addition, the non-contact power supply method can also be used to send and receive power between vehicles. Furthermore, solar cells can be set on the outside of the vehicle to charge the secondary battery when the vehicle is parked and / or driving. Such non-contact power supply can be achieved using electromagnetic induction and / or magnetic field resonance.

[0664] Fig.27C This is an example of a two-wheeled vehicle using the secondary battery of one embodiment of the present invention. Fig.27C The small motorcycle 8600 shown includes a secondary battery 8602, a rearview mirror 8601, and a turn signal light 8603. The secondary battery 8602 can supply power to the turn signal light 8603.

[0665] In addition, Fig.27C In the illustrated scooter 8600, the secondary battery 8602 can be stored in the storage box 8604 under the seat. Even if the storage box 8604 under the seat is small, the secondary battery 8602 can be stored in the storage box 8604 under the seat. The secondary battery 8602 is detachable, so when charging, the secondary battery 8602 can be brought indoors, charged, and stored before driving.

[0666] By adopting one method of the present invention, the cycle characteristics of the secondary battery can be made excellent and the discharge capacity can be increased. As a result, the secondary battery itself can be made small and lightweight. In addition, if the secondary battery itself can be made small and lightweight, it will help to achieve the lightweight of the vehicle, thereby extending the driving distance. In addition, the secondary battery installed in the vehicle can be used as a power supply source outside the vehicle. In this case, for example, the use of commercial power supplies during peak power demand can be avoided. If the use of commercial power supplies during peak power demand can be avoided, it will help save energy and reduce carbon dioxide emissions. In addition, if the cycle characteristics are excellent, the secondary battery can be used for a long period of time, thereby reducing the use of rare metals such as cobalt.

[0667] At least a part of this embodiment mode can be implemented in combination with other embodiment modes described in this specification as appropriate.

[0668] [Example 1]

[0669] In this example, a positive electrode active material according to one embodiment of the present invention was produced and the results of powder resistance measurement are described.

[0670] [Production of samples]

[0671] In this embodiment, according to Fig. 22 The positive electrode active material is manufactured by the manufacturing method shown in FIG. 23 .

[0672] As Fig. 22 As LiCoO2 in step S14, commercially available lithium cobalt oxide (CELLSEED C-10N manufactured by Nippon Chemical Industry Co., Ltd.) containing cobalt as transition metal M and containing no additive elements is prepared. In this embodiment, the initial heating in step S15 is not performed.

[0673] according to Fig.23A In step S21 shown, LiF is prepared as a F source and MgF2 is prepared as a Mg source. LiF and MgF2 are weighed so that the molar ratio is LiF:MgF2=1:3, dehydrated acetone is added as a solvent, and the mixture is pulverized and mixed by a wet method, and used as an Al source.

[0674] Next, according to Fig. 22 In step S31 and step S32, the A1 source is added to obtain a mixture 903. In step S31, the A1 source is weighed so that the number of atoms of magnesium in the A1 source is 0.5% of the number of atoms of cobalt in the lithium cobalt oxide, and mixed with the lithium cobalt oxide by a dry method.

[0675] Then, as Fig. 22 The mixture 903 is heated in step S33. The heating conditions are 850° C. and 60 hours. During heating, the crucible containing the mixture 903 is covered with a lid. A crucible and a lid formed of alumina are used. Oxygen is supplied (flowing) at a flow rate of 10 L / min to the furnace used for heating in such a way that the crucible is in an oxygen-containing atmosphere. Sample 1-1 is obtained by heating lithium cobalt oxide containing magnesium and fluorine (step S34a). In this embodiment, no A2 source is added.

[0676] In addition, samples 1-2 and 1-3 were manufactured in which the mixing ratio of the A1 source was different from that of sample 1-1.

[0677] As Sample 1-2, the materials were weighed and mixed so that the number of atoms of magnesium in the A1 source was 1.0% of the number of atoms of cobalt in the lithium cobalt oxide.

[0678] In addition, as Sample 1-3, the materials were weighed and mixed so that the number of atoms of magnesium in the A1 source was 6.0% of the number of atoms of cobalt in the lithium cobalt oxide.

[0679] As a comparative example, Sample 2 was prepared separately from the above-mentioned sample. As Sample 2, lithium cobalt oxide (CELLSEED C-10N manufactured by Nippon Chemical Industry Co., Ltd.) was used, and no treatment such as heat treatment was performed.

[0680] [Powder resistance measurement]

[0681] The powder volume resistivity of the manufactured sample is measured. As a method for measuring the powder volume resistivity, the method described in {Powder resistance measurement} of Implementation Example 1 is used. As a measuring device, MCP-PD51 manufactured by Mitsubishi Chemical Analytical Technology Co., Ltd. is used, and as a resistance meter, Loresta-GP or Hiresta-UP is used. As a resistance meter, since the range that can be measured with high accuracy is different between samples, the most suitable resistance meter is selected and used according to the resistivity of the sample. In addition, the measurement is carried out in a general laboratory environment (that is, a temperature environment above 15°C and below 30°C).

[0682] Fig.28A Schematic diagram of a measuring device capable of measuring the volume resistivity of powder. Fig.28B A conceptual diagram showing the four-probe method, Fig.28C A conceptual diagram showing a two-terminal method.

[0683] To measure the powder volume resistivity of each sample, the powder was placed in a measuring unit, and the powder resistance and powder volume were measured under pressure conditions of 13 MPa, 25 MPa, 38 MPa, 51 MPa, and 64 MPa, thereby obtaining the powder volume resistivity of each sample. Fig.29 The results are shown.

[0684] like Fig.29 As shown, in the positive electrode active material containing magnesium and fluorine (samples 1-1, 1-2 and 1-3) of one embodiment of the present invention, the powder resistance increases as the amount of the Al source mixed increases. It is believed that the powder resistance of the positive electrode active material increases because magnesium and the like are located in the shell.

[0685] The higher the powder resistance of the positive electrode active material, the less likely the current will flow through the active material when an internal short circuit occurs, thereby slowing down the reduction reaction rate of the active material. Therefore, it can be inferred that the higher the powder resistance of the positive electrode active material, the less likely it is to release oxygen from the positive electrode active material and decompose the electrolyte when an internal short circuit occurs, thereby suppressing the thermal runaway of the secondary battery, and thus reducing the risk of fire and smoke. Thus, a secondary battery using a positive electrode active material of one embodiment of the present invention can be said to be a secondary battery with excellent safety. In addition, whether thermal runaway, fire and smoke due to internal short circuit are prone to occur can be evaluated by the above-mentioned puncture test, etc.

[0686] In addition, in a secondary battery of one embodiment of the present invention, since both the positive electrode and the negative electrode include a plurality of tabs, the internal resistance of the secondary battery is reduced compared to the existing secondary battery. Therefore, even if a material with high powder resistance is used as the positive electrode active material, the influence on the charge and discharge time can be minimized. Therefore, a secondary battery that is easy to charge and discharge at high speed, has excellent safety, and has suppressed degradation can be realized.

[0687] [Example 2]

[0688] In this example, a positive electrode active material was produced under conditions different from those in the above-described Example 1, and the results of measuring the powder resistance are described.

[0689] [Production of samples]

[0690] In this embodiment, according to Fig. 22 The positive electrode active material is manufactured by the manufacturing method shown in FIG. 23 .

[0691] As Fig. 22 For the LiCoO2 of step S14, lithium cobalt oxide (CELLSEED C-10N manufactured by Nippon Chemical Industry Co., Ltd.) was prepared. As the initial heating of step S15, lithium cobalt oxide was placed in a crucible, covered with a lid, and heated at 850°C for 2 hours in a muffle furnace. After the atmosphere in the muffle furnace became an oxygen atmosphere, no flow (O2 purge) was performed.

[0692] according to Fig.23A In step S21 shown, LiF is prepared as a F source and MgF2 is prepared as a Mg source. MgF2 is weighed in a manner such that LiF:MgF2 is 1:3 (molar ratio). Next, LiF and MgF2 are mixed with dehydrated acetone and stirred at a rotation speed of 400 rpm for 12 hours to produce an additive element source (A1 source). A ball mill is used for mixing, and zirconia balls are used as a pulverizing medium. The capacity of the container of the mixing ball mill is 45 mL. 20 mL of dehydrated acetone, zirconia balls, and 20 mL of acetone are mixed. 22 g of the raw material was mixed with about 9 g of the total of the F source and the Mg source, and then sieved using a 300 μm sieve to obtain the A1 source.

[0693] Next, as step S31, the A1 source is weighed in a manner that the A1 source is 1 mol% of cobalt, and mixed with the initially heated lithium cobalt oxide by a dry method. At this time, stirring is performed under conditions that are milder than the stirring when obtaining the A1 source, that is, stirring is performed at a rotation speed of 150 rpm for 1 hour. Finally, sieving is performed using a 300 μm sieve to obtain a mixture 903 with a uniform particle size (step S32).

[0694] Next, as step S33, the mixture 903 is heated. The heating conditions are 900°C and 20 hours. During heating, the crucible containing the mixture 903 is covered with a lid. The atmosphere in the crucible is made to contain oxygen, and the entry and discharge of the oxygen are shielded (purged). A composite oxide containing Mg and F is obtained by heating (step S34a).

[0695] Next, as step S51, the composite oxide and the additive element source (A2 source) are mixed. Fig.23C In step S41 shown, nickel hydroxide that has been through a pulverizing process is prepared as a nickel source, and aluminum hydroxide that has been through a pulverizing process is prepared as an aluminum source. Nickel hydroxide and aluminum hydroxide are weighed in a manner such that they are 0.5 mol% of lithium cobalt oxide, and mixed with the composite oxide in a dry method. At this time, stirring is performed at a rotation speed of 150 rpm for 1 hour. A ball mill is used for mixing, and zirconium oxide balls are used as pulverizing media. The capacity of the container of the mixing ball mill is 45 mL, and the zirconium oxide balls are placed in a mixing bowl. 22g and a total of about 7.5g of composite oxide, nickel source and aluminum source are mixed together. This is a more gentle stirring condition than when obtaining the Al source. Finally, a 300μm sieve is used to screen and obtain a mixture 904 with a uniform particle size (step S52).

[0696] Finally, as step S53, the mixture 904 is heated. The heating is performed at 850°C for 10 hours. During the heating, the crucible containing the mixture 904 is covered with a lid. The atmosphere in the crucible is made to contain oxygen, and the entry and d...

Claims

1. A wound secondary battery comprising a positive electrode and a negative electrode, in, The positive electrode comprises a positive electrode current collector and a positive electrode active material. The positive electrode current collector includes a first electrode tab and a second electrode tab, The negative electrode comprises a negative electrode current collector and a negative electrode active material. The negative electrode current collector includes a third electrode tab and a fourth electrode tab, The first pole tab is located closer to the winding center than the second pole tab. The third pole tab is located closer to the winding center than the fourth pole tab. The first electrode tab and the second electrode tab are joined at a first joining portion, The third electrode tab is joined to the fourth electrode tab at a second joining portion, The positive electrode active material includes a first region and a second region located on a surface side of the positive electrode active material. The first region comprises lithium, cobalt and oxygen, Furthermore, the second region includes lithium, cobalt, magnesium and oxygen.

2. A wound secondary battery comprising a positive electrode and a negative electrode, in, The positive electrode comprises a positive electrode current collector and a positive electrode active material. The positive electrode current collector includes a first pole tab, a second pole tab and a fifth pole tab, The negative electrode comprises a negative electrode current collector and a negative electrode active material. The negative electrode current collector includes a third electrode tab, a fourth electrode tab and a sixth electrode tab, The first electrode tab, the second electrode tab, and the fifth electrode tab are sequentially connected at a first connection portion from the side closest to the winding center. The third pole tab, the fourth pole tab and the sixth pole tab are sequentially connected at the second connection part from the side close to the winding center. In the first joint portion, the first pole tab and the fifth pole tab are arranged in a manner of clamping the second pole tab. In the second joint portion, the third pole tab and the sixth pole tab are arranged in a manner of clamping the fourth pole tab. The positive electrode active material includes a first region and a second region located on a surface side of the positive electrode active material. The first region comprises lithium, cobalt and oxygen, Furthermore, the second region includes lithium, cobalt, magnesium and oxygen.

3. A wound secondary battery comprising a positive electrode and a negative electrode, in, The positive electrode comprises a positive electrode current collector and a positive electrode active material. The positive electrode current collector includes a first pole tab, a second pole tab and a fifth pole tab, The negative electrode comprises a negative electrode current collector and a negative electrode active material. The negative electrode current collector includes a third electrode tab, a fourth electrode tab and a sixth electrode tab, The first electrode tab, the second electrode tab, and the fifth electrode tab are sequentially connected at a first connection portion from the side closest to the winding center. The third pole tab, the fourth pole tab and the sixth pole tab are sequentially connected at the second connection part from the side close to the winding center. In the first joint portion, the second pole tab and the fifth pole tab are arranged in a manner of clamping the first pole tab. In the second joint portion, the fourth pole tab and the sixth pole tab are arranged in a manner of clamping the third pole tab. The positive electrode active material includes a first region and a second region located on a surface side of the positive electrode active material. The first region comprises lithium, cobalt and oxygen, Furthermore, the second region includes lithium, cobalt, magnesium and oxygen.

4. The secondary battery according to any one of claims 1 to 3, The thickness of the second region is greater than or equal to 2 nm and less than or equal to 5 nm.

5. The secondary battery according to any one of claims 1 to 3, The second region further comprises nickel.

6. The secondary battery according to any one of claims 1 to 3, The second region further comprises fluorine.

7. The secondary battery according to any one of claims 1 to 3, The first region further comprises aluminum.

8. The secondary battery according to any one of claims 1 to 3, The second region is located within 5 nm from the surface of the positive electrode active material.

9. The secondary battery according to any one of claims 1 to 3, The volume resistivity of the powder of the positive electrode active material is 1.0×10 5 Ω·cm or more.

10. The secondary battery according to any one of claims 1 to 3, The volume resistivity of the powder of the positive electrode active material is 2.0×10 5 Ω·cm or more.

11. The secondary battery according to any one of claims 1 to 3, The volume resistivity of the powder of the positive electrode active material is 1.0×10 5 Ω·cm or more, and 2.0×10 5 Ω·cm or more.

Citation Information

Patent Citations

  • Nonaqueous electrolyte secondary battery

    JP2019129009A

  • Method for manufacturing positive electrode active material

    JP2019179758A

  • Positive electrode active material, manufacturing method thereof, and secondary battery

    JP2020140954A

  • Positive electrode active material and method for producing positive electrode active material

    WO2020026078A1